Salinity-alkalinity gradients and biocrust types jointly shape bacterial community assembly and carbon‑nitrogen functioning in dryland soils surrounding playas in northeast Spain - Shubin Lan; Andrew D. Thomas; Stephen Tooth; Ian Saunders (CATENA, 2026)

Could wastewater and clinical surveillance address blind spots in antimicrobial use and AMR? — Evidence from Australia’s Northern Territory - Jinglong Li; Teresa M. Wozniak; Sonja Janson; Michael D. Stephens; Kevin V. Thomas; Jake W. O'Brien (Water Research, 2026)

Analyzing the resilience and development trajectories of water resource systems in transboundary river basins: Lessons from the Mekong - Lin Chai; Liang Yuan; Weijun He; Dagmawi Mulugeta Degefu; Xia Wu; Yang Kong; Thomas Stephen Ramsey (Journal of Hydrology, 2026)

Modelling a decade of daily open water evaporation for existing and planned water storages: A spatially explicit analysis for the Pilbara region of north-western Australia - David L. McJannet; Stephen B. Stewart; Dejun Cai; Thomas G. Van Niel; Tim R. McVicar; Steven D. Boxall (Journal of Hydrology, 2026)

A multi-modal workflow identifies non-γ-glutamyl kokumi peptides in plant proteins - Christina M. Reumiller; Raise Ahmad; Stephen R. Haines; Jihan Kim; Ancy Thomas; David O. Hooks; Debashree Roy; Harjinder Singh; Evelyne Maes (Food Chemistry, 2026)

Preferential solvation drives polysaccharide conformation and viscoelasticity - Pallab Kumar Borah; Joshua E.S.J. Reid; Thomas MacCalman; Amir H. Irani; Daniela Russo; Jens Smiatek; Johannes Hunger; Mona Sarter; Vlad Dinu; Francesca Natali; Michael Boehm; Stephen E. Harding; et al. (Carbohydrate Polymers, 2026)

Beyond evaporites: Assessing hypersalinity using boron-based salinity proxies - Mariano N. Remírez; Geoffrey J. Gilleaudeau; Swapan K. Sahoo; Lucía Guerra; Chelsea Pederson; Eduardo Piovano; Alan J. Kaufman; Adrian Immenhauser; Stephen W. Lokier; Thomas J. Algeo (Chemical Geology, 2026)

Simulating pathways to achieve water-energy-food nexus security in the Yangtze River Delta - Qing Qin; Liang Yuan; Weijun He; Dagmawi Mulugeta Degefu; Xia Wu; Yang Kong; Thomas Stephen Ramsey (Regional Environmental Change, 2026)

Genetic mapping identifies QTL and candidate genes including Mendel's A gene controlling high levels of partial resistance to Fusarium avenaceum in Pea - Stephen O. Awodele; Krishna K. Gali; Bunyamin Tar’an; Sabine Banniza; Syama Chatterton; Ambuj B. Jha; Martine Jean; Navajeet Chakravarthy; Lachagari V. B. Reddy; Thomas D. Warkentin (Theoretical and Applied Genetics, 2026)

Evolution of Cooperative Water-Sharing Strategies Between Finite-Sized Riparian Country Coalitions in Transboundary Rivers Under Stochastic Perturbation - Ruicong Sun; Liang Yuan; Weijun He; Xia Wu; Dagmawi Mulugeta Degefu; Yang Kong; Thomas Stephen Ramsey (Water Resources Management, 2026)

Farm level natural capital accounting to connect on-ground agroforestry decision making with local and global imperatives: A case study in Tasmania, Australia - Daniel S. Mendham; Anthony O'Grady; Stephen Stewart; Jacqueline R. England; Suzanne M. Prober; Thomas Baker; Shaun Brooks; Martin Moroni; Chris Ware; Aysha Fleming; Stephen Roxburgh; Sue Ogilvy; et al. (Agricultural Systems, 2026)

Time to treat the climate and nature crisis as one indivisible global health emergency - Kamran Abbasi; Parveen Ali; Virginia Barbour; Thomas Benfield; Kirsten Bibbins-Domingo; Gregory E. Erhabor; Stephen Hancocks; Richard Horton; Laurie Laybourn-Langton; Robert Mash; Peush Sahni; Wadeia Mohammad Sharief; et al. (Climate and Development, 2026)

A single dose of cannabidiol increases ad libitum energy intake in healthy adults but does not affect postprandial glucose or lipid metabolism - Drusus A. Johnson; Mark P. Funnell; Thomas G. Cable; Donald Peden; Chris J. McLeod; Patrick C. Wheeler; Stephen J. Bailey; Tom Clifford; Liam M. Heaney; Lewis J. James (Appetite, 2026)

Hydro-methanolic extract of Azadirachta Indica (A. Juss) leaves contains benzene, (1-pentyloctyl)- and modulates the reproductive cycle of mature Wistar rats - Ijeoma Chika Chibuogwu; Ahovi Abdulmumin Abdulhamid; Stephen Adakole Ejembi; Samson Eneojo Abalaka; Oluwa Adikpe Agbonu; Barde Thomas; Aliyu Adamu (Next Research, 2026)

Effects of psychostimulants on locomotor activity in the BTBR T+ Itpr3tf/J mouse: implications for comorbid autism spectrum disorder and attention deficit hyperactivity disorder - William E. Fantegrossi; Hannah E. Shaw; Stephen A. Fagot; Kamryn Thomas; Harpreet Kaur (Psychopharmacology, 2026)

Diagnosing Linearity Along the Carbon Cascade in Terrestrial Biosphere Models and Observations - Huanyuan Zhang‐Zheng; Vivek K. Arora; Peter Anthoni; Thomas A. M. Pugh; Atul K. Jain; Wenping Yuan; Yadvinder Malhi; Julia Nabel; Daniel S. Goll; Julia Pongratz; Benjamin Poulter; Anthony P. Walker; et al. (Global Change Biology, 2026)
Elevated carbon dioxide (eCO 2 ) acts as a fertiliser for photosynthesis, driving an increase in gross primary production (GPP). However, it is unclear how effectively increased GPP propagates along the ‘carbon (C) cascade’ to increase net primary production (NPP) and vegetation C stocks ( C veg ) in different plant compartments. Vegetation models were criticised for being overly sensitive to photosynthesis (source‐driven), neglecting sink‐driven processes which may attenuate (or amplify) changes in NPP and vegetation C stocks. Here, we introduce an analytical framework to diagnose linearity ( L ) as ratios of relative changes in linked fluxes and pools. We then apply this framework to 16 models of the TRENDY v11 ensemble and to observation‐based estimates of CO 2 sensitivities. We found widely varying global patterns in L across models. Six models showed a majority of grid cells with larger relative changes in NPP than in GPP ( L NPP:GPP > 1 for > 60% of gridcells), indicating increased vegetation carbon use efficiency under eCO 2 . Only three models had L NPP:GPP 60% of gridcells. Four models showed a majority of gridcells with larger relative changes in estimated steady‐state C veg than in NPP, while five models showed the opposite—in both cases with a large spread of L Cveg*:NPP across grid cells within models. Observations‐based analysis reveals median L Cveg*:NPP C veg , ( L Croot:Cveg > 1) while five models showed the opposite. Most field evidence shows L Croot:Cveg > 1. Widely differing distributions of L among models and links in the C cascade reveal a strong influence of nonlinear behaviour in individual models. However, due to the spread in L , across the whole models ensemble, L deviations from 1 were roughly balanced, leading to an overall linear behaviour of terrestrial C cycle representations in the multi‐model‐mean.

Modernizing America’s National Forest Inventory through a Third Blue Ribbon Panel - Aaron Weiskittel; Dale Hogg; John W. Coulston; Christopher W. Woodall; Holly L. Munro; Hailemariam Temesgen; Timothy Foley; Nathaniel Osborne; Nathaniel Naumann; James Rakestraw; John S. Gunn; Nadia Tase; et al. (Journal of Forestry, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Sulphides to weathering products: metal evolution in seafloor massive sulphide deposits at the Semenov hydrothermal cluster, Mid-Atlantic Ridge - Christian S. Bishop; Pierre Josso; Anna Lichtschlag; Stephen Roberts; Thomas M. Belgrano; J. Andy Milton; Maxime Lesage; Bramley J. Murton (Mineralium Deposita, 2026)
Seafloor massive sulphide (SMS) deposits are potential sources of Cu, Zn, Au and Ag, however, how seafloor weathering affects the content of these metals in the deposits remains poorly understood. Key sulphide weathering products, i.e. Fe-oxyhydroxide and atacamite, can provide insight into metal mobilisation during and after oxidation of sulphides. Ten Fe-oxyhydroxide and three massive sulphide samples from the Semenov hydrothermal cluster (13°30′N, Mid-Atlantic Ridge) were studied; five Fe-oxyhydroxides and all sulphides were analysed by LA-ICP-MS with one sulphide sample analysed by LA-TOF-ICP-MS mapping. Additionally, a sequential leaching study comprising nine Fe-oxyhydroxide samples was performed. Copper is mainly sequestered into the sulphide weathering products atacamite (~ 60%) and Fe-oxyhydroxide (~ 30%). Initially, Fe‑oxyhydroxide precipitates as ferrihydrite, inheriting the metal content of its sulphide precursor (e.g., pyrite or chalcopyrite). Concurrently, Au and Ag are displaced from the sulphide and become concentrated along the oxidation front at the sulphide rims rather than being incorporated into the nascent Fe‑oxyhydroxide. As oxidation proceeds, further breakdown of sulphides such as chalcopyrite, releases Cu that initially adsorb onto existing Fe‑oxyhydroxide. When sufficient mobilised Cu reacts with oxygenated seawater, atacamite precipitates, sequestering the Cu in a stable mineral form, serving as an exploration indicator for Cu‑rich Fe‑oxyhydroxide deposits and underlying massive sulphide deposits. Complete sulphide oxidation leads to the loss of Au and Ag from the solid system into seawater or their migration downwards toward a redox boundary within the SMS mound. Crystallisation of ferrihydrite into more stable goethite liberates substantial amounts of Cu (92%) and Zn (57%). However, the metal loss caused by this process may be limited if released metals re-adsorbed onto adjacent Fe‑oxyhydroxide. These results reveal that Fe‑oxyhydroxides can act as effective long‑term traps for Cu and Zn, suggesting that older, fully or partially oxidised off-axis SMS deposits may retain considerable base metals, expanding exploration areas.

Cold-water fisheries in a warmer world: Increasing temperature redistributes angling effort and concentrates activity in cold-water refugia - Thomas M. Detmer; Stephen F. Jane; Peter B. McIntyre; Clifford E. Kraft (Ambio, 2026)

P-T-t-d constraints on post-orogenic deformation and coeval mineralisation in the Archean-Paleoproterozoic transition zone of the southern West African Craton - Julien Perret; Nicolas Thébaud; Bruno V. Ribeiro; Naomi M. Tucker; Stephen Centrella; Thomas G. Koné; Quentin Masurel (Journal of Structural Geology, 2026)

Submerged nanofiltration for reducing trace organic chemicals in conventionally treated wastewater - Son Minh Te; Stephen Gray; Takahiro Fujioka; Minna Saaristo; John Leeder; Deepak Surendhra Mallya; William McCance; Michael Thomas; Mikel Duke (Desalination, 2026)

Heterogeneous iron-doped covalent triazine framework for the efficient photocatalytic upcycling of polystyrene waste to valuable aromatics under ambient conditions - Zeinab M. Saeed; Thaksen Jadhav; Renny Mathew; Xuan Li; Shamraiz H. Talib; Sasi Stephen; Andreas Kafizas; Franziska Emmerling; Dalaver H. Anjum; Ana Guilherme Buzanich; Brijith Thomas; Sharmarke Mohamed (Chemical Engineering Journal, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Preserving the gut microbiome: hydrogel-forming microneedle delivery of tetracycline reduces gut microbiome disruption compared to oral administration - Stephen A. Kelly; Li Zhao; Jonathan Nzakizwanayo; Aoife M. Rodgers; Thomas P. Thompson; Andrew J. Lee; Helen O. McCarthy; John W. McGrath; Rebecca J. Ingram; Brian V. Jones; Brendan F. Gilmore; Ryan F. Donnelly (Drug Delivery and Translational Research, 2026)
Antibiotics cause significant gut microbiome dysbiosis, particularly when administered orally. This contributes to antimicrobial resistance (AMR) and is associated with myriad health conditions. Novel drug delivery strategies that minimize gut exposure while maintaining therapeutic efficacy are urgently needed. This study aimed to evaluate whether a novel transdermal system could reduce gut microbiome disruption compared to oral delivery. Sprague-Dawley rats received a single tetracycline dose via oral gavage, IV injection, or hydrogel-forming microneedle patch. Faecal samples were collected longitudinally and analysed using 16 S rRNA gene sequencing. Oral tetracycline caused the greatest disruption to gut microbiota. Compared to the timepoint immediately prior to treatment (Day 5a), peak dysbiosis was observed at Day 7. The Firmicutes: Bacteroidetes ratio was significantly reduced following oral and IV tetracycline therapy, but not following microneedle administration. The most significant reductions in alpha and beta diversity at Day 7 were observed in the oral group. Differential abundance analysis showed oral treatment resulted in the highest number of depleted and enriched taxa. The microbiome-sparing effect of microneedle delivery was consistent across all analytical measures, offering a promising strategy to preserve host microbiome health. This minimally invasive approach represents a clinically viable alternative to oral and IV antibiotic administration.

Feasibility of home-based, remotely delivered exercise training to improve physical function in older sepsis survivors: a pilot randomized controlled trial - Yi Lin; Rola S. Zeidan; Rezvan Ghaderpanah; Margaret K. Ohama; Min-Han Jung; Naveen Baskaran; Juan Sarmiento Delgado; Stephen D. Anton; Barbara K. Smith; Christiaan Leeuwenburgh; Fang-Chi Hsu; Philip A. Efron; et al. (GeroScience, 2026)
Sepsis survivors frequently experience post-discharge physical function decline and encounter logistical barriers to participation in traditional outpatient rehabilitation. This pilot study examined the feasibility, safety, and preliminary efficacy of a remotely delivered, home-based exercise program on physical function in older sepsis survivors. In this single-blinded, randomized controlled trial (RCT), sepsis survivors aged ≥ 55 years were randomized to (a) 12 weeks of avatar-guided, progressive exercise training group (EX) or (b) a standard care control group (CO). Primary outcomes were feasibility (retention, adherence) and safety (adverse events), whereas secondary outcomes were changes in the 30-s Sit-to-Stand (30SSTS), 4-Stage Balance Test (4SBT), Timed Up-and-Go (TUG) tests, and Eastern Cooperative Oncology Group/Zubrod's (ECOG/Zubrod) performance status score. Twenty-one participants were randomized to either EX ( n = 10, mean age = 69.6 ± 8.5 years, 40% females) or CO ( n = 11, mean age = 72.3 ± 7.9 years, 45% females). Mean retention was 95% and adherence to exercise training was 76%. Thirty-four adverse events (AEs) occurred (EX = 11; CO = 16; consented but not randomized = 7 events), including four serious AEs that were unrelated to the study. The EX group showed trends toward improvements in lower-extremity strength (30SSTS: 1.14 ± 2.91 repetitions, Cohen’s d = 0.393) and balance (4SBT: 5.07 ± 4.75 s, d = 1.07), whereas the CO group showed no change in balance on the 4SBT (0.01 ± 4.38 s, d = 0.003) and trends toward decline in lower-extremity strength on the 30SSTS (− 0.88 ± 0.99 repetitions, d = − 0.883). TUG performance showed modest trends toward reductions in completion time in both groups (EX: − 1.42 ± 6.58 s, d = − 0.216; CO: − 1.27 ± 2.73 s, d = − 0.466). ECOG/Zubrod scores showed a modest trend toward improvement in the EX group subset. This pilot RCT demonstrated that a 12-week, remotely delivered exercise program was safe and feasible for older sepsis survivors and showed preliminary signals of positive change in lower-extremity strength, balance, and functional status, which warrants testing efficacy in an adequately powered Phase IIb RCT. ClinicalTrials.gov NCT05568511.

A geometrically informed permutation test for dependency in spatiotemporal patterns of protein species in microscopy images - Thomas R. Honnor; Stephen J. Royle; Adam M. Johansen; Julia A. Brettschneider (Journal of Theoretical Biology, 2026)

Geology and geochronology of the Ubendian belt in Malawi; whither the Nyika Terrane? - Robert J. Thomas; Thomas Fullgraf; Stephen D. Boger; Alexis Plunder; Benjamin le Bayon; Nicolas Charles; Dirk Frei; Yann Lahaye; Kondwani Dombola (Journal of African Earth Sciences, 2026)

Tracing paleoenvironmental change across the Permian-Triassic transition in Colorado - Mike J. Zawaski; James W. Hagadorn; Karen R. Whiteley; Mark Longman; Michael Yusas; Bonita L. Lahey; Alexandra A. Phillips; Thomas J. Algeo; Jun Shen; János Haas; Zhanhong Liu; Stephen J. Mojzsis (Gondwana Research, 2026)

FEMA GRAS assessment of natural flavor complexes: Vanilla extract, Bitter almond oil, Wintergreen oil and related flavoring ingredients - F. Peter Guengerich; Samuel M. Cohen; Gerhard Eisenbrand; Shoji Fukushima; Nigel J. Gooderham; Stephen S. Hecht; Ivonne M.C.M. Rietjens; Thomas J. Rosol; Jeanne M. Davidsen; Christie L. Harman; Sean V. Taylor (Food and Chemical Toxicology, 2026)

FEMA GRAS assessment of natural flavor complexes: Pepper, ginger, coniferous-derived and related flavoring ingredients - Stephen S. Hecht; Samuel M. Cohen; Gerhard Eisenbrand; Shoji Fukushima; Nigel J. Gooderham; F. Peter Guengerich; Ivonne M.C.M. Rietjens; Thomas J. Rosol; Jeanne M. Davidsen; Christie L. Harman; Sean V. Taylor (Food and Chemical Toxicology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Astronomically tuned chronostratigraphy of an Upper Triassic–Middle Jurassic lacustrine succession in Southwest China - Qian He; Haotian Zhang; Stephen P. Hesselbo; Sofie Lindström; Sev Kender; Christian J. Bjerrum; Mingsong Li; Jianxin Yu; Yongdong Wang; Thomas J. Algeo; Yong Lei; Jun Shen (Global and Planetary Change, 2026)

Geospatial assessment of United States tropical cyclone disaster risk - Stephen M. Strader; Sydney J. Walsh; Thomas M. Linehan; Caroline M. Carlson (Natural Hazards, 2026)
This study provides an overview of tropical cyclone (TC) hazard risk, population exposure, societal vulnerability, and community resilience for conterminous United States (CONUS) counties. TC hazard and disaster indices developed in this work combine measures of hazard risk (TC HR ), exposure (TC EXP ), vulnerability (TC VUL ), resilience (TC RES ), and disaster risk (TC DR ) to determine the counties that are most likely to experience TC hazard impacts and suffer from a disaster. Results from this research indicate that counties in Florida, Louisiana, North Carolina, and southeastern Texas are most prone to TC disasters. Harris and Cameron, TX Counties rank highest of all counties in terms of TC disaster risk. Whereas TC disaster potential is largely greater for Atlantic and Gulf Coast counties because of a combination of high TC hazard incidence and population exposure, many inland or non-coastal counties across the southeastern and northeastern CONUS are also highly disaster prone due to frequent inland flash flooding from landfalling TCs intersecting vulnerable communities. Geospatial patterns in TC hazards and fatalities in relation to the underlying population exposure, vulnerability, and resilience are critical for understanding how the next TC disaster may unfold. In all, outcomes from this research are aimed at improving local, state, and federal stakeholder (e.g., emergency managers, policymakers, land use planners) knowledge about the various threats their communities face from TCs. Our findings may assist officials with developing TC hazard-specific mitigation and resilience-building strategies with the ultimate goal of reducing casualties and losses from future TCs.

A blueprint of initial LCA in Agri-food production systems: Practical recommendations for crop and livestock production systems - Indika Thushari; Asma Jebari; Alison Carswell; Thomas C. Ponsioen; Stephen Morse; Richard Murphy; Conor Walsh (Agricultural Systems, 2026)

Chemical and isotopic analyses reconstruct multi-scalar copper circulation networks in West Africa: evidence from Akjoujt and Walaldé, 1st millenium BCE – 1st millenium CE - Jay Stephens; Antoine Courcier; Alioune Deme; Thomas Fenn; Susan Keech McIntosh; Roderick J. McIntosh; Guillaume Sarah; Virginie Renson (Archaeological and Anthropological Sciences, 2026)

Oyster Size Distributions Vary Across Time and Space in the Tampa Bay Estuary, 250–2024 ce - Jaime A. Rogers; Thomas J. Pluckhahn; Kendal Jackson; Gregory S. Herbert; Stephen P. Geiger; Victor D. Thompson (Journal of Biogeography, 2026)
Aim Restoration benchmarks often assume an undisturbed historic range of variability, if they include historic information at all. However, recent research highlights the need for a more nuanced understanding of shifting baselines and how to best incorporate past variabilities in modern management. We investigate trends in oyster size through time (ca. 250–2024 ce ) and space (ca. 1000 km 2 ) in the Tampa Bay Estuary to understand when and where ecologically significant changes to oyster populations occurred. By implementing a multiscalar approach, this study contributes historical ecological data relevant to contemporary restoration and management efforts and provides insights into understanding long‐term socioecological dynamics in Florida's largest open‐water estuary. Location Tampa Bay Estuary, Florida, USA. Time Period ca. 250–2024 ce . Taxon Mollusca; Crassostrea virginica . Methods We measured sizes of over 15,000 oyster shells from archaeological sites and contemporary reefs across four estuarine sub‐basins over approximately 2000 years to assess how mean and maximum shell sizes responded to shifts in climate and human harvesting and settlement patterns. Results We demonstrate a non‐linear decline in oyster sizes through time, including a steep decline in oyster size prior to European colonization and commercial harvest. Changes in oyster size varied across sub‐regions, and there was no consistent response to climatic variability. A moderate rebound in oyster size during the 19th century is evident and coincides with several social factors that alleviated harvest pressures for a relatively short period. However, most of the largest contemporary oysters remain significantly smaller than those in the deeper past. Main Conclusions Archaeological datasets provide relevant historical ecological information for understanding modern era declines in molluscs. Our data reveal that no single baseline exists for oyster size in Tampa Bay. Instead, oyster populations responded in complex ways to climatic variability, ecological stressors and human interactions. Oyster size is a valuable functional trait linked to reproduction and reef resilience, and management targets that reference past demographic states should be framed as dynamic ranges and evaluated at sub‐regional scales.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

In Vivo Clearance of Immune Complexes: Insights Into Human Drug/Anti-Drug Antibody Complex Clearance Dynamics - Eugenia Opolka-Hoffmann; Stephen Fowler; Thomas Bach; Gregor Jordan; Roland F. Staack (The AAPS Journal, 2026)
Immunogenicity of monoclonal antibodies (mAbs) and other biotherapeutics remains a significant clinical challenge. The resulting anti-drug antibodies (ADAs) can neutralize the drug, accelerate its clearance, diminish efficacy, and potentially trigger hypersensitivity reactions via the formation of immune complexes (ICs). Current pharmacokinetic (PK) and ADA assays typically measure the drug or ADAs but provide limited information on IC structure, concentration, and duration of exposure in humans. While rat studies suggest larger ICs are rapidly cleared, human dynamics are less understood. This study investigated IC formation and clearance in patients enrolled in a terminated Phase 1 clinical trial of TYRP1-TCB, a novel T-cell engager. Analysis of patient samples revealed that six patients, treated with 0.4 mg every three weeks, developed ADAs, resulting in IC formation. These complexes were evaluated using size exclusion chromatography (SEC) and enzyme-linked immunosorbent assay (ELISA). ICs of diverse sizes were detected, with larger ICs cleared faster than smaller ones. These findings highlighted the need for appropriate PK assays in clinical studies. Total drug PK assays alone may overestimate drug exposure during an immune response, as they do not distinguish between binding competent and ADA-bound drug. In contrast, active drug assays do not give any information on circulating drug that can no longer bind to the target. Neither approach gives information on circulating ICs, which may represent the majority of the drug administered following a strong ADA response. This study underscores the importance of understanding ADA and IC dynamics for ensuring the safe and effective use of biotherapeutics. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The composition of gases from a diffusion flame above longleaf pine needle fuel beds - David.R. Weise; Thomas H. Fletcher; Timothy J. Johnson; WeiMin Hao; Russell G. Tonkyn; Catherine A. Banach; Javier Palarea-Albaladejo; Mahsa Alizadeh; Stephen Baker (Fuel, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Comparing Influences of Natural and Artificial Woody Habitat on Benthic Macroinvertebrates in a North Temperate Lake - Matthew P. Woo; Thomas M. Detmer; Montana E. Airey; Stephen F. Jane; Dov F. Sax; Evan Dlugos; Emma G. Menard; Julián Torres-Dowdall; Peter B. McIntyre (Hydrobiologia, 2026)
Littoral habitat is an important organizing force in lacustrine food webs. Modification of littoral habitat directly impacts aquatic macroinvertebrates, which are important vectors between basal resources and higher trophic levels. Lakeshore residential development is a pervasive phenomenon often characterized by the loss of coarse woody habitat (CWH) from lakes, and the construction of artificial wooden structures (docks and ramps). To characterize the effects of artificial wooden structures on macroinvertebrate spatial distributions, we surveyed assemblages across a lightly developed lake in New York’s Adirondack Park. Using benthic sweeps and Hester-Dendy samplers, we sampled assemblages at both natural CWH and artificial wooden structures (boat ramps), and compared them to those in adjacent, non-woody areas. We found that both CWH and artificial wooden structures facilitated larger, more complex assemblages than non-woody areas. We additionally considered general shoreline characteristics, and found only compositional effects on assemblages. We suggest that impacts on aquatic macroinvertebrates arise at a fine spatial scale, and find evidence that development-associated CWH loss drives macroinvertebrate depletion. Although CWH and artificial wooden structures are unlikely to be equivalent at whole-lake scales, macroinvertebrate depletion may be functionally alleviated at fine scales by the construction of artificial wooden structures such as ramps.

Changes in Key Biodiversity Area networks following national comprehensive assessments - Andrew J. Plumptre; Zoltan Waliczky; Daniele Baisero; Olivia Crowe; Jeannot Kivono; Cecilia Tobar; Maria Gabriela Toscano; Natalia Boulad; Hugo Costa; Camila Davila; Sophie Dirou; Eleuterio Duarte; et al. (Conservation Biology, 2026)
Key Biodiversity Areas (KBAs) are sites of significance for the global persistence of biodiversity. Based on the Global Standard for the Identification of Key Biodiversity Areas (KBA Standard), published in 2016, sites are currently being assessed for KBA designation in a growing number of countries across the world. For these assessments, the KBA criteria are applied to all species and ecosystems with available data. We reviewed the first comprehensive assessments of 11 countries and compared the KBA network before and after assessments. The mean (SD) number of KBAs per country increased by 69.6% (102.1), and the mean total extent of KBAs per country increased by 164.2% (150.7). More than half of the KBAs in 2024 had >50% of their area outside the 2019 KBAs, indicating a substantial increase in KBA extent (54.0% [18.8] of KBAs). The mean proportion of each KBA covered by protected or conserved areas decreased from 56.2% (20.2) to 44.5% (15.5), owing to the incorporation of unprotected sites in the KBA network. On average, 41.1% (14.0) of sites in each country (mean 44.5 [46.4] sites per country) and 47.2% (20.5) of new KBA area after the assessment were completely unprotected, indicating that many of the new sites were not recognized in national protected area networks as significant for biodiversity before the assessment. Making a comprehensive assessment of KBAs increased the combined coverage of protected and conserved area networks from 25.4% (10.6) to 32.0% (13.1) in each country and thus contributed to reducing biodiversity loss. Therefore, comprehensive assessments of KBAs led to a substantially increased number and extent of recognized sites of importance for biodiversity published in the World Database of KBAs. Where such assessments have not been made, many important areas for biodiversity may be overlooked. We therefore encourage other nations to update their KBA networks to inform efforts to meet the goals and targets of the Kunming–Montreal Global Biodiversity Framework.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Plasma-enhanced electrostatic precipitation (PE-ESP) of restaurant smoke emissions - Boxin Zhang; Derek Schrock; Fuoad Pavin; Andrey Livchak; Mark Thomas; Sunil Murthy; Dan Singleton; Stephen B. Cronin (Environmental Science and Pollution Research, 2026)

Collaborative evaluation of in silico predictions for high throughput toxicokinetics - John F. Wambaugh; Nisha S. Sipes; Gilberto Padilla Mercado; Jon A. Arnot; Linda Bertato; Trevor N. Brown; Nicola Chirico; Christopher Cook; Daniel E. Dawson; Sarah E. Davidson-Fritz; Stephen S. Ferguson; Michael-Rock Goldsmith; et al. (Toxicology in Vitro, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Reconciling environmental sustainability in emerging economies: evidence from China on the role of water transportation, green finance, renewable energy, and economic growth - Noor Hashim Khan; Weijun He; An Min; Thomas Stephen Ramsey (Environment, Development and Sustainability, 2025)

Systematic evaluation of Tox21 compounds that target β-adrenergic receptors and their role in cardiotoxicity - Xi Luo; Li Zhang; Srilatha Sakamuru; Precious A. Adesina; Jinghua Zhao; Menghang Xia; Tuan Xu; Deborah K. Ngan; Jameson Travers; Savannah Wood; Ray Sukhawanit; Anthony Garrison; et al. (Toxicology and Applied Pharmacology, 2025)

Bridging in vitro and in vivo inhalation toxicity: Volatile organic compounds elicit similar transcriptomic points of departure in human airway cells and mouse respiratory tract - Thomas W. Jackson; Jessica R. Murray; Celia M. Schacht; Paul A. Evansky; Michael E. Monsees; Joshua A. Harrill; M. Ian Gilmour; Andrew F. Johnstone; Wanda C. Williams; Rachel D. Grindstaff; Mette C. Schladweiler; Samuel A. Vance; et al. (Environmental Pollution, 2025)

The art of bringing extinction to a freeze - History and future of species conservation - Thomas Hildebrandt; Susanne Holtze; Muhammad Agil; Pierfrancesco Biasetti; Julia Bohner; Miguel Casares; Loles Carbonell; Silvia Colleoni; Hayden Cuthill; Barbara De Mori; Sebastian Diecke; Cesare Galli; et al. (Cryobiology, 2025)

Insights into human muscle biology from human primary skeletal muscle cell culture - Thomas Francis; Casper Soendenbroe; Norman R. Lazarus; Abigail L. Mackey; Stephen D. R. Harridge (Journal of Muscle Research and Cell Motility, 2025)
This review arises from the symposium held in honour of Prof Jenny Morgan at UCL in 2024 and the authors would like to acknowledge the outstanding contribution that Prof Morgan has made to the field of translational muscle cell biology. Prof Morgan published a review article in 2010 entitled: Are human and mice satellite cells really the same? In which the authors highlighted differences between species which are still pertinent to skeletal muscle cell culture studies today. To our knowledge there are no comprehensive reviews which outline the considerable work that has been undertaken using human primary skeletal muscle origin cells as the main model system. This review highlights the multitude of muscle biology that has been investigated using human primary cells, as well as discussing the advantages and disadvantages over other cell models. We also discuss future directions for primary cell culture models utilising the latest technologies in cell type specificity and culture systems.

Robust Daytime In Situ Target Strength Estimation of Pacific Hake (Merluccius productus) over a Wide Size Range - Dezhang Chu; Stéphane Gauthier; Stephen de Blois; Julia Clemons; Rebecca Thomas (Journal of Marine Science and Engineering, 2025)
Accurate determination of the target strength (TS) of a fish species is essential for estimating the biomass of fish stocks using acoustic technology. This study estimated the daytime in situ target strength of Pacific hake (Merluccius productus) at 38 kHz using echosounder data collected during hake biomass acoustic-trawl surveys and research cruises conducted from 2009 to 2019 by U.S. and Canadian scientists. The intercept term for the 20-log TS regression over fish length at 38 kHz, b20 was found to be −67.9 dB re 1 m2 (CI: −68.09, −67.72), closely aligning with the currently used value of −68 dB in biomass assessments. Applying the revised b20 value of −67.9 dB in past stock assessments suggests that biomass estimates would be underestimated by less than 3%, which is well within the typical uncertainty range of fish stock assessments.

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

The Properties of Individual Fire Events Are Essential for Understanding Global Fire Regimes - Adam L. Mahood; Ty Tuff; Megan E. Cattau; Virginia Iglesias; Thomas E. Hanson; Jilmarie Stephens; Nayani Ilangakoon; Maxwell C. Cook; R. Chelsea Nagy; David Barnard; E. Natasha Stavros; Amy DeCastro; et al. (Global Ecology and Biogeography, 2025)
Aim As fire activity changes globally, we need to better understand the spatial and temporal characteristics of the individual events that, when aggregated, constitute fire regimes. Most global studies analyze point detections of burned area, without delineating or considering the properties of individual events. Furthermore, there is a critical need to understand fire patterns within the context of the geopolitical boundaries within which fires are managed. Location Global. Time Period 2003–2020. Major Taxa Studied Fire. Methods We divided 241 countries by Köppen‐Geiger climate classifications and quantified four event‐based fire regime metrics: size, duration, and mean and maximum growth rate; and four area‐based metrics: burned area, number of fires, season length, and season peak. We examined the correlations among fire regime components, and between each fire regime component and climate normals. We quantified temporal trends, and used mixed models to analyze how climate and landcover change were associated with event‐based components of fire regimes. Results Event‐based metrics were weakly correlated with area‐based metrics. Countries with warmer and less variable climates had high burned area, more fire events, longer season lengths and shorter event durations. Countries with high annual temperature range and low precipitation tended to have fewer events but larger fires that were faster‐spreading and occurred later in the year. The growth rate and size of individual fire events are increasing in 18% and 21% of regions we analysed, respectively. Interannual variability in size and growth rate was associated with aridity increases in boreal areas, and landcover changes in arid areas. Main Conclusions Drivers of burned area and fire seasonality are well understood but largely unrelated to the properties of individual events. A more detailed understanding of the spatial and temporal aspects of fire events at broad scales will assist fire management efforts in preparing for a warmer future.

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

Plant evolution and environmental variation create a geographic mosaic of predator-prey interactions and natural selection - David Solance Smith; Chanchanok Sudta; Anya Krause; Joseph K. Bailey; Stephen M. Shuster; Thomas G. Whitham (Evolutionary Ecology, 2025)

The Measure of Scarcity of Blue and Green Water and Its Driving Factors via the SWAT Model: An Application to the Upper Qingjiang River, China - Min An; Wei Xu; Xue Fang; Chen Cheng; Thomas Stephen Ramsey (Irrigation and Drainage, 2025)
Blue and green water is vital for the economy and life. Water scarcity occurs when the water resource supply is insufficient to support human, ecological and economic activities within a certain time and space. The water scarcity index quantifies regional blue–green water shortages providing a new perspective for evaluating water usage. Moreover, analysing the driving factors of blue–green water changes can offer a reliable reference for exploring their causes. Taking the Qingjiang River as an example, this study first used the SWAT model to simulate the upper Qingjiang River's monthly streamflow. Then, management levels were mapped to township scale via GIS to calculate blue–green water scarcities. Finally, a geo‐detector detected the impacts of natural and socio‐economic factors on blue–green water. The results show that (1) the SWAT model has good simulation results and accurately describes the water cycle process in the upper Qingjiang River. (2) From 2010 to 2022, the blue water scarcity indices were stable, whereas the green water scarcity indices first increased but then decreased. (3) The driving force of interaction is stronger than the single‐factor effect on blue–green water. This study examines water resource conditions in the basin, offering insights for township‐scale water resource management.

Can Solar‐Powered Irrigation Systems Naturally Meet Crop Water Requirements? Proof of Concept From a Case Study in Sub‐Saharan Africa - Eric Oppong Danso; Christiana Dietzen; William Akortey; Bernard Kwabena Boadi Mensah; Peter Bilson Obour; John Bright Amoah Nyasapoh; Ebenezer Agyapong; Elorm Grace Ayayi; Nana Oduro Osei Bonsu; Michael Osei Adu; Emmanuel Arthur; Jacob Ulzen; et al. (Irrigation and Drainage, 2025)
Irrigation scheduling is crucial for ensuring precise water delivery to crops. However, in many sub‐Saharan African irrigation schemes, water is applied without considering crop water needs, resulting in low crop water productivity and low yields. Solar‐powered irrigation systems can automatically meet these needs by utilizing solar radiation, which drives both evapotranspiration and solar panel power production for pumping. This study aimed to integrate irrigation scheduling into a solar‐driven irrigation system and assess the impact of meteorological variables on reference evapotranspiration (ET o ) in Ghana. A 50‐watt solar panel powered a 12‐V submersible pump, with a flow meter installed on the outlet pipe for hourly volume of water pumped (VWP) data readings. These data were used to examine correlations between solar radiation (R s ) and ET o , as well as between R s and VWP. Partial correlation analyses were used to assess the relative influences of R s , wind speed (U 2 ), relative humidity (RH) and air temperature (T air ) on ET o across 10 locations in Ghana's agroecological zones. The study revealed a strong linear correlation between the hourly R s and ET o ( R 2 > 0.9) and between the hourly R s and VWP ( R 2 = 0.8). The VWP was sufficient to meet crop‐water demand year‐round. Solar radiation was consistently the primary meteorological factor influencing ET o in Ghana.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Using sub-diurnal surface-air temperature difference anomaly derived from Himawari-8 geostationary satellite and meteorological grids for early detection of vegetation drought stress: Application to Australia's 2017–2019 Tinderbox Drought - Dejun Cai; Tim R. McVicar; Thomas G. Van Niel; Randall J. Donohue; Yuhei Yamamoto; Stephen B. Stewart; Kazuhito Ichii; Matthew P. Stenson (Remote Sensing of Environment, 2025)

Reality gaps in formalisation of wooden furniture microenterprises in Kenya - Rattiya Suddeephong Lippe; Stephen Maina Kiama; Veronica Alonso; Thomas Buchholz; Jörg Schweinle (Forest Policy and Economics, 2025)

Calibration of the FullCAM model for Australian native vegetation - David I. Forrester; Jacqueline R. England; Chiara Pasut; Keryn I. Paul; Lauren T. Bennett; Chris Eastaugh; Thomas Fairman; Melissa Fedrigo; Carl R. Gosper; Sabine Kasel; Tom Lewis; Crispen Marunda; et al. (Ecological Modelling, 2025)

Testing the robustness of the carbonate uranium isotope proxy: Evidence from a partial dissolution study - Jennifer L. Morford; Maya Elrick; Stephen Romaniello; Thomas J. Algeo; Geoffrey J. Gilleaudeau; Tyler Goepfert; Elvis Wilson; Kate Meyers; Lena Berry; Elizabeth Driscoll; Samuel Patzkowsky; Carol de Wet (Chemical Geology, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Nicotinamide riboside combined with exercise to treat hypertension in middle-aged and older adults: a pilot randomized clinical trial - Yi Lin; Rola S. Zeidan; Stephanie Lapierre-Nguyen; Hannah M. Costello; Stephen D. Anton; Thomas W. Buford; Demetra D. Christou; Michelle L. Gumz; Christiaan Leeuwenburgh; Christopher R. Martens; Mary M. McDermott; Marie E. Migaud; et al. (GeroScience, 2025)
Aerobic exercise lowers blood pressure (BP) with varying effects in hypertensive adults, potentially due to age-related nicotinamide adenine dinucleotide (NAD) metabolism dysregulation. This pilot randomized clinical trial (RCT) tested the efficacy of combining aerobic exercise with the NAD booster nicotinamide riboside (NR) to enhance BP control. In this double-blinded RCT, 54 sedentary adults (≥ 55 years) with mean daytime systolic BP (SBP) ≥ 130 mmHg were randomized to 6 weeks of 1000 mg/day of NR combined with 3 days/week of supervised 30-min walking exercise (NR + Ex), Placebo combined with the same exercise regimen (PL + Ex), or NR alone (NR). The primary outcome was daytime SBP. Other outcomes included pulse wave velocity (PWV), NAD catabolites, and nighttime BP. The primary comparison was between NR + Ex and PL + Ex. Of 54 participants (mean age 67 years, 61% female), 49 (NR + Ex: n = 15, PL + Ex: n = 16, NR: n = 18) completed all study visits (93% adherence to exercise and 90% to supplementation). NR + Ex (mean change = 5.19 ± 13.2 mmHg) did not reduce SBP more than PL + Ex (− 2.71 ± 10.5 mmHg). NR + Ex (− 0.31 ± 0.77 m/s) showed a trend toward a greater reduction in PWV. Levels of NAD catabolites were higher in NR groups. In a post hoc analysis, NR + Ex showed a trend toward greater nighttime BP reductions (systolic: − 9.6 ± 9.22; diastolic: − 4.51 ± 7.12 mmHg) in participants without antihypertensive medications. NR + Ex was not superior to PL + Ex in reducing BP in hypertensive middle-aged and older. However, trends toward greater nighttime BP reduction in NR + Ex in participants without antihypertensive medication warrant further investigation in a Phase IIb RCT. Graphical Abstract

Tectono-thermal evolution of the eastern Balkan: constraints from low-temperature thermochronometry - Lorenzo Gemignani; Silvia Cattò; Massimiliano Zattin; Xiaoqin Jiao; Stephen J. Vincent; Andrew Carter; Dian Vangelov; Thomas Gusmeo; Irene Albino; William Cavazza (International Geology Review, 2025)

A commentary on strategic community-led directions for water quality modelling in Australia and New Zealand - Danlu Guo; Anna Lintern; Alexander H. Elliott; Melanie E. Roberts; Susan M. Cuddy; Ulrike Bende-Michl; Baihua Fu; Klaus Joehnk; Robert Sargent; Danswell Starrs; Anthony J. Jakeman; Vaughn Grey; et al. (Journal of Hydrology, 2025)

High resolution variability in wet deposition in the southeastern United States - Brianna H. Matthews; Stephen Noble; Mariam Cherif; Thomas L. White; Jian-Hua Qian; Matthew R. Nelson (Atmospheric Pollution Research, 2025)

Outcomes Following Second Allogeneic Stem Cell Transplant for Graft Failure or Poor Graft Function: A Single Centre Experience - Jowon L. Kim; Moss A. Bruton Joe; Shanee Chung; Hannah Cherniawsky; Donna L. Forrest; Florian Kuchenbauer; Deepesh Lad; Stephen H. Nantel; Sujaatha Narayanan; Thomas J. Nevill; Judith Rodrigo; David Sanford; et al. (Stem Cell Reviews and Reports, 2025)

Systematic revision of the genus Orchidasma Looss, 1900 and description of Orchidasma orchilobata n. sp. from the loggerhead Caretta caretta (L.) and Kemp’s ridley Lepidochelys kempii (Garman) turtles - Thomas G. Rosser; Aiden Meaux; Ethan T. Woodyard; Justin M. Stilwell; Bradley M. Richardson; Logan R. S. Robison; Jill B. Hudnall; Kaylin McNulty; Jonah A. Nguyen; Divya Rose; Debra Moore; Beth Peterman; et al. (Systematic Parasitology, 2025)

AviList: a unified global bird checklist - Frank E. Rheindt; Paul F. Donald; David B. Donsker; Jeffrey A. Gerbracht; Marshall J. Iliff; Denis Lepage; Janette A. Norman; Pamela C. Rasmussen; Richard Schodde; Thomas S. Schulenberg; Juan I. Areta; Frederik P. Brammer; et al. (Biodiversity and Conservation, 2025)

Impacts of year-to-year weather variability and inter-panel spacing on agrivoltaic crop yields in Massachusetts - Kate Doubleday; Kristen Oleskewicz; Silvana Ovaitt; Thomas Hickey; Stephen J. Herbert; Jordan Macknick (Agroforestry Systems, 2025)
Deployment of utility-scale solar power plants could lead to agricultural land-use changes. Agrivoltaics, a dual land use combining solar and agriculture on the same land, can provide multiple environmental benefits, including improving soil quality and water use efficiency. The body of agrivoltaic field data is still growing, and crop responses to different solar configurations under different local climates are highly varied. We investigate the impact of adding spacing between adjacent solar panels in a fixed-tilt system to improve light diffusion to crops. For four crops (broccoli, peppers, kale, Swiss chard) grown across 3 years in an agrivoltaic system in Massachusetts, we found that only kale had a linearly increasing trend as the inter-panel spacing increased from 0.6 m to 1.5 m (2 ft to 5 ft). However, there were significant year-to-year differences in the yield of agrivoltaic versus control fields. Agrivoltaic and full sun fields produced equivalent yields in a hot, dry year, whereas the full-sun control beds produced more salable yield for all four crops in a warm, wet year. This demonstrates variability of agricultural outcomes and the need for more multi-year studies to ensure agrivoltaic impacts are not under- or overestimated.

Early Cretaceous vegetation in a polar ecosystem—Palynology and zircon dating of the Koonwarra Fossil Bed, Victoria, Australia - Vivi Vajda; Olena A. Shevchuk; Stephen F. Poropat; Ashley Krüger; Patricia Vickers-Rich; Thomas H. Rich (Review of Palaeobotany and Palynology, 2025)

Thermal shock resistance of lightweight cements developed for geothermal conditions - William Kibikas; Tatiana Pyatina; Thomas Dewers; Stephen Bauer; Toshifumi Sugama; Meng Meng (Geothermics, 2025)

Fluid pressure fluctuations and the seismic signature of a fault-controlled fluid migration pulse - Ashley Stanton-Yonge; Almudena Sánchez De La Muela; Rebecca K. Pearce; James O.S. Hammond; Thomas M. Mitchell; Stephen P. Hicks; W. Ashley Griffith; Max Moorkamp; Philip G. Meredith; José Cembrano (Earth and Planetary Science Letters, 2025)

Comprehensive Characterisation of the RFC1 Repeat in an Australian Cohort - Kayli C. Davies; Haloom Rafehi; Liam G. Fearnley; Penny Snell; Greta Gillies; Tess A. Field; Gábor M. Halmágyi; Kishore R. Kumar; Kate Pope; Renee Smyth; Susan E. Tomlinson; Stephen Tisch; et al. (The Cerebellum, 2025)

Nanoparticulate and colloidal uranium and plutonium in spent nuclear fuel storage pond effluents - Thomas S. Neill; Katherine Morris; Scott Harrison; Pete Apps; Nick Bryan; Stephen Parry; J. Frederick W. Mosselmans; Giannantonio Cibin; Bruce Rigby; Francis R. Livens; Samuel Shaw (Journal of Hazardous Materials, 2025)

Assessing the impact of climate change on groundwater level changes using ensemble models - Stephen Afrifa; Tao Zhang; Peter Appiahene; Xin Zhao; Vijayakumar Varadarajan; Thomas Atta-Darkwa; Yanzhang Geng; Mensah Samuel Yaw (Sustainable Water Resources Management, 2025)

A decade of German heatwave data reveals shift in local impact perception - Kerstin Katharina Zander; Duy Nguyen; Stephen Thomas Garnett (Mitigation and Adaptation Strategies for Global Change, 2025)
Heat is a global public health risk, even in temperate climates like Europe, which has experienced an increasing number of intense heatwaves over the past decade. This study uses a unique dataset of more than 57,000 X (formerly Twitter) conversations from users in Germany about heatwaves between 2013 and 2022. We showed that, as heatwaves in Germany have become more frequent and intense, social media activity on this topic has also increased. Structural topic modelling revealed nine topics, with an increase in the number and diversity of topics since 2018, a year marked by unprecedented drought and heat in Europe, including Germany. Before 2018, German heat-related tweets primarily expressed concerns about global heatwaves and their associated mortality, such as those in Australia. In 2015, there was a brief spike in tweets as users began to comment on the local impacts of heat on their daily lives, including complaints about high temperatures, air-conditioning shortages and heat-related train delays. However, it was in 2018 that conversations about local heat impacts and personal adaptation strategies proliferated. That year initiated a long-term shift in perceptions of heatwaves in people in Germany, including growing concerns about health implications, droughts and wildfires shifting from being a problem outside Europe to one affecting many European countries, including those frequently visited by Germans as tourists.

Adrenergic receptor subtypes differentially influence acrolein-induced ventilatory, vascular leakage, and inflammatory responses - Devin I. Alewel; Stephen H. Gavett; Katherine M. Rentschler; Mette C. Schladweiler; Colette N. Miller; Paul A. Evansky; Thomas W. Jackson; Wanda C. Williams; Urmila P. Kodavanti (Toxicology and Applied Pharmacology, 2025)

7 days of L-citrulline supplementation does not improve running performance in the heat whilst in a hypohydrated state - Thomas G. Cable; Mark P. Funnell; Kirsty M. Reynolds; Ella F. Hudson; Heather Z. Macrae; Drusus A. Johnson; Lee Taylor; Liam M. Heaney; Stephen A. Mears; Stephen J. Bailey; Lewis J. James (European Journal of Applied Physiology, 2025)
Purpose 7 days L-citrulline supplementation has been reported to improve blood pressure, $$\mathop {\text{V}}\limits^{.}$$ V . O 2 kinetics, gastrointestinal (GI) perfusion and endurance cycling performance through increasing arterial blood flow. In situations where blood volume is compromised (e.g., hyperthermia/hypohydration), L-citrulline may improve thermoregulation and exercise performance by redistributing blood flow to aid heat loss and/or muscle function. This study assessed 7 days L-citrulline supplementation on running performance in the heat, whilst mildly hypohydrated. Methods 13 endurance runners (2 female, 31 ± 8 y, $$\mathop {\text{V}}\limits^{.}$$ V . O 2 peak 60 ± 6 mL/kg/min) participated in a randomised crossover study with 7 days L-citrulline (CIT; 6 g/d) or placebo (maltodextrin powder; PLA) supplementation. Participants completed a 50 min running ‘preload’ at 65% $$\mathop {\text{V}}\limits^{.}$$ V . O 2 peak (32 °C, 50% relative humidity) to induce hyperthermia and hypohydration before a 3 km running time trial (TT). Body mass and blood samples were collected at baseline, pre-preload, post-preload and post-TT, whilst core and skin temperature, heart rate and perceptual responses were collected periodically throughout. Results TT performance was not different between trials (CIT 865 ± 142 s; PLA 892 ± 154 s; P = 0.437). Core and skin temperature and heart rate ( P ≥ 0.270), hydration (sweat rate, plasma volume, osmolality) indices ( P ≥ 0.216), GI damage ( P ≥ 0.260) and perceptual responses ( P ≥ 0.610) were not different between trials during the preload and TT. Conclusions 7 days of L-citrulline supplementation had no effect on 3 km running performance in the heat or any effects on thermoregulation or GI damage in trained runners in a hypohydrated state.

Overcoming ‘Diffusion Limits’ – Principles required to measure high molar mass polymers by diffusion ordered NMR - Thomas Swift; Edward Dyson; Natalia Koniuch; Richard Telford; Stephen Rimmer (Analytica Chimica Acta, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Incorporating citizen science into IUCN Red List assessments - Rachael Gallagher; Erin Roger; Jasmin Packer; Cameron Slatyer; Jodi Rowley; Will Cornwell; Emilie Ens; Sarah Legge; Colin Simpfendorfer; Ruby Stephens; Thomas Mesaglio (Conservation Biology, 2025)
Many citizen scientists are highly motivated to help address the current extinction crisis. Their work is making valuable contributions to protecting species by raising awareness, identifying species occurrences, assessing population trends, and informing direct management actions, such as captive breeding. However, clear guidance is lacking about how to use existing citizen science data sets and how to design effective citizen science programs that directly inform extinction risk assessments and resulting conservation actions based on the International Union for Conservation of Nature (IUCN) Red List criteria. This may be because of a mismatch between what citizen science can deliver to address extinction risk and the reality of what is needed to inform threatened species listing based on IUCN criteria. To overcome this problem, we examined each IUCN Red List criterion (A–E) relative to the five major types of citizen science outputs relevant to IUCN assessments (occurrence data, presence–absence observations, structured surveys, physical samples, and narratives) to recommend which outputs are most suited to use when applying the IUCN extinction risk assessment process. We explored real‐world examples of citizen science projects on amphibians and fungi that have delivered valuable data and knowledge for IUCN assessments. We found that although occurrence data are routinely used in the assessment process, simply adding more observations of occurrence from citizen science information may not be as valuable as inclusion of more nuanced data types, such as presence–absence data or information on threats from structured surveys. We then explored the characteristics of citizen science projects that have already delivered valuable data to support assessments. These projects were led by recognized experts who champion and validate citizen science data, thereby giving greater confidence in its accuracy. We urge increased recognition of the value of citizen science data within the assessment process.

Reassessing the HMS Challenger collection as a late 19th century surface ocean indicator using X-ray micro-computed tomography - Stergios D. Zarkogiannis; Thomas J. Wood; C. Giles Miller; Stephen Stukins; Brett Clark (Frontiers in Marine Science, 2025)
Plankton tow net samples collected during the HMS Challenger expedition (1872–1876) have highlighted the potential to provide an unique window into past oceanic conditions. This study aims to assess the suitability of HMS Challenger sediment samples as indicators of late 19 th century surface oceanic conditions using X-ray micro-computed tomography (μCT). We used μCT to examine all 21 available Challenger samples from the global ocean that were labelled as ‘tow-net at dredge’, ‘weights’ , or ‘trawl’ . Our analysis reveals that most samples contain benthic foraminifera shells, along with high concentrations of foraminiferal fragments and detrital quartz grains, while the remaining samples consist of sedimentary material devoid of calcareous microfossils. These findings suggest that these tow-net samples include resuspended bottom sediments rather than exclusively surface-derived material. This distinction is critical because it demonstrates that two types of Challenger tow-net samples exist: surface ocean samples and deep-water tow-net samples that incorporate seafloor material. The surface tow-net samples were recently located and are referenced in this study. These findings highlight the importance of re-evaluating historical sediment collections with modern analytical techniques to ensure accurate paleoceanographic interpretations. Furthermore, the study demonstrates the effectiveness of μCT as a non-destructive tool for sediment analysis, allowing for the detailed examination of collections without the need for washing or wet sieving.

Sensor-measured versus reported latrine use to characterize sanitation intervention uptake in a randomized controlled trial among households in rural Bangladesh - Mahfuza Islam; Jesse D. Contreras; Leanne Unicomb; Mahbubur Rahman; Benjamin F. Arnold; John M. Colford; Stephen P. Luby; Evan A. Thomas; Ayse Ercumen (International Journal of Hygiene and Environmental Health, 2025)

Predicting the impact of rare variants on RNA splicing in CAGI6 - Jenny Lord; Carolina Jaramillo Oquendo; Htoo A. Wai; Andrew G. L. Douglas; David J. Bunyan; Yaqiong Wang; Zhiqiang Hu; Zishuo Zeng; Daniel Danis; Panagiotis Katsonis; Amanda Williams; Olivier Lichtarge; et al. (Human Genetics, 2025)
Variants which disrupt splicing are a frequent cause of rare disease that have been under-ascertained clinically. Accurate and efficient methods to predict a variant’s impact on splicing are needed to interpret the growing number of variants of unknown significance (VUS) identified by exome and genome sequencing. Here, we present the results of the CAGI6 Splicing VUS challenge, which invited predictions of the splicing impact of 56 variants ascertained clinically and functionally validated to determine splicing impact. The performance of 12 prediction methods, along with SpliceAI and CADD, was compared on the 56 functionally validated variants. The maximum accuracy achieved was 82% from two different approaches, one weighting SpliceAI scores by minor allele frequency, and one applying the recently published Splicing Prediction Pipeline (SPiP). SPiP performed optimally in terms of sensitivity, while an ensemble method combining multiple prediction tools and information from databases exceeded all others for specificity. Several challenge methods equalled or exceeded the performance of SpliceAI, with ultimate choice of prediction method likely to depend on experimental or clinical aims. One quarter of the variants were incorrectly predicted by at least 50% of the methods, highlighting the need for further improvements to splicing prediction methods for successful clinical application.

Correction to: Prioritizing Opportunities to Empower Forest Carbon Decisions Through Strategic Investment in Forest Modeling Capacity - Christopher W. Woodall; Holly L. Munro; Jeff W. Atkins; Bronson P. Bullock; Thomas R. Fox; Coeli M. Hoover; Stephen M. Kinane; Lara T. Murray; Stephen P. Prisley; John D. Shaw; Erin Smith-Mateja; Aaron R. Weiskittel; et al. (Journal of Forestry, 2025)

Prioritizing Opportunities to Empower Forest Carbon Decisions Through Strategic Investment in Forest Modeling Capacity - Christopher W. Woodall; Holly L. Munro; Jeff W. Atkins; Bronson P. Bullock; Thomas R. Fox; Coeli M. Hoover; Stephen M. Kinane; Lara T. Murray; Stephen P. Prisley; John D. Shaw; Erin Smith-Mateja; Aaron R. Weiskittel; et al. (Journal of Forestry, 2025)

Effect of silvopasture, paddock trees and linear agroforestry systems on agricultural productivity: A global quantitative analysis - Thomas P. Baker; Jacqueline R. England; Shaun T. Brooks; Stephen B. Stewart; Daniel Mendham (Agricultural Systems, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Genetic Monitoring of a Lethal Control Programme for Wild Canids With Complex Mating Strategies - Thomas A. A. Prowse; Aysegul Birand; Danielle Stephens; Andrew P. Woolnough (Molecular Ecology, 2025)
Although mammalian carnivores are ecologically important, they also drive human–wildlife conflicts. Managing carnivores using lethal control is controversial, in part because the impact of control effort is often uncertain due to limited abundance monitoring. We used an Australian metapopulation of wild dogs as a model system to investigate the feasibility of monitoring effective population size () to detect reductions in census population size () following control. Based on microsatellite data collected over an 11‐year period, we parameterised an individual‐based spatial population model for wild dogs that integrated demography, genetics, random or hierarchical mating, dispersal between subpopulations and compensatory immigration. and trajectories were simulated under different proportional culling rates and genetic sampling regimes. We also used simulations without culling as null models to define 95% critical values for assessing the significance of empirical changes in over time. We concluded there were significant reductions (39%–62%) in in each subpopulation of the wild dog metapopulation, mostly likely due to control. In simulations assuming a hierarchical rather than random mating system, the impact of control on was weakened because reproduction by subordinate individuals increased as dominant individuals were removed, yet reduced following culling. Sensitivity analyses demonstrated that becomes an unreliable proxy of when compensatory immigration is strong and compensatory reproduction is weak, in which case can increase following culling due to the immigration of new genotypes. Nonetheless, our results suggest can provide information about wild dog over sufficiently short timescales to inform management.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Site‐Specific Nutrient Data Reveal the Importance of Soils in Driving the Mycorrhizal Make‐Up of Woody Vegetation Worldwide - Xiaobin Hua; Christopher H. Lusk; Ian A. Dickie; Stephen Adu‐Bredu; Kathryn J. Allen; Viviana Araus; Laurent Augusto; Pavel Barsukov; David Bauman; Félix Brédoire; David F. R. P. Burslem; James W. Dalling; et al. (Global Ecology and Biogeography, 2025)
Aim Arbuscular mycorrhizas (AM) and ectomycorrhizas (ECM) have different impacts on nutrient cycling, carbon storage, community dynamics and enhancement of photosynthesis by rising CO 2 . Recent global analyses have concluded that patterns of AM/ECM dominance in forests worldwide are shaped by climate, with soil nutrients contributing negligible additional explanatory power. However, their reliance on nutrient data from GIS surfaces masks important local influences of parent material, topography and soil age on soil nutrient status. We asked if use of site‐specific nutrient data reveals a more important role for nutrients. Time Period Present day. Location Global dataset comprising 703 sites, encompassing forests, savanna/woodlands, shrublands and deserts on all continents except Antarctica. Taxa Studied Arborescent plants, including angiosperms, gymnosperms and tree ferns. Methods Generalised Additive Models for Location, Scale and Shape (GAMLSS) to determine the effects of climate variables, soil nitrogen and soil phosphorus on the proportional representation of ECM and of non‐mycorrhizal species (NM) in woody vegetation. Results GAMLSS showed a strong negative relationship of ECM representation with mean annual temperature (MAT), and a strong negative relationship with soil total nitrogen. NM representation was highest on dry sites and phosphorus‐poor sites. Reanalysis showed that GIS‐derived soil nutrient data had less explanatory power than site‐specific nutrient data, and resulted in poorer model fits. Conclusions Our results support the long‐held belief that soil nutrients as well as climate influence the relative fitness of different mycorrhizal syndromes worldwide, and demonstrate the value of using site‐specific nutrient data. Soil nutrients should be considered when predicting the impact of climate change on the mycorrhizal composition of vegetation and resulting shifts in ecosystem processes.

Atmospheric Pressure Rivalry Between the Arctic and Northern Pacific: Implications for Alaskan Climate Variability - Igor V. Polyakov; Thomas J. Ballinger; James E. Overland; Stephen J. Vavrus; Seth L. Danielson; Rick Lader; Uma S. Bhatt; Amy S. Hendricks; Franz J. Mueter (International Journal of Climatology, 2024)
Located at the confluence of the Arctic and North Pacific and with Alaska at its heart, the Pacific Arctic Region (PAR) is a unique and interconnected regional climate system. Significant climatic changes in the PAR are described by a novel, mobile monthly Alaska Arctic Front (AAF) index, which is defined by sea level pressure differences between the migratory cores of the Beaufort High and Aleutian Low. Regional climate variability associated with the AAF shows prominent decadal signatures that are driven by the opposing effects of the North Pacific and the Arctic atmospheric pressure fields. Low AAF (negative phase) is dominated by North Pacific forcing, whereas high AAF (positive phase) is dominated by Arctic atmospheric processes. The recent (2011–2021) negative AAF phase, which is associated with the westward displacement of Aleutian Low explaining stronger northward winds and enhanced water transport northward through Bering Strait, is conducive to increased oceanic heat and freshwater content, reduced regional sea ice cover in the PAR, and to the expansion of Pacific species into the Arctic. These factors are all indicators of the Pacification of the Arctic Ocean, a key feature of climate change related to progression of anomalous Pacific water masses and biota into the polar basins. It is not yet clear if or when the recent phase of decadal variability will change and alter the rate of Pacification of the Arctic climate system.

Circulating small extracellular vesicles as blood-based biomarkers of muscle health in aging nonhuman primates - Shalini Mishra; Ashish Kumar; Yangen He; Yixin Su; Sangeeta Singh; Mark F. Santos; Rakesh Singh; Jingyun Lee; Cristina M. Furdui; Carol A. Shively; Stephen B. Kritchevsky; Thomas C. Register; et al. (GeroScience, 2024)
Age-associated loss of muscle mass and function and subsequent mobility decline define poor health outcomes, reduced quality of life, and mortality risk. The rate and extent of aging-related muscle loss varies across older adults. It is challenging to understand the molecular pathogenesis of mobility decline, as anthropometric and imaging techniques, primarily used in muscle function assessment, do not offer much molecular information. Small extracellular vesicles (sEV) are lipid membrane-bound, nano-sized (≤ 200 nm) vesicles which carry a wide array of biomolecules as their cargo. sEV contain cell/tissue-specific signatures on their surface and can be isolated from biofluids. These properties pose sEV as a minimally invasive means to monitor the functional and biological health of difficult-to-access tissues, establishing them as a promising liquid biopsy tool. Here, we first isolated skeletal muscle-derived sEV (sEV SKM ) from the serum of vervet monkeys (16 to < 25 years old) using alpha sarcoglycan (SGCA) as a muscle-specific sEV surface marker. sEV SKM were extensively characterized for size, concentration, purity, and specificity. Further, sEV SKM isolated from young (11–15 years) and old (25–29 years) monkeys’ serum were characterized for oxidized proteins by mass spectrometry and miRNAs by small-RNAseq. Notably, the analysis of oxidized proteins indicated perturbation of metabolic pathways, actin cytoskeleton, muscle cytoskeleton regulation, and HIF-1 signaling in older monkeys. Furthermore, small-RNAseq analysis identified differential expression of several miRNAs regulating metabolic pathways, inflammation, and stress signaling. Altogether, these results suggest that it is feasible to isolate sEV SKM and use them to identify molecular biomarkers that reflect the physiological state of muscle tissue.

The effect of repeated hot water immersion on vascular function, blood pressure and central haemodynamics in individuals with type 2 diabetes mellitus - Thomas J. James; Jo Corbett; Michael Cummings; Sharon Allard; Stephen J. Bailey; Clare Eglin; Harvey Belcher; Daniel D. Piccolo; Michael Tipton; Maria Perissiou; Zoe L. Saynor; Anthony I. Shepherd (Journal of Thermal Biology, 2024)

Turning the tide: Rhythmic aggregation behaviour in Anurida maritima (Collembola) is entrained by inundation - Martijn J.T.N. Timmermans; Madeleine King; Diane Purchase; Benjamin J.A. Dickins; Thomas E. Dickins; Stephen Kett (Journal of Experimental Marine Biology and Ecology, 2024)

Improved mechanical, thermal, and barrier properties of halloysite nanotubes and nanocellulose incorporated PVA-PEO films: For food packaging applications - Jija Thomas; P. Selvin Thomas; Ranimol Stephen (Food Packaging and Shelf Life, 2024)

Fuel fumes and foliage: The fate of speciated gasoline VOCs during phytoremediation and their impact on the bacterial phenotype - Stephen Matheson; Robert Fleck; Thomas Lockwood; Raissa L. Gill; Luowen Lyu; Peter J. Irga; Fraser R. Torpy (Environmental Pollution, 2024)

Lithological and compositional diversity of diamond substrates beneath the Koidu kimberlite reveals addition of subducted sediments - Mei Yan Lai; Thomas Stachel; Matthew F. Hardman; D. Graham Pearson; Jeff W. Harris; Richard A. Stern; Stephen E. Haggerty (Contributions to Mineralogy and Petrology, 2024)

First report of iris yellow spot virus infecting shallot (Allium cepa var. aggregatum) in Australia - Sari Nurulita; Andrew D. W. Geering; Kathleen S. Crew; Stephen Harper; John E. Thomas (Australasian Plant Pathology, 2024)
In 2019, symptoms typical of infection by iris yellow spot virus (IYSV; family Tospoviridae , genus Orthotospovirus ) were observed on shallot ( A. cepa var. aggregatum ) grown at the Gatton Research Facility, Department of Agriculture and Fisheries, Queensland. Initial testing by DAS-ELISA was positive for IYSV, and subsequent specific RT-PCR amplifying part of the RdRp (L-segment) and sequencing of amplicons confirmed the IYSV infection. This is the first record of IYSV infection of shallot in Australia.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Long-term patterns and trends in water column biogeochemistry in a changing environment - Paul Julian; James W. Fourqurean; Stephen E. Davis; Donatto Surratt; Evelyn E. Gaiser; John S. Kominoski; Tiffany G. Troxler; Joseph N. Boyer; Serge Thomas; Henry O. Briceño; Christopher J. Madden; Enrique Montes; et al. (Estuarine, Coastal and Shelf Science, 2024)

Harnessing the power of tidal flat diatoms to combat climate change - Jihae Park; Hojun Lee; Jana Asselman; Colin Janssen; Stephen Depuydt; Jonas De Saeger; Thomas Friedl; Koen Sabbe; Wim Vyverman; Catharina J. M. Philippart; Jaime Pitarch; Philippe M. Heynderickx; et al. (Critical Reviews in Environmental Science and Technology, 2024)

Correction: Continental scale spatial temporal interpolation of near-surface air temperature: do 1 km hourly grids for Australia outperform regional and global reanalysis outputs? - Stephen B. Stewart; Tim R. McVicar; Thomas G. Van Niel; Dejun Cai (Climate Dynamics, 2024)

Continental scale spatial temporal interpolation of near-surface air temperature: do 1 km hourly grids for Australia outperform regional and global reanalysis outputs? - Stephen B. Stewart; Tim R. McVicar; Thomas G. Van Niel; Dejun Cai (Climate Dynamics, 2024)
Near-surface air temperature is an essential climate variable for the study of many biophysical phenomena, yet is often only available as a daily mean or extrema (minimum, maximum). While many applications require sub-diurnal dynamics, temporal interpolation methods have substantial limitations and atmospheric reanalyses are complex models that typically have coarse spatial resolution and may only be periodically updated. To overcome these issues, we developed an hourly air temperature product for Australia with spatial interpolation of hourly observations from 621 stations between 1990 and 2019. The model was validated with hourly observations from 28 independent stations, compared against empirical temporal interpolation methods, and both regional (BARRA-R) and global (ERA5-Land) reanalysis outputs. We developed a time-varying (i.e., time-of-day and day-of-year) coastal distance index that corresponds to the known dynamics of sea breeze systems, improving interpolation performance by up to 22.4% during spring and summer in the afternoon and evening hours. Cross-validation and independent validation ( n = 24/4 OzFlux/CosmOz field stations) statistics of our hourly output showed performance that was comparable with contemporary Australian interpolations of daily air temperature extrema (climatology/hourly/validation: R 2 = 0.99/0.96/0.92, RMSE = 0.75/1.56/1.78 °C, Bias = -0.00/0.00/-0.03 °C). Our analyses demonstrate the limitations of temporal interpolation of daily air temperature extrema, which can be biased due to the inability to represent frontal systems and assumptions regarding rates of temperature change and the timing of minimum and maximum air temperature. Spatially interpolated hourly air temperature compared well against both BARRA-R and ERA5-Land, and performed better than both reanalyses when evaluated against the 28 independent validation stations. Our research demonstrates that spatial interpolation of sub-diurnal meteorological fields, such as air temperature, can mitigate the limitations of alternative data sources for studies of near-surface phenomena and plays an important ongoing role in supporting numerous scientific applications.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Probabilistic hazard analyses for a small island: methods for quantifying tephra fall hazard and appraising possible impacts on Ascension Island - Sara Osman; Julia Crummy; Mark Thomas; Stephen Carver (Bulletin of Volcanology, 2024)
Proximal to the source, tephra fall can cause severe disruption, and populations of small volcanically active islands can be particularly susceptible. Volcanic hazard assessments draw on data from past events generated from historical observations and the geological record. However, on small volcanic islands, many eruptive deposits are under-represented or missing due to the bulk of tephra being deposited offshore and high erosion rates from weather and landslides. Ascension Island is such an island located in the South Atlantic, with geological evidence of mafic and felsic explosive volcanism. Limited tephra preservation makes it difficult to correlate explosive eruption deposits and constrains the frequency or magnitude of past eruptions. We therefore combined knowledge from the geological record together with eruptions from the analogous São Miguel island, Azores, to probabilistically model a range of possible future explosive eruption scenarios. We simulated felsic events from a single vent in the east of the island, and, as mafic volcanism has largely occurred from monogenetic vents, we accounted for uncertainty in future vent location by using a grid of equally probable source locations within the areas of most recent eruptive activity. We investigated the hazards and some potential impacts of short-lived explosive events where tephra fall deposits could cause significant damage and our results provide probabilities of tephra fall loads from modelled events exceeding threshold values for potential damage. For basaltic events with 6–10 km plume heights, we found a 50% probability that tephra fallout across the west side of the island would impact roads and the airport during a single explosive event, and if roofs cannot be cleared, three modelled explosive phases produced tephra loads that may be sufficient to cause roof collapse (≥ 100 kg m −2 ). For trachytic events, our results show a 50% probability of loads of 2–12 kg m −2 for a plume height of 6 km increasing to 898–3167 kg m −2 for a plume height of 19 km. Our results can assist in raising awareness of the potential impacts of tephra fall from short-lived explosive events on small islands.

Integrated modeling of nature’s role in human well-being: A research agenda - Rebecca Chaplin-Kramer; Stephen Polasky; Rob Alkemade; Neil D. Burgess; William W.L. Cheung; Ingo Fetzer; Mike Harfoot; Thomas W. Hertel; Samantha L.L. Hill; Justin Andrew Johnson; Jan H. Janse; Patrick José v. Jeetze; et al. (Global Environmental Change, 2024)

Dynamic collapse and regrowth of the Antarctic Ice Sheet in the Weddell Sea sector during the middle Miocene: A novel multi-proxy sedimentary provenance approach using in-situ 87Rb/87Sr dating of detrital K-feldspar - Roland Neofitu; Chris Mark; Suzanne O'Connell; Thomas Zack; Delia Rösel; Darren Mark; Dan Barfod; Michael J. Flowerdew; Samuel Kelley; J. Stephen Daly (Earth and Planetary Science Letters, 2024)

Japanese Yew (Taxus) poisoning of wild ungulates in Utah during the winter of 2022–2023 - Stephen T. Lee; Jane Kelly; Virginia Stout; Sydney Lamb; Thomas J. Baldwin; Daniel Cook (Toxicon, 2024)

More than a canopy cover metric: Influence of canopy quality, water-use strategies and site climate on urban forest cooling potential - Mohammad A. Rahman; Stefan Arndt; Felipe Bravo; Pui K. Cheung; Natalie van Doorn; Eleonora Franceschi; Miren del Río; Stephen J. Livesley; Astrid Moser-Reischl; Nayanesh Pattnaik; Thomas Rötzer; Heiko Paeth; et al. (Landscape and Urban Planning, 2024)

Turkey tail mushroom (Trametes versicolor): an edible macrofungi with immense medicinal properties - Olaide Olawunmi Ajibola; Cirilo Nolasco-Hipolito; Octavio Carvajal-Zarrabal; Shanti F Salleh; Gbadebo C Adeyinka; Stephen A Adefegha; Mirja K Ahmmed; Kazi Sumaiya; Raymond Thomas (Current Opinion in Food Science, 2024)

Deep learning structural insights into heterotrimeric alternatively spliced P2X7 receptors - Sophie K. F. De Salis; Jake Zheng Chen; Kristen K. Skarratt; Stephen J. Fuller; Thomas Balle (Purinergic Signalling, 2024)
P2X7 receptors (P2X7Rs) are membrane-bound ATP-gated ion channels that are composed of three subunits. Different subunit structures may be expressed due to alternative splicing of the P2RX7 gene, altering the receptor’s function when combined with the wild-type P2X7A subunits. In this study, the application of the deep-learning method, AlphaFold2-Multimer (AF2M), for the generation of trimeric P2X7Rs was validated by comparing an AF2M-generated rat wild-type P2X7A receptor with a structure determined by cryogenic electron microscopy (cryo-EM) (Protein Data Bank Identification: 6U9V). The results suggested AF2M could firstly, accurately predict the structures of P2X7Rs and secondly, accurately identify the highest quality model through the ranking system. Subsequently, AF2M was used to generate models of heterotrimeric alternatively spliced P2X7Rs consisting of one or two wild-type P2X7A subunits in combination with one or two P2X7B, P2X7E, P2X7J, and P2X7L splice variant subunits. The top-ranking models were deemed valid based on AF2M’s confidence measures, stability in molecular dynamics simulations, and consistent flexibility of the conserved regions between the models. The structure of the heterotrimeric receptors, which were missing key residues in the ATP binding sites and carboxyl terminal domains (CTDs) compared to the wild-type receptor, help to explain their observed functions. Overall, the models produced in this study (available as supplementary material) unlock the possibility of structure-based studies into the heterotrimeric P2X7Rs.

An obituary: Dr. Helmut Cölfen 1965–2023 - Borries Demeler; Denis Gebauer; Emre Brookes; Jeffrey Fagan; Johannes Walter; José García de la Torre; Juan Manuel García-Ruiz; Kristian Schilling; Mengdi Chen; Lukas Dobler; Olwyn Byron; Stephen E. Harding; et al. (European Biophysics Journal, 2024)

Is EGD Needed in all Patients after Suicidal or Exploratory Caustic Ingestions? - Michael Levine; Yaron Finkelstein; William J. Trautman; Dazhe Cao; Evan Schwarz; Ari Filip; Leanne Cook; Sameer Arbussattar Pathan; Cherie Obilom; Jim Liu; Joseph Yanta; Neta Cohen; et al. (Journal of Medical Toxicology, 2024)

Soil properties of thickets and adjacent land use types in coastal savanna landscape of Ghana - Emmanuel Baidoo; Vincent Logah; Thomas Adjei-Gyapong; Caleb M. Ocansey; George K.D. Ametsitsi; Stephen Narh; Elmar M. Veenendaal (Geoderma Regional, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Rates of tree cover loss in key biodiversity areas on Indigenous Peoples’ lands - Ashley Thomas Simkins; Paul F. Donald; Alison E. Beresford; Stuart H. M. Butchart; Julia E. Fa; Alvaro Onrubia Fernández‐Llamazares; Stephen T. Garnett; Graeme M. Buchanan (Conservation Biology, 2024)
Indigenous Peoples’ lands (IPL) cover at least 38 million km 2 (28.1%) of Earth's terrestrial surface. These lands can be important for biodiversity conservation. Around 20.7% of IPL intersect areas protected by government (PAs). Many sites of importance for biodiversity within IPL could make a substantial but hitherto unquantified contribution to global site‐based conservation targets. Key Biodiversity Areas (KBAs) represent the largest global network of systematically identified sites of high importance for biodiversity. We assessed the effectiveness of IPL in slowing biodiversity loss inside and outside PAs by quantifying tree cover loss from 2000 to 2019 in KBAs at international and national levels and comparing it with losses at equivalent sites outside mapped IPL. Based on a matched sample of 1‐km 2 cells in KBAs inside and outside mapped IPL, tree cover loss in KBAs outside PAs was lower inside IPL than outside IPL. By contrast, tree cover loss in KBAs inside PAs was lower outside IPL than inside IPL (although the difference was far smaller). National rates of tree cover loss in KBAs varied greatly in relation to their IPL and PA status. In one half of the 44 countries we examined individually, there was no significant difference in the rate of tree cover loss in KBAs inside and outside mapped IPL. The reasons for this intercountry variation could illuminate the importance of IPL in meeting the Convention on Biological Diversity's ambition of conserving 30% of land by 2030. Critical to this will be coordinated action by governments to strengthen and enforce Indigenous Peoples’ rights, secure their collective systems of tenure and governance, and recognize their aspirations for their lands and futures.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Hypohydration induced by prolonged cycling in the heat increases biomarkers of renal injury in males - Loris A. Juett; Jack E. Drury; Thomas B. Greensmith; Alfie P. Thompson; Mark P. Funnell; Lewis J. James; Stephen A. Mears (European Journal of Applied Physiology, 2024)
Purpose Recent studies have shown that hypohydration can increase renal injury. However, the contribution of hypohydration to the extent of renal injury is often confounded by exercise induced muscle damage. Therefore, the aim of the present study was to investigate the effect of manipulating hydration status during moderate-intensity cycling in the heat on biomarkers of renal injury. Methods Following familiarisation, fourteen active males (age: 21 [20–22] y; BMI: 22.1 ± 1.9 kg/m 2 ; $$ \dot{V} $$ V ˙ O 2peak : 55 ± 9 mL/kg/min) completed two experimental trials, in a randomised cross-over design. Experimental trials consisted of up to 120 min of intermittent cycling (~ 50% W peak ) in the heat (~ 35 °C, ~ 50% relative humidity). During exercise, subjects consumed either a water volume equal to 100% body mass losses (EU) or minimal water (HYP; 75–100 mL) to induce ~ 3% body mass loss. Blood and urine samples were collected at baseline, 30 min post-exercise and 24 h post-baseline, with an additional urine sample collected immediately post-exercise. Results Thirty minutes post-exercise, body mass and plasma volume were lower in HYP than EU ( P < 0.001), whereas serum and urine osmolality ( P < 0.001), osmolality-corrected urinary kidney injury molecule-1 concentrations (HYP: 2.74 [1.87–5.44] ng/mOsm, EU: 1.15 [0.84–2.37] ng/mOsm; P = 0.024), and percentage change in osmolality-corrected urinary neutrophil gelatinase-associated lipocalin concentrations (HYP: 61 [17–141] %, EU: 7.1 [– 4 to 24] %; P = 0.033) were greater in HYP than EU. Conclusion Hypohydration produced by cycling in the heat increased renal tubular injury, compared to maintaining euhydration with water ingestion.

Natural capital accounting of land resources based on ecological footprint and ecosystem services value - Bei Wang; Weijun He; Min An; Xue Fang; Thomas Stephen Ramsey (Science of The Total Environment, 2024)

The economics of nature's healing touch: A systematic review and conceptual framework of green space, pharmaceutical prescriptions, and healthcare expenditure associations - Muhammad Mainuddin Patwary; Mondira Bardhan; Matthew H.E.M. Browning; Thomas Astell-Burt; Matilda van den Bosch; Jiaying Dong; Angel M. Dzhambov; Payam Dadvand; Tracy Fasolino; Iana Markevych; Olivia McAnirlin; Mark J. Nieuwenhuijsen; et al. (Science of The Total Environment, 2024)

Towards richer knowledge partnerships between ecology and ethnoecology - Zsolt Molnár; Yildiz Aumeeruddy-Thomas; Dániel Babai; Sandra Díaz; Stephen T. Garnett; Rosemary Hill; Peter Bates; Eduardo S. Brondízio; Joji Cariño; László Demeter; Álvaro Fernández-Llamazares; Maximilien Guèze; et al. (Trends in Ecology & Evolution, 2024)

Developing expert scientific consensus on the environmental and societal effects of marine artificial structures prior to decommissioning - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Todd Bond; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Jennifer Dannheim; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

The ethical assessment of Assisted Reproductive Technologies (ART) in wildlife conservation - Barbara de Mori; Elena Mercugliano; Pierfrancesco Biasetti; Ilaria Pollastri; Maria Michela Spiriti; Daniela Florio; Francesco Andreucci; Frank Göritz; Susanne Holtze; Cesare Galli; Jan Stejskal; Silvia Colleoni; et al. (Biological Conservation, 2024)

Time to Treat the Climate and Nature Crisis as One Indivisible Global Health Emergency - Kamran Abbasi; Parveen Ali; Virginia Barbour; Thomas Benfield; Kirsten Bibbins-Domingo; Stephen Hancocks; Richard Horton; Laurie Laybourn-Langton; Robert Mash; Peush Sahni; Wadeia Mohammad Sharief; Paul Yonga; et al. (Current Environmental Health Reports, 2024)

Time to Treat the Climate and Nature Crisis as One Indivisible Global Health Emergency - Kamran Abbasi; Parveen Ali; Virginia Barbour; Thomas Benfield; Kirsten Bibbins-Domingo; Stephen Hancocks; Richard Horton; Laurie Laybourn-Langton; Robert Mash; Peush Sahni; Wadeia Mohammad Sharief; Paul Yonga; et al. (Current Climate Change Reports, 2024)

A differential game of water pollution management in the trans-jurisdictional river basin - Liang Yuan; Yuzhi Qi; Weijun He; Xia Wu; Yang Kong; Thomas Stephen Ramsey; Dagmawi Mulugeta Degefu (Journal of Cleaner Production, 2024)

Simulation study on the effect of differentiated carbon tax adjustment on CO2 emissions reduction in China from the perspective of carbon footprint - Xue Fang; Weijun He; FaGuang Wen; Min An; Mengfei Song; Bei Wang; Thomas Stephen Ramsey (Journal of Cleaner Production, 2024)

To what extent can decommissioning options for marine artificial structures move us toward environmental targets? - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Nicola Beaumont; Silvana Birchenough; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

The development of a novel decision support system for regional land use planning for brownfield land - Ellis B. Hammond; Frederic Coulon; Stephen H. Hallett; Russell Thomas; Alistair Dick; Drew Hardy; Mark Dickens; Emma Washbourn; Darren J. Beriro (Journal of Environmental Management, 2024)

Participatory study of policy process for wildlife conservation and ecotourism in Eswatini: A multiple streams analysis - Thomas Gregory Moorman; Stephen S. Ditchkoff; Kelly Dunning; Phumla Mnguni; Daniel Morris; Caroline Ward (Environmental Science & Policy, 2024)

A Set Pair Analysis Method for Assessing and Forecasting Water Conflict Risk in Transboundary River Basins - Liang Yuan; Chenyuan Liu; Xia Wu; Weijun He; Yang Kong; Dagmawi Mulugeta Degefu; Thomas Stephen Ramsey (Water Resources Management, 2024)

Combined effects of green tea supplementation and eccentric exercise on nuclear factor erythroid 2-related factor 2 activity - Josh Thorley; Craig Thomas; Nicolas Thon; Hannah Nuttall; Neil R. W. Martin; Nicolette Bishop; Stephen J. Bailey; Tom Clifford (European Journal of Applied Physiology, 2024)
Purpose This study investigated whether combining eccentric exercise and green tea supplementation synergistically increased nuclear factor erythroid 2-related factor 2 (NRF2) activity, a transcription factor responsible for coordinating endogenous antioxidant expression. Methods In a double-blinded, randomized, between-subjects design, 24 males (mean [SD]; 23 [3] years, 179.6 [6.1] cm, 78.8 [10.6] kg) performed 100 drop jumps following a 6 days supplementation period with either green tea (poly)phenols ( n = 12; 500 mg·d −1 ) or a placebo ( n = 12; inulin). NRF2/antioxidant response element (ARE) binding in peripheral blood mononuclear cells (PBMCs), catalase (CAT) and glutathione reductase (GR) activity, 8-hydroxy-2′-deoxyguanosine (8-OHdG) excretion, and differential leukocyte counts were measured pre-, post-, 1 h and 24 h post-exercise. Results Exercise did not increase NRF2/ARE binding ( p = 0.12) (fold change vs rest: green tea = [post] 0.78 ± 0.45, [1 h] 1.17 ± 0.54, [24 h] 1.06 ± 0.56; placebo = [post] 1.40 ± 1.50, [1 h] 2.98 ± 3.70, [24 h] 1.04 ± 0.45). Furthermore, CAT activity ( p = 0.12) and 8-OHdG excretion ( p = 0.42) were unchanged in response to exercise and were not augmented by green tea supplementation ( p > 0.05 for all). Exercise increased GR activity by 30% ( p = 0.01), however no differences were found between supplement groups ( p = 0.51). Leukocyte and neutrophil concentrations were only elevated post-exercise ( p < 0.001 for all). Conclusion Eccentric exercise, either performed alone or in conjunction with green tea supplementation, did not significantly increase NRF2 activity in PBMCs. Trial registration number osf.io/kz37g (registered: 15/09/21). Graphical abstract

How an illuminated headline affects catches and species separation in a Celtic Sea mixed demersal trawl fishery - Samantha F. Birch; Stephen D. Gregory; David L. Maxwell; Marieke Desender; Thomas L. Catchpole (Fisheries Research, 2023)

Southern limit of the Patagonian Ice Sheet - Dominic A. Hodgson; Stephen J. Roberts; Eñaut Izagirre; Bianca B. Perren; François De Vleeschouwer; Sarah J. Davies; Thomas Bishop; Robert D. McCulloch; Juan-Carlos Aravena (Quaternary Science Reviews, 2023)

Phylogeography, hybrid zones and contemporary species boundaries in the south-eastern Australian smooth frogs (Anura: Myobatrachidae: Geocrinia) - Thomas Parkin; Stephen C. Donnellan; Benjamin Parkin; Glenn M. Shea; Jodi J.L. Rowley (Molecular Phylogenetics and Evolution, 2023)

From data to decisions: Empowering brownfield redevelopment with a novel decision support system - Ellis B. Hammond; Frederic Coulon; Stephen H. Hallett; Russell Thomas; Alistair Dick; Drew Hardy; Mark Dickens; Emma Washbourn; Darren J. Beriro (Journal of Environmental Management, 2023)

Timing is everything; operational changes at a pumping station with a gravity sluice to provide safe downstream passage for silver European eels and deliver considerable financial savings - Liam J. Carter; Rosalind M. Wright; Robert E. Thomas; Jake Reeds; Leona A. Murphy; Stephen J. Collier; Oliver Evans; Henrik Baktoft; Jonathan D. Bolland (Journal of Environmental Management, 2023)

In response to the Letter to the Editor from Xiao regarding our article, “FEMA GRAS assessment of natural flavor complexes: Asafetida oil, garlic oil and onion oil” - Jeanne M. Davidsen; Samuel M. Cohen; Gerhard Eisenbrand; Shoji Fukushima; Nigel J. Gooderham; F. Peter Guengerich; Stephen S. Hecht; Ivonne M.C.M. Rietjens; Thomas J. Rosol; Christie L. Harman; Danarubini Ramanan; Sean V. Taylor (Food and Chemical Toxicology, 2023)

Dormancy and Physiological Age of Seed Tubers from a Diverse Set of Potato Cultivars Grown at Different Altitudes and in Different Seasons in Kenya - Thomas K. Kwambai; Denis Griffin; Moses Nyongesa; Stephen Byrne; Monica Gorman; Paul C. Struik (Potato Research, 2023)
The study was conducted to determine the dormancy and physiological age characteristics of diverse potato genotypes as influenced by growing altitudes and seasons for future breeding strategies and optimal patterns of use. Dormancy and sprouting characteristics have an impact on tuber production, storability and seed quality for planting and ware for consumption and the market. This study presents the results of dormancy and physiological age measurements conducted on 47 potato genotypes grown at three altitudes with three replications at each location and in two contrasting growing seasons. The seed tubers were evaluated at low altitude under darkness on moist sand storage conditions to assess their dormancy release, number of sprouts, sprout weight, sprout length and percentage tuber weight loss. Results showed significant ( p < 0.001) differences among genotypes, locations and seasons, and significant interactions between these factors for days to dormancy release, number of sprouts per tuber at dormancy release and at 45 days after dormancy release, length of longest sprout, weight loss percentage of unsprouted and sprouted tubers at dormancy release and at 45 days after dormancy release, respectively. There was a wide variation in time to dormancy release (54 to 136 days); most genotypes showed medium to long dormancy. Seed tubers grown at low altitude showed longer dormancy than those grown at higher altitudes, while genotypic differences in dormancy were very consistent across environments. Genotypes strongly differed in sprouting characteristics and weight loss. There were highly significant interactions between altitude and season for all variables assessed, except for the number of sprouts 45 days after dormancy release and the weight loss after sprouting. Generally, the genotypic effects were larger than those of altitude, season and the interaction effects for all variables evaluated. This paper will allow variety selection to optimize seed quality at planting and minimize storage losses while providing new targets for breeders.

Changing nutritional seascapes of kelp forests - Tanika C. Shalders; Curtis Champion; Kirsten Benkendorff; Tom Davis; Thomas Wernberg; Stephen Morris; Melinda A. Coleman (Frontiers in Marine Science, 2023)
Ocean warming and short-term extreme events (e.g. marine heatwaves) are becoming more intense and frequent and have had major impacts on ecosystems. Seaweeds are foundational components of temperate reefs, providing nutrition for a diversity of species and underpinning temperate food webs. While the impacts of climate-driven environmental change on seaweed distribution, abundance and interactions are well studied, potential impacts on the provision of nutrients from seaweeds and their availability to consumers remain poorly understood. Here, we use metabolomic and lipidomic approaches to understand how the provision of nutrients from key seaweeds may be altered under climate change. We optimize a small-scale microextraction technique to test the effects of warming and marine heatwaves on the nutritional quality of two Australian habitat-forming seaweeds; Ecklonia and Sargassum . We then model changes in lipid availability in response to climate-driven ocean warming throughout Ecklonia ’s eastern Australian distribution. Contrary to expectations, ocean warming and marine heatwaves had limited effects on seaweed nutritional quality, indicating resilience in the nutritional value of these species to climate-driven warming. However, nutritional quality varied significantly between species, which presents new implications for predicted species redistributions from the base of the food chain. Modelling revealed a projected net loss of 3.5% of lipids across the east coast of Australia by 2100 under RCP 8.5 in response to shifts in the redistribution of Ecklonia biomass. The climate-driven redistribution of seaweeds is likely to alter the availability of seaweed-derived nutrients to consumers, which may have broad implications for the transfer of energy within temperate marine food webs.

Fuelling phytoremediation: gasoline degradation by green wall systems—a case study - Stephen Matheson; Robert Fleck; Thomas Lockwood; Raissa L Gill; Peter J Irga; Fraser R Torpy (Environmental Science and Pollution Research, 2023)
The capacity for indoor plants including green wall systems to remove specific volatile organic compounds (VOCs) is well documented in the literature; however under realistic settings, indoor occupants are exposed to a complex mixture of harmful compounds sourced from various emission sources. Gasoline vapour is one of the key sources of these emissions, with several studies demonstrating that indoor occupants in areas surrounding gasoline stations or with residentially attached garages are exposed to far higher concentrations of harmful VOCs. Here we assess the potential of a commercial small passive green wall system, commercially named the ‘LivePicture Go’ from Ambius P/L, Australia, to drawdown VOCs that comprise gasoline vapour, including total VOC (TVOC) removal and specific removal of individual speciated VOCs over time. An 8-h TVOC removal efficiency of 42.45% was achieved, along with the complete removal of eicosane, 1,2,3-trimethyl-benzene, and hexadecane. Further, the green wall also effectively reduced concentrations of a range of harmful benzene derivatives and other VOCs. These results demonstrate the potential of botanical systems to simultaneously remove a wide variety of VOCs, although future research is needed to improve upon and ensure efficiency of these systems over time and within practical applications.

Land degradation neutrality: Testing the indicator in a temperate agricultural landscape - Amy Thomas; Laura Bentley; Chris Feeney; Stephen Lofts; Ciaran Robb; Ed C Rowe; Amanda Thomson; Eleanor Warren-Thomas; Bridget Emmett (Journal of Environmental Management, 2023)

Using the fuzzy evidential reasoning approach to assess and forecast the water conflict risk in transboundary Rivers: A case study of the Mekong river basin - Liang Yuan; Xia Wu; Weijun He; Yang Kong; Dagmawi Mulugeta Degefu; Thomas Stephen Ramsey (Journal of Hydrology, 2023)

Spatial-Temporal evolvement and the contributing factors for the economic potential of ecosystem services in counties situated along a river - Min An; Yiwen Wu; Yanheng Ouyang; Mengfei Song; Jin Huang; Xiaohua Dong; Ramsey Thomas Stephen (Journal for Nature Conservation, 2023)

Examining the Potential Formation of Ternary DNA Complexes with Chromium‑Cysteine, Chromium-Ascorbate, and Chromium-Glutathione and Implications for Their Carcinogenicity - Sydney Marchi; Emma Lankford; Bradley Dorin; Eilidh Drummond; Sumner C. Thomas; Stephen A. Woski; John B. Vincent (Biological Trace Element Research, 2023)

FEMA GRAS assessment of natural flavor complexes: Sage oil, Orris Root Extract and Tagetes Oil and related flavoring ingredients - Nigel J. Gooderham; Samuel M. Cohen; Gerhard Eisenbrand; Shoji Fukushima; F. Peter Guengerich; Stephen S. Hecht; Ivonne M.C.M. Rietjens; Thomas J. Rosol; Jeanne M. Davidsen; Christie L. Harman; Shannen E. Kelly; Sean V. Taylor (Food and Chemical Toxicology, 2023)

Utilizing the strategic concession behavior in a bargaining game for optimal allocation of water in a transboundary river basin during water bankruptcy - Liang Yuan; Xia Wu; Weijun He; Dagmawi Mulugeta Degefu; Yang Kong; Yang Yang; Shasha Xu; Thomas Stephen Ramsey (Environmental Impact Assessment Review, 2023)

Diaporthe gulyae colonizes seeds of sunflower (Helianthus annuus) systematically through leaf, petiole and stem infection - Susan M. Thompson; Stephen M. Neate; Thomas J. Gulya; Elizabeth A. B. Aitken (European Journal of Plant Pathology, 2023)

Parasite manipulation of host phenotypes inferred from transcriptional analyses in a trematode‐amphipod system - David M. Rand; Joaquin C. B. Nunez; Shawn Williams; Stephen Rong; John T. Burley; Kimberly B. Neil; Adam N. Spierer; Wilson McKerrow; David S. Johnson; Yevgeniy Raynes; Thomas J. Fayton; Nicholas Skvir; et al. (Molecular Ecology, 2023)
Manipulation of host phenotypes by parasites is hypothesized to be an adaptive strategy enhancing parasite transmission across hosts and generations. Characterizing the molecular mechanisms of manipulation is important to advance our understanding of host–parasite coevolution. The trematode ( Levinseniella byrdi ) is known to alter the colour and behaviour of its amphipod host ( Orchestia grillus ) presumably increasing predation of amphipods which enhances trematode transmission through its life cycle. We sampled 24 infected and 24 uninfected amphipods from a salt marsh in Massachusetts to perform differential gene expression analysis. In addition, we constructed novel genomic tools for O. grillus including a de novo genome and transcriptome. We discovered that trematode infection results in upregulation of amphipod transcripts associated with pigmentation and detection of external stimuli, and downregulation of multiple amphipod transcripts implicated in invertebrate immune responses, such as vacuolar ATPase genes. We hypothesize that suppression of immune genes and the altered expression of genes associated with coloration and behaviour may allow the trematode to persist in the amphipod and engage in further biochemical manipulation that promotes transmission. The genomic tools and transcriptomic analyses reported provide new opportunities to discover how parasites alter diverse pathways underlying host phenotypic changes in natural populations.

Occurrences of tropical, subtropical and rare marine fishes in Aotearoa New Zealand indicate biodiversity change - Irene Middleton; Malcolm Francis; J. David Aguirre; Carl Struthers; Thomas Trnski; Clinton Duffy; John Anderson; Mary Carney; Nathan Cox; Stephen Hemstalk; Blair Herbert; Craig Johnston; et al. (Journal of Biogeography, 2023)
Aim Climate change is driving biogeographic change globally, including poleward range shifts of species and the increasing abundance of rare species. We examine spatiotemporal patterns in the occurrences of tropical, subtropical and rare marine fishes in Aotearoa New Zealand to determine whether biodiversity change is occurring in this temperate region and to set a baseline for future monitoring of climate change impacts. Location Aotearoa New Zealand (NZ). Taxon Marine fishes. Methods We consolidated 100 years of unpublished records and citizen science sightings of tropical, subtropical and rare fishes to develop a focal species database for NZ. Using hotspot analysis, we identified geographic locations where the occurrence and diversity of focal species is greater than expected. We examine the spatiotemporal variation in hotspots by focal species lifestage, habitat and taxonomic family. Results Focal species occurrences and diversity in NZ have increased. We present 17 new‐to‐NZ marine fish species, and a new‐to‐NZ family. Focal species now account for 6.5% of pelagic fishes and 17.3% of benthic fishes in NZ. The northeast of the North Island (Te Ika‐a‐Māui) was a consistent hotspot of focal species occurrences and diversity. Hotspots of mature and pelagic fish occurrences appeared further south than juvenile and benthic species occurrences. Families with tropical affinities (Labridae and Pomacentridae) were restricted to northeastern NZ whereas hotspots of families with temperate affinities (i.e. Cheilodactylidae) extended into the South Island (Te Waipounamu). Main Conclusions Tropical, subtropical and rare fishes are a major component of the fish biodiversity in temperate NZ, and their occurrences and diversity has increased over the past half‐century. Northeastern NZ consistently has the highest occurrence rate and diversity of warmer‐water fishes. Our study demonstrates the value in consolidating citizen scientist observations to detect biodiversity change, and to inform current baselines and future monitoring of climate‐related biodiversity change.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Will green technological progress help industrial collaborative agglomeration increase regional carbon productivity: evidence from Yangtze River Delta urban agglomerations - Weijun He; Yizhan Li; Xu Meng; Mengfei Song; Thomas Stephen Ramsey; Min An (Environment, Development and Sustainability, 2023)

Warming waters of the Gulf of Maine: The role of Shelf, Slope and Gulf Stream Water masses - David W. Townsend; Neal R. Pettigrew; Maura A. Thomas; Stephen Moore (Progress in Oceanography, 2023)

The influence of passive wedge-wire screen aperture and flow velocity on juvenile European eel exclusion, impingement and passage - Liam J. Carter; Stephen J. Collier; Robert E. Thomas; Josh Norman; Rosalind M. Wright; Jonathan D. Bolland (Ecological Engineering, 2023)

Adaptability analysis of water pollution and advanced industrial structure in Jiangsu Province, China - Yang Kong; Weijun He; Juqin Shen; Liang Yuan; Xin Gao; Thomas Stephen Ramsey; Qingling Peng; Dagmawi Mulugeta Degefu; Fuhua Sun (Ecological Modelling, 2023)

Global reanalysis products cannot reproduce seasonal and diurnal cycles of tropospheric ozone in the Congo Basin - Inês Vieira; Hans Verbeeck; Félicien Meunier; Marc Peaucelle; Thomas Sibret; Lodewijk Lefevre; Alexander W. Cheesman; Flossie Brown; Stephen Sitch; José Mbifo; Pascal Boeckx; Marijn Bauters (Atmospheric Environment, 2023)

Correction to: Maximum heat ratio: bi-directional method for fast and slow sap flow measurements - Jose Gutierrez Lopez; Thomas Pypker; Julian Licata; Stephen S. O. Burgess; Heidi Asbjornsen (Plant and Soil, 2023)

Comparative sedimentation equilibrium analysis of two IgG1 glycoforms: IgGCri and IgGWid - Khalil Abu Hammad; Vlad Dinu; Thomas E. MacCalman; Jacob Pattem; Margaret Goodall; Richard B. Gillis; Roy Jefferis; Stephen E. Harding (European Biophysics Journal, 2023)
The solution properties of two different glycoforms of IgG1 (IgG1Cri and IgG1Wid) are compared using primarily sedimentation equilibrium analysis with two complementary analysis routines: SEDFIT-MSTAR and MULTISIG. IgGCri bears diantennary complex-type glycans on its Fc domain that are fully core fucosylated and partially sialylated, whilst on IgGWid, they are non-fucosylated, partially galactosylated and non-sialylated. IgGWid is also Fab glycosylated. Despite these differences, SEDFIT-MSTAR analysis shows similar weight average molar masses M w of ~ (150 ± 5) kDa for IgGCri and ~ (154 ± 5) kDa for IgGWid and both glycoforms show evidence of the presence of a small fraction of dimer confirmed by MULTISIG analysis and also by sedimentation coefficient distributions from supportive sedimentation velocity measurements. The closeness of the sedimentation equilibrium behaviour and sedimentation coefficient distributions with a main peak sedimentation coefficient of ~ 6.4S for both glycoforms at different concentrations suggest that the different glycosylation profiles do not significantly impact on molar mass (molecular weight) nor conformation in solution.

Development of a field-deployable qPCR assay for real-time pest monitoring in algal cultivation systems - Monica R. Sanchez; Ellen Denning; Thomas C. Biondi; Blake Hovde; Stephen Eacker; Stephanie Getto; Harmanpreet Kaur; Ahlem Jebali; Isidora Echenique-Subiabre; Matt Green; Julia Gerber; Ben Auch; et al. (Algal Research, 2023)

Sex-specific respiratory and systemic endocrine effects of acute acrolein and trichloroethylene inhalation - Devin I. Alewel; Thomas W. Jackson; Samuel A. Vance; Mette C. Schladweiler; Paul A. Evansky; Andres R. Henriquez; Rachel Grindstaff; Stephen H. Gavett; Urmila P. Kodavanti (Toxicology Letters, 2023)

Effects of projected end-of-century temperature on the muscle development of neonate epaulette sharks, Hemiscyllium ocellatum - Peyton A. Thomas; Emily E. Peele; Carolyn R. Wheeler; Kara Yopak; Jodie L. Rummer; John W. Mandelman; Stephen T. Kinsey (Marine Biology, 2023)

Elevated Galectin-9 across the human brain correlates with HIV neuropathology and detrimental cognitive states - Thomas A. Premeaux; Stephen T. Yeung; Satish K. Pillai; Lishomwa C. Ndhlovu (Journal of NeuroVirology, 2023)

The NASA space weather science and observation gap analysis - Angelos Vourlidas; Drew Turner; Doug Biesecker; Anthea Coster; Alec Engell; George Ho; Thomas Immel; Catherine Keys; Louis Lanzerotti; Gang Lu; Noé Lugaz; Janet Luhmann; et al. (Advances in Space Research, 2023)

Social feasibility assessments in conservation translocations - Thomas R. Dando; Sarah L. Crowley; Richard P. Young; Stephen P. Carter; Robbie A. McDonald (Trends in Ecology & Evolution, 2023)

There's something in the air: A review of sources, prevalence and behaviour of microplastics in the atmosphere - Stacey O'Brien; Cassandra Rauert; Francisca Ribeiro; Elvis D. Okoffo; Stephen D. Burrows; Jake W. O'Brien; Xianyu Wang; Stephanie L. Wright; Kevin V. Thomas (Science of The Total Environment, 2023)

A mercury and trace element geochemical record across Oceanic Anoxic Event 1b in Arctic Canada - Jennifer M. Galloway; Stephen E. Grasby; Feiyue Wang; Thomas Hadlari; Keith Dewing; Stéphane Bodin; Hamed Sanei (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Lack of correlation between growth rate and sequence type among Cronobacter sakazakii - Emily E. Jackson; Nathalie Gnanou Besse; Rabeb Bennour Hennekinne; Timothy Ells; Michel Laurentie; Thomas Meheut; Stephen J. Forsythe (Food Microbiology, 2023)

FEMA GRAS assessment of natural flavor complexes: Lemongrass oil, chamomile oils, citronella oil and related flavoring ingredients - Thomas J. Rosol; Samuel M. Cohen; Gerhard Eisenbrand; Shoji Fukushima; Nigel J. Gooderham; F. Peter Guengerich; Stephen S. Hecht; Ivonne M.C.M. Rietjens; Jeanne M. Davidsen; Christie L. Harman; Shannen Kelly; Danarubini Ramanan; et al. (Food and Chemical Toxicology, 2023)

FEMA GRAS assessment of derivatives of basil, nutmeg, parsley, tarragon and related allylalkoxybenzene-containing natural flavor complexes - Jeanne M. Davidsen; Samuel M. Cohen; Gerhard Eisenbrand; Shoji Fukushima; Nigel J. Gooderham; F. Peter Guengerich; Stephen S. Hecht; Ivonne M.C.M. Rietjens; Thomas J. Rosol; Christie L. Harman; Sean V. Taylor (Food and Chemical Toxicology, 2023)

Global oceanic anoxia linked with the Capitanian (Middle Permian) marine mass extinction - Huyue Song; Thomas J. Algeo; Haijun Song; Jinnan Tong; Paul B. Wignall; David P.G. Bond; Wang Zheng; Xinming Chen; Stephen J. Romaniello; Hengye Wei; Ariel D. Anbar (Earth and Planetary Science Letters, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Chromosome-length genome assemblies and cytogenomic analyses of pangolins reveal remarkable chromosome counts and plasticity - Marlys L. Houck; Klaus-Peter Koepfli; Taylor Hains; Ruqayya Khan; Suellen J. Charter; Julie A. Fronczek; Ann C. Misuraca; Sergei Kliver; Polina L. Perelman; Violetta Beklemisheva; Alexander Graphodatsky; Shu-Jin Luo; et al. (Chromosome Research, 2023)

Molecular targets of insecticides and herbicides – Are there useful overlaps? - Stephen O. Duke; Zhiqiang Pan; Amar G. Chittiboyina; Daniel R. Swale; Thomas C. Sparks (Pesticide Biochemistry and Physiology, 2023)

FEMA GRAS assessment of natural flavor complexes: Allspice, anise, fennel-derived and related flavoring ingredients - Ivonne M.C.M. Rietjens; Samuel M. Cohen; Gerhard Eisenbrand; Shoji Fukushima; Nigel J. Gooderham; F. Peter Guengerich; Stephen S. Hecht; Thomas J. Rosol; Jeanne M. Davidsen; Christie L. Harman; Sean V. Taylor (Food and Chemical Toxicology, 2023)

Great expectations: patients’ preferences for clinically significant results from genomic sequencing - Salma Shickh; Agnes Sebastian; Marc Clausen; Chloe Mighton; Christine Elser; Andrea Eisen; Larissa Waldman; Seema Panchal; Thomas Ward; June C. Carroll; Emily Glogowski; Kasmintan A. Schrader; et al. (Human Genetics, 2023)

Application of decision tools to ethical analysis in biodiversity conservation - Pierfrancesco Biasetti; Thomas B. Hildebrandt; Frank Göritz; Robert Hermes; Susanne Holtze; Jan Stejskal; Cesare Galli; Ilaria Pollastri; Alessia Muzzo; Isaac Lekolool; David Ndereeh; Patrick Omondi; et al. (Conservation Biology, 2023)
Achieving ethically responsible decisions is crucial for the success of biodiversity conservation projects. We adapted the ethical matrix, decision tree, and Bateson's cube to assist in the ethical analysis of complex conservation scenarios by structuring these tools so that they can implement the different value dimensions (environmental, social, and animal welfare) involved in conservation ethics. We then applied them to a case study relative to the decision‐making process regarding whether or not to continue collecting biomaterial on the oldest of the two remaining northern white rhinoceroses ( Ceratotherium simum cottoni ), a functionally extinct subspecies of the white rhinoceros. We used the ethical matrix to gather ethical pros and cons and as a starting point for a participatory approach to ethical decision‐making. We used decision trees to compare the different options at stake on the basis of a set of ethical desiderata. We used Bateson's cube to establish a threshold of ethical acceptability and model the results of a simple survey. The application of these tools proved to be pivotal in structuring the decision‐making process and in helping reach a shared, reasoned, and transparent decision on the best option from an ethical point of view among those available.

Wastewater surveillance of SARS-CoV-2 and influenza in preK-12 schools shows school, community, and citywide infections - Madeline Wolken; Thomas Sun; Camille McCall; Rebecca Schneider; Kelsey Caton; Courtney Hundley; Loren Hopkins; Katherine Ensor; Kaavya Domakonda; Prashant Kalvapalle; David Persse; Stephen Williams; et al. (Water Research, 2023)

FEMA GRAS assessment of natural flavor complexes: Asafetida oil, garlic oil and onion oil - Jeanne M. Davidsen; Samuel M. Cohen; Gerhard Eisenbrand; Shoji Fukushima; Nigel J. Gooderham; F. Peter Guengerich; Stephen S. Hecht; Ivonne M.C.M. Rietjens; Thomas J. Rosol; Christie L. Harman; Danarubini Ramanan; Sean V. Taylor (Food and Chemical Toxicology, 2023)

Making the invisible visible: Using a qualitative system dynamics model to map disparities in cumulative environmental stressors and children's neurodevelopment - Devon C. Payne-Sturges; Ellis Ballard; Deborah A. Cory-Slechta; Stephen B. Thomas; Peter Hovmand (Environmental Research, 2023)

Context and mitigation of lost circulation during geothermal drilling in diverse geologic settings - Carmen Winn; Patrick Dobson; Craig Ulrich; Timothy Kneafsey; Thomas S. Lowry; John Akerley; Ben Delwiche; Abraham Samuel; Stephen Bauer (Geothermics, 2023)

Advancing the potential impact of future scenarios by integrating psychological principles - Isabell Richter; Elizabeth Gabe-Thomas; Ana M. Queirós; Stephen R.J. Sheppard; Sabine Pahl (Environmental Science & Policy, 2023)

Is an MRI-derived anatomical measure of dementia risk also a measure of brain aging? - Ramon Casanova; Andrea M. Anderson; Ryan T. Barnard; Jamie N. Justice; Anna Kucharska-Newton; Beverly Gwen Windham; Priya Palta; Rebecca F. Gottesman; Thomas H. Mosley; Timothy M. Hughes; Lynne E. Wagenknecht; Stephen B. Kritchevsky (GeroScience, 2023)

Mitigation of emissions and energy consumption due to light-duty vehicle size increases - David Gohlke; Jarod Kelly; Thomas Stephens; Xinyi Wu; Yan Zhou (Transportation Research Part D: Transport and Environment, 2023)

Development of multidimensional water poverty in the Yangtze River Economic Belt, China - Liang Yuan; Dongquan Yang; Xia Wu; Weijun He; Yang Kong; Thomas Stephen Ramsey; Dagmawi Mulugeta Degefu (Journal of Environmental Management, 2023)

Digital tools for brownfield redevelopment: Stakeholder perspectives and opportunities - Ellis B. Hammond; Frederic Coulon; Stephen H. Hallett; Russell Thomas; Drew Hardy; Darren J. Beriro (Journal of Environmental Management, 2023)

Isolating the mechanisms for asteroid surface refreshing - Francesca E. DeMeo; Michaël Marsset; David Polishook; Brian J. Burt; Richard P. Binzel; Sunao Hasegawa; Mikael Granvik; Nicholas A. Moskovitz; Alissa Earle; Schelte J. Bus; Cristina A. Thomas; Andrew S. Rivkin; et al. (Icarus, 2023)

Recovery from persistent nutrient-N limitation following the Permian–Triassic mass extinction - Yong Du; Huyue Song; Stephen E. Grasby; Teng Xing; Haijun Song; Li Tian; Daoliang Chu; Yuyang Wu; Jacopo Dal Corso; Thomas J. Algeo; Jinnan Tong (Earth and Planetary Science Letters, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Effects of grid spacing on high-frequency precipitation variance in coupled high-resolution global ocean–atmosphere models - Charles X. Light; Brian K. Arbic; Paige E. Martin; Laurent Brodeau; J. Thomas Farrar; Stephen M. Griffies; Ben P. Kirtman; Lucas C. Laurindo; Dimitris Menemenlis; Andrea Molod; Arin D. Nelson; Ebenezer Nyadjro; et al. (Climate Dynamics, 2022)
High-frequency precipitation variance is calculated in 12 different free-running (non-data-assimilative) coupled high resolution atmosphere–ocean model simulations, an assimilative coupled atmosphere–ocean weather forecast model, and an assimilative reanalysis. The results are compared with results from satellite estimates of precipitation and rain gauge observations. An analysis of irregular sub-daily fluctuations, which was applied by Covey et al. (Geophys Res Lett 45:12514–12522, 2018. https://doi.org/10.1029/2018GL078926 ) to satellite products and low-resolution climate models, is applied here to rain gauges and higher-resolution models. In contrast to lower-resolution climate simulations, which Covey et al. (2018) found to be lacking with respect to variance in irregular sub-daily fluctuations, the highest-resolution simulations examined here display an irregular sub-daily fluctuation variance that lies closer to that found in satellite products. Most of the simulations used here cannot be analyzed via the Covey et al. (2018) technique, because they do not output precipitation at sub-daily intervals. Thus the remainder of the paper focuses on frequency power spectral density of precipitation and on cumulative distribution functions over time scales (2–100 days) that are still relatively “high-frequency” in the context of climate modeling. Refined atmospheric or oceanic model grid spacing is generally found to increase high-frequency precipitation variance in simulations, approaching the values derived from observations. Mesoscale-eddy-rich ocean simulations significantly increase precipitation variance only when the atmosphere grid spacing is sufficiently fine (< 0.5°). Despite the improvements noted above, all of the simulations examined here suffer from the “drizzle effect”, in which precipitation is not temporally intermittent to the extent found in observations.

Particle Property Characterization and Data Curation for Effective Powder Property Modeling in the Pharmaceutical Industry - Robert C. Wadams; Ilgaz Akseli; Jacob Albrecht; Ana P. Ferreira; John F. Gamble; Michael Leane; Stephen Thomas; Yue Schuman; Lauren Taylor; Mike Tobyn (AAPS PharmSciTech, 2022)

Developing a Dedicated Leadership Curriculum for Radiation Oncology Residents - Ethan Y. Song; Jessica Chuang; Jessica M. Frakes; Thomas Dilling; Joann F. Quinn; Stephen Rosenberg; Peter Johnstone; Louis Harrison; Sarah E. Hoffe (Journal of Cancer Education, 2022)

The influence of carbon emission disclosure on enterprise value under ownership heterogeneity: evidence from the heavily polluting corporations - Liang Yuan; Yuying Chen; Weijun He; Yang Kong; Xia Wu; Dagmawi Mulugeta Degefu; Thomas Stephen Ramsey (Environmental Science and Pollution Research, 2022)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Insufficient Evidence for Multiple Species of Tyrannosaurus in the Latest Cretaceous of North America: A Comment on “The Tyrant Lizard King, Queen and Emperor: Multiple Lines of Morphological and Stratigraphic Evidence Support Subtle Evolution and Probable Speciation Within the North American Genus Tyrannosaurus” - Thomas D. Carr; James G. Napoli; Stephen L. Brusatte; Thomas R. Holtz; David W. E. Hone; Thomas E. Williamson; Lindsay E. Zanno (Evolutionary Biology, 2022)
The Late Cretaceous dinosaur Tyrannosaurus rex was recently split into three species based on the premise that variation in the T. rex hypodigm is exceptional, indicating cryptic species and “robust” and “gracile” morphs. The morphs are based on proportional ratios throughout the skeleton. The species are claimed to be stratigraphically separate, with an early robust species followed by robust and gracile descendants. There are problems with the hypothesis: the taxon diagnoses are based on two features that overlap between the species; several skulls cannot be identified based on the diagnoses; proportional comparisons between Tyrannosaurus and other theropods are based on incomparable samples; the tooth data are problematic; the stratigraphic framework divides the Hell Creek Formation into thirds, without the stratigraphic position of each specimen, or independent age control showing the subdivisions are coeval over the entire geographic area; previous work found variation in T. rex , but it cannot be parsed into discrete categories. We tested for “gracile” and “robust” morphs by analyzing the femoral and tooth ratios that were published in the multiple species study using agglomerative hierarchical clustering. The results found that each set of ratios are explained by one cluster, showing that dimorphism is not supported. We tested for exceptional variation of the femoral ratio of Tyrannosaurus ; we calculated the mean intraspecific robusticity for 112 species of living birds and 4 nonavian theropods. The results showed that the absolute variation in Tyrannosaurus is unexceptional and it does not indicate cryptic diversity. We conclude that “ T. regina ” and “ T. imperator ” are subjective junior synonyms of T. rex .

Uncertainty of Gridded Precipitation at Local and Continent Scales: A Direct Comparison of Rainfall from SILO and AWAP in Australia - Guobin Fu; Olga Barron; Stephen P. Charles; Michael J. Donn; Thomas G. Van Niel; Geoff Hodgson (Asia-Pacific Journal of Atmospheric Sciences, 2022)

Daily synoptic conditions associated with occurrences of compound events in estuaries along North Atlantic coastlines - Paula Camus; Ivan D. Haigh; Thomas Wahl; Ahmed A. Nasr; Fernando J. Méndez; Stephen E. Darby; Robert J. Nicholls (International Journal of Climatology, 2022)
Coastal compound flooding events occur when extreme events of rainfall, river discharge and sea level coincide and collectively increase water surface elevation, exacerbating flooding. The meteorological conditions that generate these events are usually low‐pressure systems that generate high winds and intense rainfall. In this study, we identify the types of synoptic atmospheric conditions that are typically associated with coastal compound events using a weather‐type approach, for the North Atlantic coastlines (encompassing northwest Europe and the east coast of the United States). Compound events are identified along the estuaries of the study region from 1980 to 2014 based on an impact function defined by water surface elevation that resulted from the combination of river discharge and sea level. We find that compound events are more frequent along European as opposed to U.S. coastlines. In both cases, they are associated with a few dominant weather patterns. European hotspots of compound events are concentrated in the west coast of United Kingdom, the northwest coast of the Iberian Peninsula and around the Strait of Gibraltar. These areas share the same weather patterns which represent the main pathways of storms that cross the North Atlantic Ocean. In the case of U.S. locations, the areas with highest number of compound events are located mainly in the Gulf of Mexico and along Mexico and along the mid‐eastern U.S. coastlines. In these areas, compound events are produced by transitional weather patterns, which describe storms that travel northward parallel to the coastline. Splitting the occurrence of compound events in the corresponding weather types discriminates the interannual variability based on the relationship with dominant climate indices in the North Atlantic Ocean.

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Groundwater resource management during construction dewatering - James Watson; Stephen Thomas; Thomas Goodfellow (Sustainable Water Resources Management, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Rapid assessments of Pacific Ocean net coral reef carbonate budgets and net calcification following the 2014–2017 global coral bleaching event - Travis A. Courtney; Hannah C. Barkley; Stephen Chan; Courtney S. Couch; Tye L. Kindinger; Thomas A. Oliver; David J. Kriegman; Andreas J. Andersson (Limnology and Oceanography, 2022)
The 2014–2017 global coral bleaching event caused widespread coral mortality; however, its impact on the capacity for coral reefs to maintain calcium carbonate structures has not been determined. Here, we quantified remotely sensed maximum heat stress during the 2014–2017 bleaching event, census‐based net carbonate budgets from benthic imagery and fish survey data, and net reef calcification from salinity normalized seawater total alkalinity anomalies collected from 2017–2019 for 56 Pacific coral reef sites (Mariana Islands, Northwestern Hawaiian Islands, Pacific Remote Island Areas, and American Samoa). We incorporated the census‐based and chemistry‐based metrics to determine a calcification vulnerability index for each site to maintain calcium carbonate balance to provide accessible information to managers and policy makers. Most coral reef sites likely experienced ecologically severe (79%, n = 44) or significant (9%, n = 7) heat stress during the 2014–2017 coral bleaching event. Census‐based net carbonate budgets (mean ± 95% = 2.1 ± 0.6 kg CaCO 3 m −2 yr −1 ) were positive for 77% of sites ( n = 43), neutral for 16% of sites ( n = 9), and negative for 7% of sites ( n = 4). Chemistry‐based relative net reef calcification (mean ± 95% = 22 ± 10 μ mol kg −1 ) was positive for 84% of sites ( n = 47), neutral for 11% of sites ( n = 6), and negative for 5% of sites ( n = 3). The calcification vulnerability index suggested the Pacific Ocean reef sites surveyed were of minimal (68%, n = 38) to moderate (32%, n = 18) concern for maintaining calcium carbonate balance following the bleaching event. This suggests that many reefs maintained positive calcium carbonate balance, but that a large number of reefs may be approaching a potential threshold for maintaining their calcium carbonate balance under the climate crisis.

Winter ecology of specialist and generalist morphs of European whitefish, Coregonus lavaretus , in subarctic northern Europe - Brian Hayden; Chris Harrod; Stephen Thomas; Kimmo K. Kahilainen (Journal of Fish Biology, 2022)
European whitefish is a model species for adaptive radiation of fishes in temperate and subarctic lakes. In northern Europe the most commonly observed morphotypes are a generalist (LSR) morph and a pelagic specialist (DR) morph. The evolution of a pelagic specialist morph is something of an enigma, however, as this region is characterized by long, dark winters with pelagic primary production limited to a brief window in late summer. We conducted the first winter‐based study of polymorphic whitefish populations to determine the winter ecology of both morphs, and we combined seasonal diet and stable isotope analysis with several proxies of condition in three polymorphic whitefish populations. The generalist LSR morph fed on benthic and pelagic prey in summer but was solely reliant on benthic prey in winter. This was associated with a noticeable but moderate reduction in condition, lipid content and stomach fullness in winter relative to summer. In contrast, the DR whitefish occupied a strict pelagic niche in both seasons. A significant reduction in pelagic prey during winter resulted in severe decrease in condition, lipid content and stomach fullness in DR whitefish in winter relative to summer, with the pelagic morph apparently approaching starvation in winter. We suggest that this divergent approach to seasonal foraging is associated with the divergent life‐history traits of both morphs.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

A multi-weight fuzzy Methodological Framework for Allocating Coalition Payoffs of Joint Water Environment Governance in Transboundary River Basins - Liang Yuan; Xia Wu; Weijun He; Yang Kong; Thomas Stephen Ramsey; Dagmawi Mulugeta Degefu (Water Resources Management, 2022)

Detection of two poleroviruses infecting garlic (Allium sativum) in Australia - Sari Nurulita; Andrew D. W. Geering; Kathleen S. Crew; Stephen M. Harper; John E. Thomas (Australasian Plant Pathology, 2022)
Two near complete polerovirus genomes were assembled using high throughput sequencing (HTS) data from two separate samples of garlic cultivar ‘Glenlarge’ grown in Gatton, Queensland, Australia. Whole genome sequence comparisons showed that one contig shared 96.7% nucleotide identity with phasey bean mild yellows virus (MT966032.1) and the other, 99.8% nucleotide identity with turnip yellows virus (MT586581.1). Phylogenetic analyses further revealed that the isolates fell within the PBMYV group 2 and TuYV group 2 clades, respectively. This is the first report of these poleroviruses infecting garlic.

Identification of environmental chemicals that activate p53 signaling after in vitro metabolic activation - Masato Ooka; Jinghua Zhao; Pranav Shah; Jameson Travers; Carleen Klumpp-Thomas; Xin Xu; Ruili Huang; Stephen Ferguson; Kristine L. Witt; Stephanie L. Smith-Roe; Anton Simeonov; Menghang Xia (Archives of Toxicology, 2022)
Currently, approximately 80,000 chemicals are used in commerce. Most have little-to-no toxicity information. The U.S. Toxicology in the 21st Century (Tox21) program has conducted a battery of in vitro assays using a quantitative high-throughput screening (qHTS) platform to gain toxicity information on environmental chemicals. Due to technical challenges, standard methods for providing xenobiotic metabolism could not be applied to qHTS assays. To address this limitation, we screened the Tox21 10,000-compound (10K) library, with concentrations ranging from 2.8 nM to 92 µM, using a p53 beta-lactamase reporter gene assay (p53-bla) alone or with rat liver microsomes (RLM) or human liver microsomes (HLM) supplemented with NADPH, to identify compounds that induce p53 signaling after biotransformation. Two hundred and seventy-eight compounds were identified as active under any of these three conditions. Of these 278 compounds, 73 gave more potent responses in the p53-bla assay with RLM, and 2 were more potent in the p53-bla assay with HLM compared with the responses they generated in the p53-bla assay without microsomes. To confirm the role of metabolism in the differential responses, we re-tested these 75 compounds in the absence of NADPH or with heat-attenuated microsomes. Forty-four compounds treated with RLM, but none with HLM, became less potent under these conditions, confirming the role of RLM in metabolic activation. Further evidence of biotransformation was obtained by measuring the half-life of the parent compounds in the presence of microsomes. Together, the data support the use of RLM in qHTS for identifying chemicals requiring biotransformation to induce biological responses.

Trophic Structure and Diet of Predatory Teleost Fishes in a Tropical Demersal Shelf Ecosystem - Conrad W. Speed; Mark G. Meekan; Matthew J. Birt; Miles J. G. Parsons; Dianne McLean; Brett M. Taylor; Luke Thomas; Robert McCauley; Jayson M. Semmens; Stephen J. Newman (Frontiers in Marine Science, 2022)
Predatory fishes are a major component of many tropical fisheries, although little is known about their diet and trophic structure, which can hinder effective management. We used stable isotopes δ 15 N and δ 13 C in conjunction with dietary prey items of five fishes ( Lutjanus sebae , Lethrinus punctulatus , Epinephelus areolatus , Epinephelus multinotatus , and Plectropomus maculatus ) to describe the diet and trophic structure across this assemblage. A total of 153 isotope and 87 stomach content samples were collected at two locations that were ≈30 km apart, over two sampling trips, separated by three months. There was clear separation of species’ mean δ 15 N and δ 13 C values in isotopic space; the highest mean δ 15 N was exhibited by E. multinotatus (13.50 ± 0.11 SE) and the lowest was L. punctulatus (11.05 ± 0.13). These two species had the lowest overlap of isotopic niche space, whereas the highest overlap occurred between L. sebae and P. maculatus . δ 15 N increased with fish body size for all species. However, body size was not significantly related to δ 13 C values for any species. There was a notable shift in both δ 15 N and δ 13 C between sampling trips, with δ 13 C being more depleted in the second trip. There was also a difference in δ 13 C between locations for all species, suggesting localised foraging. A multiple tissue comparison for L. sebae indicated positive relationships for both δ 15 N and δ 13 C between dorsal fin and muscle tissue. Mean δ 15 N values were the same for both fin (12.1 ± 0.10 SE) and muscle tissue (12.1 ± 0.09 SE), although δ 13 C was more enriched in fin (-15.6 ± 0.14 SE) compared to muscle tissue (-17.3 ± 0.11 SE). The most common dietary items across species were teleosts and crustaceans, which was consistent with isotope data indicating a reliance on a demersal food web (δ 13 C values ranging from -18 to -15‰). The results from our study indicate a dynamic spatio-temporal trophic structure and diet for commercially important demersal species and highlight the benefits of a multi-facetted sampling approach.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Tropical and subtropical Asia's valued tree species under threat - Hannes Gaisberger; Tobias Fremout; Chris J. Kettle; Barbara Vinceti; Della Kemalasari; Tania Kanchanarak; Evert Thomas; Josep M. Serra‐Diaz; Jens‐Christian Svenning; Ferry Slik; Wichan Eiadthong; Kandasamy Palanisamy; et al. (Conservation Biology, 2022)
Tree diversity in Asia's tropical and subtropical forests is central to nature‐based solutions. Species vulnerability to multiple threats, which affect provision of ecosystem services, is poorly understood. We conducted a region‐wide, spatially explicit assessment of the vulnerability of 63 socioeconomically important tree species to overexploitation, fire, overgrazing, habitat conversion, and climate change. Trees were selected for assessment from national priority lists, and selections were validated by an expert network representing 20 countries. We used Maxent suitability modeling to predict species distribution ranges, freely accessible spatial data sets to map threat exposures, and functional traits to estimate threat sensitivities. Species‐specific vulnerability maps were created as the product of exposure maps and sensitivity estimates. Based on vulnerability to current threats and climate change, we identified priority areas for conservation and restoration. Overall, 74% of the most important areas for conservation of these trees fell outside protected areas, and all species were severely threatened across an average of 47% of their native ranges. The most imminent threats were overexploitation and habitat conversion; populations were severely threatened by these factors in an average of 24% and 16% of their ranges, respectively. Our model predicted limited overall climate change impacts, although some study species were likely to lose over 15% of their habitat by 2050 due to climate change. We pinpointed specific natural areas in Borneo rain forests as hotspots for in situ conservation of forest genetic resources, more than 82% of which fell outside designated protected areas. We also identified degraded areas in Western Ghats, Indochina dry forests, and Sumatran rain forests as hotspots for restoration, where planting or assisted natural regeneration will help conserve these species, and croplands in southern India and Thailand as potentially important agroforestry options. Our results highlight the need for regionally coordinated action for effective conservation and restoration.

Development of duplex qPCR targeting Carnobacterium maltaromaticum and Vagococcus salmoninarum - Isaac Standish; Rebekah McCann; Corey Puzach; Eric Leis; Jennifer Bailey; Sara Dziki; Ryan Katona; Ellen Lark; Carey Edwards; Brandon Keesler; Stephen Reichley; Stacy King; et al. (Journal of Fish Diseases, 2022)
In November 2018, Vagococcus salmoninarum was identified as the causative agent of a chronic coldwater streptococcosis epizootic in broodstock brook trout ( Salvelinus fontinalis ) at the Iron River National Fish Hatchery in Wisconsin, USA. By February 2019, the epizootic spread to adjacent raceways containing broodstock lake trout ( Salvelinus namaycush ), whereby fish were found to be coinfected with Carnobacterium maltaromaticum and V . salmoninarum . To differentiate these two pathogens and determine the primary cause of the lake trout morbidity, a quantitative real‐time PCR (qPCR) was developed targeting the C . maltaromaticum phenylalanyl‐tRNA synthase alpha subunit ( pheS ) gene. The qPCR was combined with a V . salmoninarum qPCR, creating a duplex qPCR assay that simultaneously quantitates C. maltaromaticum and V . salmoninarum concentrations in individual lake trout tissues, and screens presumptive isolates from hatchery inspections and wild fish from national fish hatchery source waters throughout the Great Lakes basin. Vagococcus salmoninarum and C. maltaromaticum were co‐detected in broodstock brook trout from two tribal hatcheries and C. maltaromaticum was present in wild fish in source waters of several national fish hatcheries. This study provides a powerful new tool to differentiate and diagnose two emerging Gram‐positive bacterial pathogens.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Effects of human footprint and biophysical factors on the body‐size structure of fished marine species - Nestor E. Bosch; Jacquomo Monk; Jordan Goetze; Shaun Wilson; Russell C. Babcock; Neville Barrett; Jock Clough; Leanne M. Currey‐Randall; David V. Fairclough; Rebecca Fisher; Brooke A. Gibbons; David Harasti; et al. (Conservation Biology, 2022)
Marine fisheries in coastal ecosystems in many areas of the world have historically removed large‐bodied individuals, potentially impairing ecosystem functioning and the long‐term sustainability of fish populations. Reporting on size‐based indicators that link to food‐web structure can contribute to ecosystem‐based management, but the application of these indicators over large (cross‐ecosystem) geographical scales has been limited to either fisheries‐dependent catch data or diver‐based methods restricted to shallow waters (

Elucidating competing strategic behaviors using prospect theory, system dynamics, and evolutionary game: a case of transjurisdictional water pollution problem in China - Liang Yuan; Weijun He; Dagmawi Mulugeta Degefu; Yang Kong; Xia Wu; Shasha Xu; Zhongchi Wan; Thomas Stephen Ramsey (Environmental Science and Pollution Research, 2022)

Eoarchean subduction-like magmatism recorded in 3750 Ma mafic–ultramafic rocks of the Ukaliq supracrustal belt (Québec) - Thomas Grocolas; Pierre Bouilhol; Guillaume Caro; Stephen J. Mojzsis (Contributions to Mineralogy and Petrology, 2022)
Our understanding of the nature of crustal formation in the Eoarchean is limited by the scarcity and poor preservation of the oldest rocks and variable and imperfect preservation of protolith magmatic signatures. These limitations hamper our ability to place quantitative constraints on thermomechanical models for early crustal genesis and hence on the operative geodynamic regimes at that time. The recently discovered ca. 3.75 Ga Ukaliq supracrustal enclave (northern Québec) is mainly composed of variably deformed and compositionally diverse serpentinized ultramafic rocks and amphibolitized mafic schists whose metamorphic peak, inferred from phase equilibria modeling, was below 720 °C. Inferred protoliths to the Ukaliq ultramafic rocks include cumulative dunites, pyroxenites, and gabbros, whereas the mafic rocks were probably picrites, basalts, and basaltic andesites. The bulk-rock and mineral chemistry documents the partial preservation of cumulative pyroxenes and probably amphiboles and demonstrates the occurrence of a clinopyroxene-dominated, tholeiitic suite and an orthopyroxene-dominated, boninite-like suite. Together with the presence of negative μ 142 Nd anomalies in the boninitic basalts, two liquid lines of descent are inferred: (i) a damp tholeiitic sequence resulting from the fractionation of a basaltic liquid produced by mantle decompression; and (ii) a boninitic suite documenting the evolution of an initially primitive basaltic andesite liquid produced by flux melting. Petrographic observations, thermodynamic modeling, bulk-rock and mineral chemistry, and 142 Nd isotopic compositions identify the Ukaliq supracrustal belt as the remnant of an Eoarchean arc crust produced by the recycling of Hadean crust in a similar way as modern-style subduction.

Examining the Potential Formation of Ternary Chromium-Histidine-DNA Complexes and Implications for Their Carcinogenicity - Emma Lankford; C. Sumner Thomas; Sydney Marchi; Silas Brown; Stephen A. Woski; John B. Vincent (Biological Trace Element Research, 2022)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Correction to: A Standards Organization for Open and FAIR Neuroscience: the International Neuroinformatics Coordinating Facility - Mathew Birdsall Abrams; Jan G. Bjaalie; Samir Das; Gary F. Egan; Satrajit S. Ghosh; Wojtek J. Goscinski; Jeffrey S. Grethe; Jeanette Hellgren Kotaleski; Eric Tatt Wei Ho; David N. Kennedy; Linda J. Lanyon; Trygve B. Leergaard; et al. (Neuroinformatics, 2022)

A Standards Organization for Open and FAIR Neuroscience: the International Neuroinformatics Coordinating Facility - Mathew Birdsall Abrams; Jan G. Bjaalie; Samir Das; Gary F. Egan; Satrajit S. Ghosh; Wojtek J. Goscinski; Jeffrey S. Grethe; Jeanette Hellgren Kotaleski; Eric Tatt Wei Ho; David N. Kennedy; Linda J. Lanyon; Trygve B. Leergaard; et al. (Neuroinformatics, 2022)
There is great need for coordination around standards and best practices in neuroscience to support efforts to make neuroscience a data-centric discipline. Major brain initiatives launched around the world are poised to generate huge stores of neuroscience data. At the same time, neuroscience, like many domains in biomedicine, is confronting the issues of transparency, rigor, and reproducibility. Widely used, validated standards and best practices are key to addressing the challenges in both big and small data science, as they are essential for integrating diverse data and for developing a robust, effective, and sustainable infrastructure to support open and reproducible neuroscience. However, developing community standards and gaining their adoption is difficult. The current landscape is characterized both by a lack of robust, validated standards and a plethora of overlapping, underdeveloped, untested and underutilized standards and best practices. The International Neuroinformatics Coordinating Facility (INCF), an independent organization dedicated to promoting data sharing through the coordination of infrastructure and standards, has recently implemented a formal procedure for evaluating and endorsing community standards and best practices in support of the FAIR principles. By formally serving as a standards organization dedicated to open and FAIR neuroscience, INCF helps evaluate, promulgate, and coordinate standards and best practices across neuroscience. Here, we provide an overview of the process and discuss how neuroscience can benefit from having a dedicated standards body.

Agricultural breadbaskets shift poleward given adaptive farmer behavior under climate change - James A. Franke; Christoph Müller; Sara Minoli; Joshua Elliott; Christian Folberth; Charles Gardner; Tobias Hank; Roberto Cesar Izaurralde; Jonas Jägermeyr; Curtis D. Jones; Wenfeng Liu; Stefan Olin; et al. (Global Change Biology, 2022)
Modern food production is spatially concentrated in global “breadbaskets.” A major unresolved question is whether these peak production regions will shift poleward as the climate warms, allowing some recovery of potential climate‐related losses. While agricultural impacts studies to date have focused on currently cultivated land, the Global Gridded Crop Model Intercomparison Project (GGCMI) Phase 2 experiment allows us to assess changes in both yields and the location of peak productivity regions under warming. We examine crop responses under projected end of century warming using seven process‐based models simulating five major crops (maize, rice, soybeans, and spring and winter wheat) with a variety of adaptation strategies. We find that in no‐adaptation cases, when planting date and cultivar choices are held fixed, regions of peak production remain stationary and yield losses can be severe, since growing seasons contract strongly with warming. When adaptations in management practices are allowed (cultivars that retain growing season length under warming and modified planting dates), peak productivity zones shift poleward and yield losses are largely recovered. While most growing‐zone shifts are ultimately limited by geography, breadbaskets studied here move poleward over 600 km on average by end of the century under RCP 8.5. These results suggest that agricultural impacts assessments can be strongly biased if restricted in spatial area or in the scope of adaptive behavior considered. Accurate evaluation of food security under climate change requires global modeling and careful treatment of adaptation strategies.

Maximum heat ratio: bi-directional method for fast and slow sap flow measurements - Jose Gutierrez Lopez; Thomas Pypker; Julian Licata; Stephen S. O. Burgess; Heidi Asbjornsen (Plant and Soil, 2021)
Background As sap flow research expands, new challenges such as fast sap flows or flows co-occurring with freeze/thaw cycles appear, which are not easily addressed with existing methods. In order to address these new challenges, sap flow methods capable of measuring bidirectional, high and slow sap flux densities ( F d , cm 3 cm −2 h −1 ), thermal properties and stem water content with minimum sensitivity to stem temperature are required. Purpose In this study we assessed the performance of a new low-power ratio-based algorithm, the maximum heat ratio ( MHR ) method, and compare it with the widely known heat ratio ( HR ) method using a cut-tree study to test it under high flows using Eucalyptus grandis trees, and a freeze/thaw experiment using Acer saccharum trunks to test its response to fast changing stem temperatures that result in freeze/thaw cycles. Results Our results indicate that MHR and HR had a strong (R 2 = 0.90) linear relationship within a F d range of 0–45 cm 3 cm −2 h −1 . Using the MHR algorithm, we were able to estimate wood thermal properties and water content, while extending the measuring range of HR to approximately 0–130 (cm 3 cm −2 h −1 ). In our freeze/thaw experiment, the main discrepancy between MHR and HR was observed during freezing, where HR had consistently lower F d (up to 10 cm 3 cm −2 h −1 ), with respect to MHR. However, both algorithms identified similar zero flows. Conclusion Consequently, MHR can be an easy-to-implement alternative algorithm/method capable of handling extreme climatic conditions, which can also run simultaneously with HR.

Towards a global list of accepted species V. The devil is in the detail - Richard L. Pyle; Saroj K. Barik; Les Christidis; Stijn Conix; Mark John Costello; Peter Paul van Dijk; Stephen T. Garnett; Donald Hobern; Paul M. Kirk; Aaron M. Lien; Thomas M. Orrell; David Remsen; et al. (Organisms Diversity & Evolution, 2021)

Towards a global list of accepted species VI: The Catalogue of Life checklist - Donald Hobern; Saroj K. Barik; Les Christidis; Stephen T.Garnett; Paul Kirk; Thomas M. Orrell; Thomas Pape; Richard L. Pyle; Kevin R. Thiele; Frank E. Zachos; Olaf Bánki (Organisms Diversity & Evolution, 2021)

Petrosal Anatomy of the Paleocene Eutherian Mammal Deltatherium fundaminis (Cope, 1881) - Sarah L. Shelley; Ornella C. Bertrand; Stephen L. Brusatte; Thomas E. Williamson (Journal of Mammalian Evolution, 2021)
We describe the tympanic anatomy of the petrosal of Deltatherium fundaminis, an enigmatic Paleocene mammal based on cranial specimens recovered from New Mexico, U.S.A. Although the ear region of Deltatherium has previously been described, there has not been a comprehensive, well-illustrated contribution using current anatomical terminology. The dental and cranial anatomy of Deltatherium is a chimera, with morphological similarities to both ‘condylarth’ and ‘cimolestan’ taxa. As such, the phylogenetic relationships of this taxon have remained elusive since its discovery, and it has variably been associated with Arctocyonidae, Pantodonta and Tillodontia. The petrosal of Deltatherium is anteriorly bordered by an open space comprising a contiguous carotid opening and pyriform fenestra. The promontorium features both a small rostral tympanic process and small epitympanic wing but lacks well-marked sulci. A large ventral facing external aperture of the canaliculus cochleae is present and bordered posteriorly by a well-developed caudal tympanic process. The hiatus Fallopii opens on the ventral surface of the petrosal. The tegmen tympani is mediolaterally broad and anteriorly expanded, and its anterior margin is perforated by a foramen for the ramus superior of the stapedial artery. The tympanohyal is small but approximates the caudal tympanic process to nearly enclose the stylomastoid notch. The mastoid is widely exposed on the basicranium and bears an enlarged mastoid process, separate from the paraoccipital process. These new observations provide novel anatomical data corroborating previous hypotheses regarding the plesiomorphic eutherian condition but also reveal subtle differences among Paleocene eutherians that have the potential to help inform the phylogeny of Deltatherium.

Correction to: Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)

Comparison of benthic macroinvertebrate assessment methods along a salinity gradient in headwater streams - Rachel A. Pence; Thomas R. Cianciolo; Damion R. Drover; Daniel L. McLaughlin; David J. Soucek; Anthony J. Timpano; Carl E. Zipper; Stephen H. Schoenholtz (Environmental Monitoring and Assessment, 2021)

Density data for Lake Ontario benthic invertebrate assemblages from 1964 to 2018 - Lyubov E. Burlakova; Alexander Y. Karatayev; Allison R. Hrycik; Susan E. Daniel; Knut Mehler; Lars G. Rudstam; James M. Watkins; Ronald Dermott; Jill Scharold; Ashley K. Elgin; Thomas F. Nalepa; Elizabeth K. Hinchey; et al. (Ecology, 2021)
Benthic invertebrates are important trophic links in aquatic food webs and serve as useful bioindicators of environmental conditions because their responses integrate the effects of both water and sediment qualities. However, long‐term data sets for benthic invertebrate assemblages across broad geographic areas are rare and, even if collected, historic data sets are often not readily accessible. This data set provides densities of benthic macroinvertebrates for all taxa collected during lake‐wide surveys in Lake Ontario, a Laurentian Great Lake, from 1964 to 2018. This information resulted from surveys funded by the governments of the United States and Canada to investigate the status and changes of Lake Ontario benthic community. Of the 13 lake‐wide benthic surveys conducted in Lake Ontario over the course of 54 yr, we were able to acquire taxonomic data to the species level for 11 of the surveys and data to the group level for the other two surveys. Density data are provided for taxa representing the Annelida, Arthropoda, Mollusca, Cnidaria, Nemertea, and Platyhelminthes phyla. Univariate and multivariate analyses revealed that the compositional structure of Lake Ontario invertebrate assemblages differed markedly by depth and were also significantly altered by the Dreissena spp. invasion in early 1990s. The introduction of invasive dreissenids has changed the community historically dominated by Diporeia , Oligochaeta, and Sphaeriidae, to a community dominated by quagga mussels and Oligochaeta. Considering the rarity of long‐term benthic data of high taxonomic resolution in lake ecosystems, this data set could be useful to explore broader aspects of ecological theory, including effects of different environmental factors and invasive species on community organization, functional and phylogenetic diversity, and spatial scale of variation in community structure. The data set could also be useful for studies on individual species including abundance and distribution, species co‐occurrence, and how the patterns of dominance and rarity change over space and time. Use of this data set for academic or educational purposes is encouraged as long as the data source is properly cited using the title of this Data Paper, the names of the authors, the year of publication, the journal name, and the article number.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Effects of inescapable stress on responses to social incentive stimuli and modulation by escitalopram - Stephen Daniels; Danielle Lemaire; Thomas Lapointe; Cheryl Limebeer; Linda Parker; Francesco Leri (Psychopharmacology, 2021)

The success of the Montreal Protocol in mitigating interactive effects of stratospheric ozone depletion and climate change on the environment - Paul W. Barnes; Janet F. Bornman; Krishna K. Pandey; Germar H. Bernhard; Alkiviadis F. Bais; Rachel E. Neale; Thomas Matthew Robson; Patrick J. Neale; Craig E. Williamson; Richard G. Zepp; Sasha Madronich; Stephen R. Wilson; et al. (Global Change Biology, 2021)

Correction to: Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

Coupled human and natural systems: The evolution and applications of an integrated framework - Jianguo Liu; Thomas Dietz; Stephen R. Carpenter; William W. Taylor; Marina Alberti; Peter Deadman; Charles Redman; Alice Pell; Carl Folke; Zhiyun Ouyang; Jane Lubchenco (Ambio, 2021)

Resilience: Now more than ever - Carl Folke; Stephen Carpenter; Thomas Elmqvist; Lance Gunderson; Brian Walker (Ambio, 2021)

Divergent climate change effects on widespread dryland plant communities driven by climatic and ecohydrological gradients - Kyle A. Palmquist; Daniel R. Schlaepfer; Rachel R. Renne; Stephen C. Torbit; Kevin E. Doherty; Thomas E. Remington; Greg Watson; John B. Bradford; William K. Lauenroth (Global Change Biology, 2021)
Plant community response to climate change will be influenced by individual plant responses that emerge from competition for limiting resources that fluctuate through time and vary across space. Projecting these responses requires an approach that integrates environmental conditions and species interactions that result from future climatic variability. Dryland plant communities are being substantially affected by climate change because their structure and function are closely tied to precipitation and temperature, yet impacts vary substantially due to environmental heterogeneity, especially in topographically complex regions. Here, we quantified the effects of climate change on big sagebrush ( Artemisia tridentata Nutt.) plant communities that span 76 million ha in the western United States. We used an individual‐based plant simulation model that represents intra‐ and inter‐specific competition for water availability, which is represented by a process‐based soil water balance model. For dominant plant functional types, we quantified changes in biomass and characterized agreement among 52 future climate scenarios. We then used a multivariate matching algorithm to generate fine‐scale interpolated surfaces of functional type biomass for our study area. Results suggest geographically divergent responses of big sagebrush to climate change (changes in biomass of −20% to +27%), declines in perennial C 3 grass and perennial forb biomass in most sites, and widespread, consistent, and sometimes large increases in perennial C 4 grasses. The largest declines in big sagebrush, perennial C 3 grass and perennial forb biomass were simulated in warm, dry sites. In contrast, we simulated no change or increases in functional type biomass in cold, moist sites. There was high agreement among climate scenarios on climate change impacts to functional type biomass, except for big sagebrush. Collectively, these results suggest divergent responses to warming in moisture‐limited versus temperature‐limited sites and potential shifts in the relative importance of some of the dominant functional types that result from competition for limiting resources.

When hazard avoidance is not an option: lessons learned from monitoring the postdisaster Oso landslide, USA - Mark E. Reid; Jonathan W. Godt; Richard G. LaHusen; Stephen L. Slaughter; Thomas C. Badger; Brian D. Collins; William H. Schulz; Rex L. Baum; Jeffrey A. Coe; Edwin L. Harp; Kevin M. Schmidt; Richard M. Iverson; et al. (Landslides, 2021)
On 22 March 2014, a massive, catastrophic landslide occurred near Oso, Washington, USA, sweeping more than 1 km across the adjacent valley flats and killing 43 people. For the following 5 weeks, hundreds of workers engaged in an exhaustive search, rescue, and recovery effort directly in the landslide runout path. These workers could not avoid the risks posed by additional large-scale slope collapses. In an effort to ensure worker safety, multiple agencies cooperated to swiftly deploy a monitoring and alerting system consisting of sensors, automated data processing and web-based display, along with defined communication protocols and clear calls to action for emergency management and search personnel. Guided by the principle that an accelerating landslide poses a greater threat than a steadily moving or stationary mass, the system was designed to detect ground motion and vibration using complementary monitoring techniques. Near real-time information was provided by continuous GPS, seismometers/geophones, and extensometers. This information was augmented by repeat-assessment techniques such as terrestrial and aerial laser scanning and time-lapse photography. Fortunately, no major additional landsliding occurred. However, we did detect small headscarp failures as well as slow movement of the remaining landslide mass with the monitoring system. This was an exceptional response situation and the lessons learned are applicable to other landslide disaster crises. They underscore the need for cogent landslide expertise and ready-to-deploy monitoring equipment, the value of using redundant monitoring techniques with distinct goals, the benefit of clearly defined communication protocols, and the importance of continued research into forecasting landslide behavior to allow timely warning.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Molecular Regulation of Lysophosphatidic Acid Receptor 1 Maturation and Desensitization - Jing Zhao; Thomas Stephens; Yutong Zhao (Cell Biochemistry and Biophysics, 2021)

Warm winters and cool springs negatively influence recruitment of Atlantic salmon ( Salmo salar L.) in a southern England chalk stream - Jessica E. Marsh; Rasmus B. Lauridsen; William D. Riley; Olivia M. Simmons; Céline Artero; Luke J. Scott; William R. C. Beaumont; William A. Beaumont; John Davy‐Bowker; Thomas Lecointre; Dylan E. Roberts; Stephen D. Gregory (Journal of Fish Biology, 2021)
Previous work suggests that juvenile salmon recruitment in rain‐fed rivers is negatively influenced by warm and wet winters and cool springs. We tested whether this is generally applicable to a southern England chalk stream characterized by comparatively stable discharges and temperatures. We found that warm spawning and cool emergence temperatures negatively influenced juvenile recruitment between 2015 and 2020. Together these findings suggest an ability to predict juvenile productivity from water temperature records around spawning and fry emergence, thereby allowing time for management interventions in years of unfavourable temperatures.

Increased connectivity and depth improve the effectiveness of marine reserves - Jordan S. Goetze; Shaun Wilson; Ben Radford; Rebecca Fisher; Tim J. Langlois; Jacquomo Monk; Nathan A. Knott; Hamish Malcolm; Leanne M. Currey‐Randall; Daniel Ierodiaconou; David Harasti; Neville Barrett; et al. (Global Change Biology, 2021)
Marine reserves are a key tool for the conservation of marine biodiversity, yet only ~2.5% of the world's oceans are protected. The integration of marine reserves into connected networks representing all habitats has been encouraged by international agreements, yet the benefits of this design has not been tested empirically. Australia has one of the largest systems of marine reserves, providing a rare opportunity to assess how connectivity influences conservation success. An Australia‐wide dataset was collected using baited remote underwater video systems deployed across a depth range from 0 to 100 m to assess the effectiveness of marine reserves for protecting teleosts subject to commercial and recreational fishing. A meta‐analytical comparison of 73 fished species within 91 marine reserves found that, on average, marine reserves had 28% greater abundance and 53% greater biomass of fished species compared to adjacent areas open to fishing. However, benefits of protection were not observed across all reserves (heterogeneity), so full subsets generalized additive modelling was used to consider factors that influence marine reserve effectiveness, including distance‐based and ecological metrics of connectivity among reserves. Our results suggest that increased connectivity and depth improve the aforementioned marine reserve benefits and that these factors should be considered to optimize such benefits over time. We provide important guidance on factors to consider when implementing marine reserves for the purpose of increasing the abundance and size of fished species, given the expected increase in coverage globally. We show that marine reserves that are highly protected (no‐take) and designed to optimize connectivity, size and depth range can provide an effective conservation strategy for fished species in temperate and tropical waters within an overarching marine biodiversity conservation framework.

A Novel Orthoreovirus Isolated From Dead Stranded Harbor Seals From Puget Sound, Washington State, United States - Ole Nielsen; Thaís C. S. Rodrigues; Vsevolod L. Popov; Kuttichantran Subramaniam; Thomas B. Waltzek; Dyanna M. Lambourn; Stephen Raverty (Frontiers in Marine Science, 2021)
As part of an ongoing investigation of harbor seal ( Phoca vitulina ) mortalities within Puget Sound, Washington State, United States, between October 2007 and July 2008, 25 seal cases were submitted for histopathology and ancillary diagnostic testing, including additional attempted virus isolation. In vitro granular and refractile cytopathic effects (CPE) were consistently observed in Vero.DogSLAMtag cells inoculated with tissue homogenates from three seals. Transmission electron microscopy of infected Vero.DogSLAMtag cells revealed cytoplasmic clusters of icosahedral viral particles morphologically consistent with members of the family Reoviridae . The complete genome of a novel species within the genus Orthoreovirus , tentatively named phocid orthoreovirus 1 (PhRV1), was determined by next-generation sequencing and confirmed by rt-PCR in isolates from the three harbor seals. This is the first report of an orthoreovirus infection associated with dead stranded harbor seals. Aside from the CPE and ultrastructural findings, no consistent signalment, gross pathology, histopathology, or ancillary diagnostic findings were identified with PhRV1 infection. Further research is needed to determine the prevalence, tissue tropism, transmission, pathogenicity, zoonotic potential, and host range of orthoreoviruses in pinnipeds. This study demonstrates the value of thorough necropsy investigations and a multidisciplinary team approach to advance our understanding of marine mammal health.

Changes in the Movement and Calling Behavior of Minke Whales (Balaenoptera acutorostrata) in Response to Navy Training - Ian N. Durbach; Catriona M. Harris; Cameron Martin; Tyler A. Helble; E. Elizabeth Henderson; Glenn Ierley; Len Thomas; Stephen W. Martin (Frontiers in Marine Science, 2021)
Many marine mammals rely on sound for foraging, maintaining group cohesion, navigation, finding mates, and avoiding predators. These behaviors are potentially disrupted by anthropogenic noise. Behavioral responses to sonar have been observed in a number of baleen whale species but relatively little is known about the responses of minke whales ( Balaenoptera acutorostrata ). Previous analyses demonstrated a spatial redistribution of localizations derived from passive acoustic detections in response to sonar activity, but the lack of a mechanism for associating localizations prevented discriminating between movement and cessation of calling as possible explanations for this redistribution. Here we extend previous analyses by including an association mechanism, allowing us to differentiate between movement responses and calling responses, and to provide direct evidence of horizontal avoidance responses by individual minke whales to sonar during U.S. Navy training activities. We fitted hidden Markov models to 627 tracks that were reconstructed from 3 years of minke whale ( B. acutorostrata ) vocalizations recorded before, during, and after naval training events at the U.S. Navy’s Pacific Missile Range Facility, Kauai, Hawaii. The fitted models were used to identify different movement behaviors and to investigate the effect of sonar activity on these behaviors. Movement was faster and more directed during sonar exposure than in baseline phases. The mean direction of movement differed during sonar exposure, and was consistent with movement away from sonar-producing ships. Animals were also more likely to cease calling during sonar. There was substantial individual variation in response. Our findings add large-sample support to previous demonstrations of horizontal avoidance responses by individual minke whales to sonar in controlled exposure experiments, and demonstrate the complex nature of behavioral responses to sonar activity: some, but not all, whales exhibited behavioral changes, which took the form of horizontal avoidance or ceasing to call.

Leech blood‐meal invertebrate‐derived DNA reveals differences in Bornean mammal diversity across habitats - Rosie Drinkwater; Tommaso Jucker; Joshua H. T. Potter; Tom Swinfield; David A. Coomes; Eleanor M. Slade; M. Thomas P. Gilbert; Owen T. Lewis; Henry Bernard; Matthew J. Struebig; Elizabeth L. Clare; Stephen J. Rossiter (Molecular Ecology, 2021)
The application of metabarcoding to environmental and invertebrate‐derived DNA (eDNA and iDNA) is a new and increasingly applied method for monitoring biodiversity across a diverse range of habitats. This approach is particularly promising for sampling in the biodiverse humid tropics, where rapid land‐use change for agriculture means there is a growing need to understand the conservation value of the remaining mosaic and degraded landscapes. Here we use iDNA from blood‐feeding leeches ( Haemadipsa picta ) to assess differences in mammalian diversity across a gradient of forest degradation in Sabah, Malaysian Borneo. We screened 557 individual leeches for mammal DNA by targeting fragments of the 16S rRNA gene and detected 14 mammalian genera. We recorded lower mammal diversity in the most heavily degraded forest compared to higher quality twice logged forest. Although the accumulation curves of diversity estimates were comparable across these habitat types, diversity was higher in twice logged forest, with more taxa of conservation concern. In addition, our analysis revealed differences between the community recorded in the heavily logged forest and that of the twice logged forest. By revealing differences in mammal diversity across a human‐modified tropical landscape, our study demonstrates the value of iDNA as a noninvasive biomonitoring approach in conservation assessments.

The evolution of the terrestrial‐terminating Irish Sea glacier during the last glaciation - Richard Christopher Chiverrell; Geoff Stephen Powell Thomas; Matthew Burke; Alicia Medialdea; Rachel Smedley; Mark Bateman; Chris Clark; Geoffrey A. T. Duller; Derek Fabel; Geraint Jenkins; Xianjiao Ou; Helen Marie Roberts; et al. (Journal of Quaternary Science, 2021)
Here we reconstruct the last advance to maximum limits and retreat of the Irish Sea Glacier (ISG), the only land‐terminating ice lobe of the western British Irish Ice Sheet. A series of reverse bedrock slopes rendered proglacial lakes endemic, forming time‐transgressive moraine‐ and bedrock‐dammed basins that evolved with ice marginal retreat. Combining, for the first time on glacial sediments, optically stimulated luminescence (OSL) bleaching profiles for cobbles with single grain and small aliquot OSL measurements on sands, has produced a coherent chronology from these heterogeneously bleached samples. This chronology constrains what is globally an early build‐up of ice during late Marine Isotope Stage 3 and Greenland Stadial (GS) 5, with ice margins reaching south Lancashire by 30 ± 1.2 ka, followed by a 120‐km advance at 28.3 ± 1.4 ka reaching its 26.5 ± 1.1 ka maximum extent during GS‐3. Early retreat during GS‐3 reflects piracy of ice sources shared with the Irish‐Sea Ice Stream (ISIS), starving the ISG. With ISG retreat, an opportunistic readvance of Welsh ice during GS‐2 rode over the ISG moraines occupying the space vacated, with ice margins oscillating within a substantial glacial over‐deepening. Our geomorphological chronosequence shows a glacial system forced by climate but mediated by piracy of ice sources shared with the ISIS, changing flow regimes and fronting environments.

Microbiology of a NaCl stalactite ‘salticle’ in Triassic halite - Thomas P. Thompson; Stephen A. Kelly; Timofey Skvortsov; Gill Plunkett; Alastair Ruffell; John E. Hallsworth; Jason Hopps; Brendan F. Gilmore (Environmental Microbiology, 2021)
Summary Large regions of Earth's surface are underlain by salt deposits that evaporated from ancient oceans and are populated by extreme halophilic microbes. Some of these halophiles may have been preserved over geological timescales within hypersaline fluid inclusions, but ingresses of water and/or anthropogenic activities can lead to the formation of alternative habitats, including NaCl stalactites or other speleothems. While the microbiology of ancient evaporites has been well studied, the ecology of these recently formed structures is less‐well understood. Here, the microbiology of a NaCl stalactite (‘salticle’) in a Triassic halite mine is characterized. The specific aims were to determine the presence of fluid inclusions, determine the microbial structure of the salticle compared with a nearby brine‐pool and surficial soil, and characterize the ecophysiological capabilities of this unique ecosystem. The salticle contained fluid inclusions, and their microbiome was composed of Euryarchaetota, Proteobacteria, and Actinobacteria, with Haloarchaea in greater abundance than brine‐pool or soil microbiomes. The salticle metagenome exhibited a greater abundance of genes involved in osmoregulation, anaerobic respiration, UV resistance, oxidative stress, and stress‐protein synthesis relative to the soil microbiome. We discuss the potential astrobiological implications of salticles as enclosed salt‐saturated habitats that are protected from ionizing radiation and have a stable water activity.

Controls on Nutrient Cycling in Estuarine Mangrove Lake Sediments - Michael S. Owens; Stephen P. Kelly; Thomas A. Frankovich; David T. Rudnick; James W. Fourqurean; Jeffrey C. Cornwell (Journal of Marine Science and Engineering, 2021)
We estimated the net exchange of nitrogen and phosphorus species using core incubations under light and dark conditions in estuarine lakes that are the aquatic interface between the freshwater Everglades and marine Florida Bay. These lakes and adjacent shallow water Florida Bay environments are sites where the restoration of hydrological flows will likely have the largest impact on salinity. Sediment respiration, measured by oxygen uptake, averaged (±S.D.) −2400 ± 1300, −300 ± 1000, and 1900 ± 1400 μmol m−2 h−1 for dark incubations, light incubations, and gross photosynthesis estimates, respectively, with dark incubations consistent with oxygen uptake measured by microelectrode profiles. Although most fluxes of soluble reactive phosphorus, nitrate, and N2–N were low under both light and dark incubation conditions, we observed a number of very high efflux events of NH4+ during dark incubations. A significant decrease in NH4+flux was observed in the light. The largest differences between light and dark effluxes of NH4+ occurred in lakes during periods of low coverage of the aquatic macrophyte Chara hornemannii Wallman, with NH4+ effluxes > 200 μmol m−2 h−1. Increasing freshwater flow from the Everglades is expected to expand lower salinity environments suitable for Chara, and therefore, diminish the sediment NH4+ effluxes that may fuel algal blooms.

Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)
Microscale thermophoresis (MST), and the closely related Temperature Related Intensity Change (TRIC), are synonyms for a recently developed measurement technique in the field of biophysics to quantify biomolecular interactions, using the (capillary-based) NanoTemper Monolith and (multiwell plate-based) Dianthus instruments. Although this technique has been extensively used within the scientific community due to its low sample consumption, ease of use, and ubiquitous applicability, MST/TRIC has not enjoyed the unambiguous acceptance from biophysicists afforded to other biophysical techniques like isothermal titration calorimetry (ITC) or surface plasmon resonance (SPR). This might be attributed to several facts, e.g., that various (not fully understood) effects are contributing to the signal, that the technique is licensed to only a single instrument developer, NanoTemper Technology, and that its reliability and reproducibility have never been tested independently and systematically. Thus, a working group of ARBRE-MOBIEU has set up a benchmark study on MST/TRIC to assess this technique as a method to characterize biomolecular interactions. Here we present the results of this study involving 32 scientific groups within Europe and two groups from the US, carrying out experiments on 40 Monolith instruments , employing a standard operation procedure and centrally prepared samples. A protein–small molecule interaction, a newly developed protein–protein interaction system and a pure dye were used as test systems. We characterized the instrument properties and evaluated instrument performance, reproducibility, the effect of different analysis tools, the influence of the experimenter during data analysis, and thus the overall reliability of this method.

Macroecological patterns of forest structure and allometric scaling in mangrove forests - Andre S. Rovai; Robert R. Twilley; Edward Castañeda‐Moya; Stephen R. Midway; Daniel A. Friess; Carl C. Trettin; Jacob J. Bukoski; Atticus E.L. Stovall; Paulo R. Pagliosa; Alessandra L. Fonseca; Richard A. Mackenzie; Aslan Aslan; et al. (Global Ecology and Biogeography, 2021)
Aim Mangrove wetlands span broad geographical gradients, resulting in functionally diverse tree communities. We asked whether latitudinal variation, allometric scaling relationships and species composition influence mangrove forest structure and biomass allocation across biogeographical regions and distinct coastal morphologies. Location Global. Time period Present. Major taxa studied Mangrove ecosystems. Methods We built the largest field‐based dataset on mangrove forest structure and biomass to date ( c . 2,800 plots from 67 countries) to address macroecological questions pertaining to structural and functional diversity of mangroves spanning biogeographical and coastal morphology gradients. We used frequentist inference statistics and machine learning models to determine environmental drivers that control biomass allocation within and across mangrove communities globally. Results Allometric scaling relationships and forest structural complexity were consistent across biogeographical and coastal morphology gradients, suggesting that mangrove biomass is controlled by regional forcings rather than by latitude or species composition. For instance, nearly 40% of the global variation in biomass was explained by regional climate and hydroperiod, revealing nonlinear thresholds that control biomass accumulation across broad geographical gradients. Furthermore, we found that ecosystem‐level carbon stocks (average 401 ± 48 MgC/ha, covering biomass and the top 1 m of soil) varied little across diverse coastal morphologies, reflecting regional bottom‐up geomorphic controls that shape global patterns in mangrove biomass apportioning. Main conclusions Our findings reconcile views of wetland and terrestrial forest macroecology. Similarities in stand structural complexity and cross‐site size–density relationships across multiscale environmental gradients show that resource allocation in mangrove ecosystems is independent of tree size and invariant to species composition or latitude. Mangroves follow a universal fractal‐based scaling relationship that describes biomass allocation for several other terrestrial tree‐dominated communities. Understanding how mangroves adhere to these universal allometric rules can improve our ability to account for biomass apportioning and carbon stocks in response to broad geographical gradients.

Sexual Mismatch Between Vessel-Associated Foraging and Discard Consumption in a Marine Top Predator - Joan Giménez; Gavin E. Arneill; Ashley Bennison; Enrico Pirotta; Hans D. Gerritsen; Thomas W. Bodey; Stuart Bearhop; Keith C. Hamer; Stephen Votier; Mark Jessopp (Frontiers in Marine Science, 2021)
Sex differences in diet and foraging behaviour are common in sexually dimorphic species, often driven by differences in the cost of locomotion or ability to exploit different ecological niches. However, sex-specific foraging strategies also occur in monomorphic or slightly dimorphic species where the drivers are poorly understood. Here, we study sex differences in foraging of northern gannets ( Morus bassanus ), where females are only slightly heavier than males. Using concurrently tracked gannets (298 full foraging trips from 81 individuals) and fishing vessels across 5 years, we quantify individual-based vessel-associated putative foraging, and relate this to discard consumption. We found a significant positive relationship between time spent in vessel-associated foraging and discard consumption for both sexes. However, while females showed greater proportions of vessel-associated foraging than males, discarded fish contributed less to the diet of females in all years. These results contrast with previous suggestions that female gannets interact with vessels less often than males, and are consistent with competitive exclusion of females from trawler-associated discards. Our findings give insight into sexual differences in foraging behaviour in the absence of dimorphism that are necessary to predict their response to environmental and anthropogenic changes.

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Forest responses to last‐millennium hydroclimate variability are governed by spatial variations in ecosystem sensitivity - Christine R. Rollinson; Andria Dawson; Ann M. Raiho; John W. Williams; Michael C. Dietze; Thomas Hickler; Stephen T. Jackson; Jason McLachlan; David JP Moore; Benjamin Poulter; Tristan Quaife; Jörg Steinkamp; et al. (Ecology Letters, 2021)
Forecasts of future forest change are governed by ecosystem sensitivity to climate change, but ecosystem model projections are under‐constrained by data at multidecadal and longer timescales. Here, we quantify ecosystem sensitivity to centennial‐scale hydroclimate variability, by comparing dendroclimatic and pollen‐inferred reconstructions of drought, forest composition and biomass for the last millennium with five ecosystem model simulations. In both observations and models, spatial patterns in ecosystem responses to hydroclimate variability are strongly governed by ecosystem sensitivity rather than climate exposure. Ecosystem sensitivity was higher in models than observations and highest in simpler models. Model‐data comparisons suggest that interactions among biodiversity, demography and ecophysiology processes dampen the sensitivity of forest composition and biomass to climate variability and change. Integrating ecosystem models with observations from timescales extending beyond the instrumental record can better understand and forecast the mechanisms regulating forest sensitivity to climate variability in a complex and changing world.

Can crown variables increase the generality of individual tree biomass equations? - David I. Forrester; Ian C. Dumbrell; Stephen R. Elms; Keryn I. Paul; Elizabeth A. Pinkard; Stephen H. Roxburgh; Thomas G. Baker (Trees, 2021)

Effect of Multi-strain Probiotic Formulation on Students Facing Examination Stress: a Double-Blind, Placebo-Controlled Study - Rajesh Venkataraman; Ratna Sudha Madempudi; Jayanthi Neelamraju; Jayesh J. Ahire; H. R. Vinay; Anila Lal; Glory Thomas; Stephy Stephen (Probiotics and Antimicrobial Proteins, 2021)

Long‐term change in the avifauna of undisturbed Amazonian rainforest: ground‐foraging birds disappear and the baseline shifts - Philip C Stouffer; Vitek Jirinec; Cameron L. Rutt; Richard O. Bierregaard; Angélica Hernández‐Palma; Erik I. Johnson; Stephen R. Midway; Luke L. Powell; Jared D. Wolfe; Thomas E. Lovejoy (Ecology Letters, 2021)
How are rainforest birds faring in the Anthropocene? We use bird captures spanning > 35 years from 55 sites within a vast area of intact Amazonian rainforest to reveal reduced abundance of terrestrial and near‐ground insectivores in the absence of deforestation, edge effects or other direct anthropogenic landscape change. Because undisturbed forest includes far fewer terrestrial and near‐ground insectivores than it did historically, today’s fragments and second growth are more impoverished than shown by comparisons with modern ‘control’ sites. Any goals for bird community recovery in Amazonian second growth should recognise that a modern bird community will inevitably differ from a baseline from > 35 years ago. Abundance patterns driven by landscape change may be the most conspicuous manifestation of human activity, but biodiversity declines in undisturbed forest represent hidden losses, possibly driven by climate change, that may be pervasive in intact Amazonian forests and other systems considered to be undisturbed.

Increasing temperature and productivity change biomass, trophic pyramids and community‐level omega‐3 fatty acid content in subarctic lake food webs - Ossi Keva; Sami J. Taipale; Brian Hayden; Stephen M. Thomas; Jussi Vesterinen; Paula Kankaala; Kimmo K. Kahilainen (Global Change Biology, 2021)
Climate change in the Arctic is outpacing the global average and land‐use is intensifying due to exploitation of previously inaccessible or unprofitable natural resources. A comprehensive understanding of how the joint effects of changing climate and productivity modify lake food web structure, biomass, trophic pyramid shape and abundance of physiologically essential biomolecules (omega‐3 fatty acids) in the biotic community is lacking. We conducted a space‐for‐time study in 20 subarctic lakes spanning a climatic (+3.2°C and precipitation: +30%) and chemical (dissolved organic carbon: +10 mg/L, total phosphorus: +45 µg/L and total nitrogen: +1,000 µg/L) gradient to test how temperature and productivity jointly affect the structure, biomass and community fatty acid content (eicosapentaenoic acid [EPA] and docosahexaenoic acid [DHA]) of whole food webs. Increasing temperature and productivity shifted lake communities towards dominance of warmer, murky‐water‐adapted taxa, with a general increase in the biomass of primary producers, and secondary and tertiary consumers, while primary invertebrate consumers did not show equally clear trends. This process altered various trophic pyramid structures towards an hour glass shape in the warmest and most productive lakes. Increasing temperature and productivity had negative fatty acid content trends (mg EPA + DHA/g dry weight) in primary producers and primary consumers, but not in secondary nor tertiary fish consumers. The massive biomass increment of fish led to increasing areal fatty acid content (kg EPA + DHA/ha) towards increasingly warmer, more productive lakes, but there were no significant trends in other trophic levels. Increasing temperature and productivity are shifting subarctic lake communities towards systems characterized by increasing dominance of cyanobacteria and cyprinid fish, although decreasing quality in terms of EPA + DHA content was observed only in phytoplankton, zooplankton and profundal benthos.

Hemolymph Proteomics and Gut Microbiota of Horseshoe Crabs Tachypleus tridentatus and Carcinoscorpius rotundicauda - Zhe Qu; Thomas C. N. Leung; Wenyan Nong; Ho Yin Yip; Ivy H. T. Lee; Siu Gin Cheung; Ngai Sai Ming; Wai Lok So; William G. Bendena; Stephen S. Tobe; Jerome H. L. Hui (Frontiers in Marine Science, 2020)
Horseshoe crabs are a group of marine chelicerates that contain only four extant species, some of which are endangered. Their hemolymph has been widely used in medical applications for endotoxin detection. Nevertheless, there is limited information on the profiles of their hemolymph proteins and their gut microbial diversity. In this study, we performed the first detailed investigation of the hemolymph proteomics and gut microbiota of two Asian horseshoe crabs Tachypleus tridentatus and Carcinoscorpius rotundicauda . Among the identified proteins being cataloged in the juvenile and adult hemolymph, unexpectedly, sesquiterpenoid signaling pathway proteins including Heat shock protein 83 (HSP83), Chd64, and a juvenile hormone binding protein (JHBP) were revealed. This provides evidence for the presence of functional sesquiterpenoid hormonal systems in these marine chelicerates. consumption of certain horseshoe crab species often leads to tetrodotoxin poisoning and the horseshoe crab is thought to possess a tetrodotoxin resistance mechanism. As such, sodium channels were analyzed and found to have critical amino acid residues that are similar to the toxin resistant pufferfish sodium channels. The source of the toxin is unknown so we investigated the gut microbiota, and found that Clostridium and Vibrio were the most dominant bacteria in T. tridentatus and C. rotundicauda , respectively. Together, this study provides a framework for further understanding of sesquiterpenoids and gut microbiota of these marine chelicerates.

Probing the effect of aroma compounds on the hydrodynamic properties of mucin glycoproteins - Vlad Dinu; Thomas MacCalman; Ni Yang; Gary G. Adams; Gleb E. Yakubov; Stephen E. Harding; Ian D. Fisk (European Biophysics Journal, 2020)
Aroma compounds are diverse low molecular weight organic molecules responsible for the flavour of food, medicines or cosmetics. Natural and artificial aroma compounds are manufactured and used by the industry to enhance the flavour and fragrance of products. While the low concentrations of aroma compounds present in food may leave no effect on the structural integrity of the mucosa, the effect of concentrated aroma volatiles is not well understood. At high concentrations, like those found in some flavoured products such as e-cigarettes, some aroma compounds are suggested to elicit a certain degree of change in the mucin glycoprotein network, depending on their functional group. These effects are particularly associated with carbonyl compounds such as aldehydes and ketones, but also phenols which may interact with mucin and other glycoproteins through other interaction mechanisms. This study demonstrates the formation of such interactions in vitro through the use of molecular hydrodynamics. Sedimentation velocity studies reveal that the strength of the carbonyl compound interaction is influenced by compound hydrophobicity, in which the more reactive short chain compounds show the largest increase in mucin-aroma sedimentation coefficients. By contrast, the presence of groups that increases the steric hindrance of the carbonyl group, such as ketones, produced a milder effect. The interaction effects were further demonstrated for hexanal using size exclusion chromatography light scattering (SEC-MALS) and intrinsic viscosity. In addition, phenolic aroma compounds were identified to reduce the sedimentation coefficient of mucin, which is consistent with interactions in the non-glycosylated mucin region.

Aminoethyl substitution enhances the self-assembly properties of an aminocellulose as a potential archaeological wood consolidant - Jennifer M. K. Wakefield; Robert Hampe; Richard B. Gillis; Agnes Sitterli; Gary G. Adams; Hartmut Kutzke; Thomas Heinze; Stephen E. Harding (European Biophysics Journal, 2020)
The 6-deoxy-6-aminocelluloses—or “aminocelluloses”—are a class of synthetic natural cellulose derivatives which are mostly aqueous soluble and have excellent film-forming properties. Recent studies have connected these properties at the molecular level with protein-like self-associative behaviour for a range of aminocelluloses including a 6-deoxy-6-(ω-aminoethyl) aminocellulose AEA-1 with the association being a two-stage process—a reversible oligomerisation followed by further (semi-reversible) aggregation into larger structures. Here, we synthesise and compare a new 6-deoxy-6-(ω-aminoethyl) aminocellulose AEA-1′ with different degree of substitution with one with further alkyl derivatisation, namely 6-deoxy-6-(ω-hydroxyethyl) aminocellulose HEA-1′. As with AEA-1, sedimentation velocity and sedimentation equilibrium in the analytical ultracentrifuge still show a two-stage process for both AEA-1′ and HEA-1′, with the latter giving higher molar masses. The consequences of these properties for use as consolidants for archaeological wood are considered.

Toward indicators of the performance of US infrastructures under climate change risks - Thomas J. Wilbanks; Rae Zimmerman; Susan Julius; Paul Kirshen; Joel B. Smith; Richard Moss; William Solecki; Matthias Ruth; Stephen Conrad; Steven J. Fernandez; Michael S. Matthews; Michael J. Savonis; et al. (Climatic Change, 2020)

Landslides across the USA: occurrence, susceptibility, and data limitations - Benjamin B. Mirus; Eric S. Jones; Rex L. Baum; Jonathan W. Godt; Stephen Slaughter; Matthew M. Crawford; Jeremy Lancaster; Thomas Stanley; Dalia B. Kirschbaum; William J. Burns; Robert G. Schmitt; Kassandra O. Lindsey; et al. (Landslides, 2020)
Detailed information about landslide occurrence is the foundation for advancing process understanding, susceptibility mapping, and risk reduction. Despite the recent revolution in digital elevation data and remote sensing technologies, landslide mapping remains resource intensive. Consequently, a modern, comprehensive map of landslide occurrence across the United States (USA) has not been compiled. As a first step toward this goal, we present a national-scale compilation of existing, publicly available landslide inventories. This geodatabase can be downloaded in its entirety or viewed through an online, searchable map, with parsimonious attributes and direct links to the contributing sources with additional details. The mapped spatial pattern and concentration of landslides are consistent with prior characterization of susceptibility within the conterminous USA, with some notable exceptions on the West Coast. Although the database is evolving and known to be incomplete in many regions, it confirms that landslides do occur across the country, thus highlighting the importance of our national-scale assessment. The map illustrates regions where high-quality mapping has occurred and, in contrast, where additional resources could improve confidence in landslide characterization. For example, borders between states and other jurisdictions are quite apparent, indicating the variation in approaches to data collection by different agencies and disparity between the resources dedicated to landslide characterization. Further investigations are needed to better assess susceptibility and to determine whether regions with high relief and steep topography, but without mapped landslides, require further landslide inventory mapping. Overall, this map provides a new resource for accessing information about known landslides across the USA.

Global ecosystems and fire: Multi‐model assessment of fire‐induced tree‐cover and carbon storage reduction - Gitta Lasslop; Stijn Hantson; Sandy P. Harrison; Dominique Bachelet; Chantelle Burton; Matthias Forkel; Matthew Forrest; Fang Li; Joe R. Melton; Chao Yue; Sally Archibald; Simon Scheiter; et al. (Global Change Biology, 2020)
In this study, we use simulations from seven global vegetation models to provide the first multi‐model estimate of fire impacts on global tree cover and the carbon cycle under current climate and anthropogenic land use conditions, averaged for the years 2001–2012. Fire globally reduces the tree covered area and vegetation carbon storage by 10%. Regionally, the effects are much stronger, up to 20% for certain latitudinal bands, and 17% in savanna regions. Global fire effects on total carbon storage and carbon turnover times are lower with the effect on gross primary productivity (GPP) close to 0. We find the strongest impacts of fire in savanna regions. Climatic conditions in regions with the highest burned area differ from regions with highest absolute fire impact, which are characterized by higher precipitation. Our estimates of fire‐induced vegetation change are lower than previous studies. We attribute these differences to different definitions of vegetation change and effects of anthropogenic land use, which were not considered in previous studies and decreases the impact of fire on tree cover. Accounting for fires significantly improves the spatial patterns of simulated tree cover, which demonstrates the need to represent fire in dynamic vegetation models. Based upon comparisons between models and observations, process understanding and representation in models, we assess a higher confidence in the fire impact on tree cover and vegetation carbon compared to GPP, total carbon storage and turnover times. We have higher confidence in the spatial patterns compared to the global totals of the simulated fire impact. As we used an ensemble of state‐of‐the‐art fire models, including effects of land use and the ensemble median or mean compares better to observational datasets than any individual model, we consider the here presented results to be the current best estimate of global fire effects on ecosystems.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Anaerobic microbial communities and their potential for bioenergy production in heavily biodegraded petroleum reservoirs - Júlia R. de Rezende; Thomas B. P. Oldenburg; Tetyana Korin; William D. L. Richardson; Milovan Fustic; Carolyn M. Aitken; Bernard F. J. Bowler; Angela Sherry; Alexander Grigoryan; Gerrit Voordouw; Stephen R. Larter; Ian M. Head; et al. (Environmental Microbiology, 2020)
Summary Most of the oil in low temperature, non‐uplifted reservoirs is biodegraded due to millions of years of microbial activity, including via methanogenesis from crude oil. To evaluate stimulating additional methanogenesis in already heavily biodegraded oil reservoirs, oil sands samples were amended with nutrients and electron acceptors, but oil sands bitumen was the only organic substrate. Methane production was monitored for over 3000 days. Methanogenesis was observed in duplicate microcosms that were unamended, amended with sulfate or that were initially oxic, however methanogenesis was not observed in nitrate‐amended controls. The highest rate of methane production was 0.15 μmol CH 4 g −1 oil d −1 , orders of magnitude lower than other reports of methanogenesis from lighter crude oils. Methanogenic Archaea and several potential syntrophic bacterial partners were detected following the incubations. GC–MS and FTICR–MS revealed no significant bitumen alteration for any specific compound or compound class, suggesting that the very slow methanogenesis observed was coupled to bitumen biodegradation in an unspecific manner. After 3000 days, methanogenic communities were amended with benzoate resulting in methanogenesis rates that were 110‐fold greater. This suggests that oil‐to‐methane conversion is limited by the recalcitrant nature of oil sands bitumen, not the microbial communities resident in heavy oil reservoirs.

Can we project changes in fish abundance and distribution in response to climate? - Jose A. Fernandes; Louise Rutterford; Stephen D. Simpson; Momme Butenschön; Thomas L. Frölicher; Andrew Yool; William W. L. Cheung; Alastair Grant (Global Change Biology, 2020)
Large‐scale and long‐term changes in fish abundance and distribution in response to climate change have been simulated using both statistical and process‐based models. However, national and regional fisheries management requires also shorter term projections on smaller spatial scales, and these need to be validated against fisheries data. A 26‐year time series of fish surveys with high spatial resolution in the North‐East Atlantic provides a unique opportunity to assess the ability of models to correctly simulate the changes in fish distribution and abundance that occurred in response to climate variability and change. We use a dynamic bioclimate envelope model forced by physical–biogeochemical output from eight ocean models to simulate changes in fish abundance and distribution at scales down to a spatial resolution of 0.5°. When comparing with these simulations with annual fish survey data, we found the largest differences at the 0.5° scale. Differences between fishery model runs driven by different biogeochemical models decrease dramatically when results are aggregated to larger scales (e.g. the whole North Sea), to total catches rather than individual species or when the ensemble mean instead of individual simulations are used. Recent improvements in the fidelity of biogeochemical models translate into lower error rates in the fisheries simulations. However, predictions based on different biogeochemical models are often more similar to each other than they are to the survey data, except for some pelagic species. We conclude that model results can be used to guide fisheries management at larger spatial scales, but more caution is needed at smaller scales.

Critical land change information enhances the understanding of carbon balance in the United States - Jinxun Liu; Benjamin M. Sleeter; Zhiliang Zhu; Thomas R. Loveland; Terry Sohl; Stephen M. Howard; Carl H. Key; Todd Hawbaker; Shuguang Liu; Bradley Reed; Mark A. Cochrane; Linda S. Heath; et al. (Global Change Biology, 2020)
Large‐scale terrestrial carbon (C) estimating studies using methods such as atmospheric inversion, biogeochemical modeling, and field inventories have produced different results. The goal of this study was to integrate fine‐scale processes including land use and land cover change into a large‐scale ecosystem framework. We analyzed the terrestrial C budget of the conterminous United States from 1971 to 2015 at 1‐km resolution using an enhanced dynamic global vegetation model and comprehensive land cover change data. Effects of atmospheric CO 2 fertilization, nitrogen deposition, climate, wildland fire, harvest, and land use/land cover change (LUCC) were considered. We estimate annual C losses from cropland harvest, forest clearcut and thinning, fire, and LUCC were 436.8, 117.9, 10.5, and 10.4 TgC/year, respectively. C stored in ecosystems increased from 119,494 to 127,157 TgC between 1971 and 2015, indicating a mean annual net C sink of 170.3 TgC/year. Although ecosystem net primary production increased by approximately 12.3 TgC/year, most of it was offset by increased C loss from harvest and natural disturbance and increased ecosystem respiration related to forest aging. As a result, the strength of the overall ecosystem C sink did not increase over time. Our modeled results indicate the conterminous US C sink was about 30% smaller than previous modeling studies, but converged more closely with inventory data.

Dynamics of a human‐modified tropical peat swamp forest revealed by repeat lidar surveys - Béatrice Wedeux; Michele Dalponte; Michael Schlund; Stephen Hagen; Mark Cochrane; Laura Graham; Aswin Usup; Andri Thomas; David Coomes (Global Change Biology, 2020)
Tropical peat swamp forests (PSFs) are globally important carbon stores under threat. In Southeast Asia, 35% of peatlands had been drained and converted to plantations by 2010, and much of the remaining forest had been logged, contributing significantly to global carbon emissions. Yet, tropical forests have the capacity to regain biomass quickly and forests on drained peatlands may grow faster in response to soil aeration, so the net effect of humans on forest biomass remains poorly understood. In this study, two lidar surveys (made in 2011 and 2014) are compared to map forest biomass dynamics across 96 km 2 of PSF in Kalimantan, Indonesia. The peatland is now legally protected for conservation, but large expanses were logged under concessions until 1998 and illegal logging continues in accessible portions. It was hypothesized that historically logged areas would be recovering biomass while recently logged areas would be losing biomass. We found that historically logged forests were recovering biomass near old canals and railways used by the concessions. Lidar detected substantial illegal logging activity—579 km of logging canals were located beneath the canopy. Some patches close to these canals have been logged in the 2011–2104 period (i.e. substantial biomass loss) but, on aggregate, these illegally logged regions were also recovering. Unexpectedly, rapid growth was also observed in intact forest that had not been logged and was over a kilometre from the nearest known canal, perhaps in response to greater aeration of surface peat. Comparing these results with flux measurements taken at other nearby sites, we find that carbon sequestration in above‐ground biomass may have offset roughly half the carbon efflux from peat oxidation. This study demonstrates the power of repeat lidar survey to map fine‐scale forest dynamics in remote areas, revealing previously unrecognized impacts of anthropogenic global change.

Oceanids C2: An Integrated Command, Control, and Data Infrastructure for the Over-the-Horizon Operation of Marine Autonomous Systems - Catherine A. Harris; Alvaro Lorenzo-Lopez; Owain Jones; Justin J. H. Buck; Alexandra Kokkinaki; Stephen Loch; Thomas Gardner; Alexander B. Phillips (Frontiers in Marine Science, 2020)

Predictors of Lesion Cavitation After Recent Small Subcortical Stroke - Thomas Gattringer; Maria Valdes Hernandez; Anna Heye; Paul A Armitage; Stephen Makin; Francesca Chappell; Daniela Pinter; Fergus Doubal; Christian Enzinger; Franz Fazekas; Joanna M. Wardlaw (Translational Stroke Research, 2020)
Morphologic evolution of recent small subcortical infarcts (RSSI) ranges from lesion disappearance to lacune formation and the reasons for this variability are still poorly understood. We hypothesized that diffusion tensor imaging (DTI) and blood-brain-barrier (BBB) abnormalities early on can predict tissue damage 1 year after an RSSI. We studied prospectively recruited patients with a symptomatic MRI-defined RSSI who underwent baseline and two pre-specified MRI examinations at 1–3-month and 1-year post-stroke. We defined the extent of long-term tissue destruction, termed cavitation index , as the ratio of the 1-year T1-weighted cavity volume to the baseline RSSI volume on FLAIR. We calculated fractional anisotropy and mean diffusivity (MD) of the RSSI and normal-appearing white matter, and BBB leakage in different tissues on dynamic contrast-enhanced MRI. Amongst 60 patients, at 1-year post-stroke, 44 patients showed some degree of RSSI cavitation on FLAIR, increasing to 50 on T2- and 56 on T1-weighted high-resolution scans, with a median cavitation index of 7% (range, 1–36%). Demographic, clinical, and cerebral small vessel disease features were not associated with the cavitation index. While lower baseline MD of the RSSI ( r s = − 0.371; p = 0.004) and more contrast leakage into CSF ( r s = 0.347; p = 0.007) were associated with the cavitation index in univariable analysis, only BBB leakage in CSF remained independently associated with cavitation (beta = 0.315, p = 0.046). Increased BBB leakage into CSF may indicate worse endothelial dysfunction and increased risk of tissue destruction post RSSI. Although cavitation was common, it only affected a small proportion of the original RSSI.

Site use and connectivity of female grey seals (Halichoerus grypus) around Wales - Izzy Langley; Tobias Rosas da Costa Oliver; Lex Hiby; Thomas B. Stringell; Ceri W. Morris; Oliver O’Cadhla; Lisa Morgan; Kate Lock; Sarah Perry; Stephen Westcott; Dave Boyle; Birgitta I. Büche; et al. (Marine Biology, 2020)
Grey seals ( Halichoerus grypus ) are a qualifying feature of three special areas of conservation (SACs) in Wales, yet relatively little is known of their site use along this coastline. Since 1992, many individuals and organisations have contributed to a grey seal photographic identification database held by Natural Resources Wales, which is one of the largest and oldest of its kind, providing key information from grey seal haul-out sites around the Celtic and Irish Seas. Here, we investigated spatial connectivity of haul-out sites and fidelity of adult females to breeding sites. The minimum number of adult female grey seals using the area between 1992 and 2016 was 2688. Individual capture histories and relative spatial transition probabilities ( P ij ) between pairs of location groups were calculated. Adjacent locations were highly connected (e.g. Lleyn Peninsula and Bardsey, P ij = 0.7) but connections spanned the entire region, up to 230 km apart (e.g. Skomer and Dee Estuary, P ij = 0.004). Resights were recorded within SACs (e.g. Lleyn Peninsula and Bardsey [Lleyn Peninsula and the Sarnau SAC], P ij = 0.7), between SACs (e.g. Bardsey and Skomer [Pembrokeshire Marine], P ij = 0.03), between SACs and non-designated areas (e.g. Skerries and Bardsey, P ij = 0.09) and between sites outside any protected area (e.g. Dee Estuary and Anglesey, P ij = 0.5). While inter-annual fidelity to breeding sites was high ( P ij = 0.82–1), individual female grey seals moved throughout the region. This evidence of extensive site use beyond protected areas is important for the management and conservation of grey seals around Wales.

The Ubiquitin System: a Regulatory Hub for Intellectual Disability and Autism Spectrum Disorder - Maria A. Kasherman; Susitha Premarathne; Thomas H. J. Burne; Stephen A. Wood; Michael Piper (Molecular Neurobiology, 2020)

Food and temperature stressors have opposing effects in determining flexible migration decisions in brown trout ( Salmo trutta ) - Louise C. Archer; Stephen A. Hutton; Luke Harman; Stephen D. McCormick; Michael N. O’Grady; Joseph P. Kerry; W. Russell Poole; Patrick Gargan; Philip McGinnity; Thomas E. Reed (Global Change Biology, 2020)
With rapid global change, organisms in natural systems are exposed to a multitude of stressors that likely co‐occur, with uncertain impacts. We explored individual and cumulative effects of co‐occurring environmental stressors on the striking, yet poorly understood, phenomenon of facultative migration. We reared offspring of a brown trout population that naturally demonstrates facultative anadromy (sea migration), under different environmental stressor treatments and measured life history responses in terms of migratory tactics and freshwater maturation rates. Juvenile fish were exposed to reduced food availability, temperatures elevated to 1.8°C above natural conditions or both treatments in combination over 18 months of experimental tank rearing. When considered in isolation, reduced food had negative effects on the size, mass and condition of fish across the experiment. We detected variable effects of warm temperatures (negative effects on size and mass, but positive effect on lipids). When combined with food restriction, temperature effects on these traits were less pronounced, implying antagonistic stressor effects on morphological traits. Stressors combined additively, but had opposing effects on life history tactics: migration increased and maturation rates decreased under low food conditions, whereas the opposite occurred in the warm temperature treatment. Not all fish had expressed maturation or migration tactics by the end of the study, and the frequency of these ‘unassigned’ fish was higher in food deprivation treatments, but lower in warm treatments. Fish showing migration tactics were smaller and in poorer condition than fish showing maturation tactics, but were similar in size to unassigned fish. We further detected effects of food restriction on hypo‐osmoregulatory function of migrants that may influence the fitness benefits of the migratory tactic at sea. We also highlight that responses to multiple stressors may vary depending on the response considered. Collectively, our results indicate contrasting effects of environmental stressors on life history trajectories in a facultatively migratory species.

Beyond Technical Fixes: climate solutions and the great derangement - Andrea Joslyn Nightingale; Siri Eriksen; Marcus Taylor; Timothy Forsyth; Mark Pelling; Andrew Newsham; Emily Boyd; Katrina Brown; Blane Harvey; Lindsey Jones; Rachel Bezner Kerr; Lyla Mehta; et al. (Climate and Development, 2020)

Dinoflagellate cyst biostratigraphy and palaeoecology of the early Paleogene Landana reference section, Cabinda Province, Angola - Thomas Steeman; Julie De Weirdt; Thierry Smith; Thierry De Putter; Florias Mees; Stephen Louwye (Palynology, 2020)

Mineral resources in life cycle impact assessment: part II – recommendations on application-dependent use of existing methods and on future method development needs - Markus Berger; Thomas Sonderegger; Rodrigo Alvarenga; Vanessa Bach; Alexander Cimprich; Jo Dewulf; Rolf Frischknecht; Jeroen Guinée; Christoph Helbig; Tom Huppertz; Olivier Jolliet; Masaharu Motoshita; et al. (The International Journal of Life Cycle Assessment, 2020)
Purpose Assessing impacts of abiotic resource use has been a topic of persistent debate among life cycle impact assessment (LCIA) method developers and a source of confusion for life cycle assessment (LCA) practitioners considering the different interpretations of the safeguard subject for mineral resources and the resulting variety of LCIA methods to choose from. Based on the review and assessment of 27 existing LCIA methods, accomplished in the first part of this paper series (Sonderegger et al. 2020), this paper provides recommendations regarding the application-dependent use of existing methods and areas for future method development. Method Within the “global guidance for LCIA indicators and methods” project of the Life Cycle Initiative hosted by UN Environment, 62 members of the “task force mineral resources” representing different stakeholders discussed the strengths and limitations of existing LCIA methods and developed initial conclusions. These were used by a subgroup of eight members at the Pellston Workshop® held in Valencia, Spain, to derive recommendations on the application-dependent use and future development of impact assessment methods. Results and discussion First, the safeguard subject for mineral resources within the area of protection (AoP) natural resources was defined. Subsequently, seven key questions regarding the consequences of mineral resource use were formulated, grouped into “inside-out” related questions (i.e., current resource use leading to changes in opportunities for future users to use resources) and “outside-in” related questions (i.e., potential restrictions of resource availability for current resource users). Existing LCIA methods were assigned to these questions, and seven methods (ADP ultimate reserves , SOP URR , LIME2 endpoint , CEENE, ADP economic reserves , ESSENZ, and GeoPolRisk) are recommended for use in current LCA studies at different levels of recommendation. All 27 identified LCIA methods were tested on an LCA case study of an electric vehicle, and yielded divergent results due to their modeling of impact mechanisms that address different questions related to mineral resource use. Besides method-specific recommendations, we recommend that all methods increase the number of minerals covered, regularly update their characterization factors, and consider the inclusion of secondary resources and anthropogenic stocks. Furthermore, the concept of dissipative resource use should be defined and integrated in future method developments. Conclusion In an international consensus-finding process, the current challenges of assessing impacts of resource use in LCA have been addressed by defining the safeguard subject for mineral resources, formulating key questions related to this safeguard subject, recommending existing LCIA methods in relation to these questions, and highlighting areas for future method development.

Mineral resources in life cycle impact assessment—part I: a critical review of existing methods - Thomas Sonderegger; Markus Berger; Rodrigo Alvarenga; Vanessa Bach; Alexander Cimprich; Jo Dewulf; Rolf Frischknecht; Jeroen Guinée; Christoph Helbig; Tom Huppertz; Olivier Jolliet; Masaharu Motoshita; et al. (The International Journal of Life Cycle Assessment, 2020)

Kelp Forest Restoration in Australia - Cayne Layton; Melinda A. Coleman; Ezequiel M. Marzinelli; Peter D. Steinberg; Stephen E. Swearer; Adriana Vergés; Thomas Wernberg; Craig R. Johnson (Frontiers in Marine Science, 2020)

Differential rearing alters taste reactivity to ethanol, sucrose, and quinine - Thomas J. Wukitsch; Emma C. Brase; Theodore J. Moser; Stephen W. Kiefer; Mary E. Cain (Psychopharmacology, 2020)

Development of a multi-assay approach for monitoring coral diversity using eDNA metabarcoding - Jason B. Alexander; Michael Bunce; Nicole White; Shaun P. Wilkinson; Arne A. S. Adam; Tina Berry; Michael Stat; Luke Thomas; Stephen J. Newman; Laurence Dugal; Zoe T. Richards (Coral Reefs, 2020)

Integrated Modeling to Evaluate Climate Change Impacts on Coupled Social-Ecological Systems in Alaska - Anne Babcock Hollowed; Kirstin Kari Holsman; Alan C. Haynie; Albert J. Hermann; Andre E. Punt; Kerim Aydin; James N. Ianelli; Stephen Kasperski; Wei Cheng; Amanda Faig; Kelly A. Kearney; Jonathan C. P. Reum; et al. (Frontiers in Marine Science, 2020)

Pediatric Bupropion Ingestions in Adolescents vs. Younger Children—a Tale of Two Populations - Steve Offerman; Michael Levine; Jasmin Gosen; Stephen H. Thomas (Journal of Medical Toxicology, 2020)

Electronic monitoring in fisheries: Lessons from global experiences and future opportunities - Aloysius T.M. van Helmond; Lars O. Mortensen; Kristian S. Plet‐Hansen; Clara Ulrich; Coby L. Needle; Daniel Oesterwind; Lotte Kindt‐Larsen; Thomas Catchpole; Stephen Mangi; Christopher Zimmermann; Hans Jakob Olesen; Nick Bailey; et al. (Fish and Fisheries, 2020)
Since the beginning of the 21st century, electronic monitoring (EM) has emerged as a cost‐efficient supplement to existing catch monitoring programmes in fisheries. An EM system consists of various activity sensors and cameras positioned on vessels to remotely record fishing activity and catches. The first objective of this review was to describe the state of play of EM in fisheries worldwide and to present the insights gained on this technology based on 100 EM trials and 12 fully implemented programmes. Despite its advantages, and its global use for monitoring, progresses in implementation in some important fishing regions are slow. Within this context, the second objective was to discuss more specifically the European experiences gained through 16 trials. Findings show that the three major benefits of EM were as follows: (a) cost‐efficiency, (b) the potential to provide more representative coverage of the fleet than any observer programme and (c) the enhanced registration of fishing activity and location. Electronic monitoring can incentivize better compliance and discard reduction, but the fishing managers and industry are often reluctant to its uptake. Improved understanding of the fisher's concerns, for example intrusion of privacy, liability and costs, and better exploration of EM benefits, for example increased traceability, sustainability claims and market access, may enhance implementation on a larger scale. In conclusion, EM as a monitoring tool embodies various solid strengths that are not diminished by its weaknesses. Electronic monitoring has the opportunity to be a powerful tool in the future monitoring of fisheries, particularly when integrated within existing monitoring programmes.

A conceptual framework for the identification and characterization of lacustrine spawning habitats for native lake charr Salvelinus namaycush - Stephen C. Riley; J. Ellen Marsden; Mark S. Ridgway; Christopher P. Konrad; Steven A. Farha; Thomas R. Binder; Trevor A. Middel; Peter C. Esselman; Charles C. Krueger (Environmental Biology of Fishes, 2019)

Transitioning the NASA SLR network to Event Timing Mode for reduced systematics, improved stability and data precision - Thomas Varghese; Randall L. Ricklefs; Erricos C. Pavlis; Magdalena Kuzmicz-Cieslak; Stephen M. Merkowitz (Journal of Geodesy, 2019)

Otolith Biochemistry—A Review - Oliver R. B. Thomas; Stephen E. Swearer (Reviews in Fisheries Science & Aquaculture, 2019)

Terrestrial Behavior in Titi Monkeys (Callicebus, Cheracebus, and Plecturocebus): Potential Correlates, Patterns, and Differences between Genera - João Pedro Souza-Alves; Italo Mourthe; Renato R. Hilário; Júlio César Bicca-Marques; Jennifer Rehg; Carla C. Gestich; Adriana C. Acero-Murcia; Patrice Adret; Rolando Aquino; Mélissa Berthet; Mark Bowler; Armando M. Calouro; et al. (International Journal of Primatology, 2019)

Precipitation and topography modulate vegetation greenness in the mountains of Baja California, México - Francisco José Del-Toro-Guerrero; Thomas Kretzschmar; Stephen H. Bullock (International Journal of Biometeorology, 2019)

Drought-Mediated Changes in Tree Physiological Processes Weaken Tree Defenses to Bark Beetle Attack - Thomas Kolb; Ken Keefover-Ring; Stephen J. Burr; Richard Hofstetter; Monica Gaylord; Kenneth F. Raffa (Journal of Chemical Ecology, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Autonomous Multi-Trophic Observations of Productivity and Export at the Australian Southern Ocean Time Series (SOTS) Reveal Sequential Mechanisms of Physical-Biological Coupling - Thomas W. Trull; Peter Jansen; Eric Schulz; Ben Weeding; Diana M. Davies; Stephen G. Bray (Frontiers in Marine Science, 2019)

A BGC-Argo Guide: Planning, Deployment, Data Handling and Usage - Henry C. Bittig; Tanya L. Maurer; Joshua N. Plant; Catherine Schmechtig; Annie P. S. Wong; Hervé Claustre; Thomas W. Trull; T. V. S. Udaya Bhaskar; Emmanuel Boss; Giorgio Dall’Olmo; Emanuele Organelli; Antoine Poteau; et al. (Frontiers in Marine Science, 2019)

Ocean Observations to Improve Our Understanding, Modeling, and Forecasting of Subseasonal-to-Seasonal Variability - Aneesh C. Subramanian; Magdalena A. Balmaseda; Luca Centurioni; Rajib Chattopadhyay; Bruce D. Cornuelle; Charlotte DeMott; Maria Flatau; Yosuke Fujii; Donata Giglio; Sarah T. Gille; Thomas M. Hamill; Harry Hendon; et al. (Frontiers in Marine Science, 2019)

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

On the Future of Argo: A Global, Full-Depth, Multi-Disciplinary Array - Dean Roemmich; Matthew H. Alford; Hervé Claustre; Kenneth Johnson; Brian King; James Moum; Peter Oke; W. Brechner Owens; Sylvie Pouliquen; Sarah Purkey; Megan Scanderbeg; Toshio Suga; et al. (Frontiers in Marine Science, 2019)

The use of a poster to reduce expectations to receive antibiotics for a common cold - Stephen R. Ritchie; Lizzie Rakhmanova; Eilish Out-O’Reilly; Stephen Reay; Mark G. Thomas; Laszlo Sajtos (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Four priorities for new links between conservation science and accounting research - Clément Feger; Laurent Mermet; Bhaskar Vira; Prue F.E. Addison; Richard Barker; Frank Birkin; John Burns; Stuart Cooper; Denis Couvet; Thomas Cuckston; Gretchen C. Daily; Colin Dey; et al. (Conservation Biology, 2019)
Article impact statement : New collaborations with accounting research can improve conservation impact of ecosystem‐based information systems.

Ocean Climate Observing Requirements in Support of Climate Research and Climate Information - Detlef Stammer; Annalisa Bracco; Krishna AchutaRao; Lisa Beal; Nathaniel L. Bindoff; Pascale Braconnot; Wenju Cai; Dake Chen; Matthew Collins; Gokhan Danabasoglu; Boris Dewitte; Riccardo Farneti; et al. (Frontiers in Marine Science, 2019)

Observational Needs for Improving Ocean and Coupled Reanalysis, S2S Prediction, and Decadal Prediction - Stephen G. Penny; Santha Akella; Magdalena A. Balmaseda; Philip Browne; James A. Carton; Matthieu Chevallier; Francois Counillon; Catia Domingues; Sergey Frolov; Patrick Heimbach; Patrick Hogan; Ibrahim Hoteit; et al. (Frontiers in Marine Science, 2019)

Correction to: Effects of combined escitalopram and aripiprazole in rats: role of the 5-HT1a receptor - Thomas Lapointe; Roger Hudson; Stephen Daniels; Brett Melanson; Yan Zhou; Francesco Leri (Psychopharmacology, 2019)

Effects of combined escitalopram and aripiprazole in rats: role of the 5-HT1a receptor - Thomas Lapointe; Roger Hudson; Stephen Daniels; Brett Melanson; Yan Zhou; Francesco Leri (Psychopharmacology, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Combined Effects of Hemlock Woolly Adelgid (Adelges tsugae) Infestation and Treatment with Imidacloprid on Eastern Hemlock (Tsuga canadensis) Leaf Radiometry - Heath W Garris; Thomas H Settle; Jonathan E Crossman; Stephen J Grider; Shawnté L Michaels (Journal of Forestry, 2019)
The neonicotinoid systemic insecticide imidacloprid has proven to be an effective treatment for the prevention and control of hemlock woolly adelgid (Adelges tsugae Annand) in southeastern populations of eastern hemlock (Tsuga canadensis L.). Recent studies have demonstrated that imidacloprid and A. tsugae both stimulate salicylic acid-dependent physiological responses in plant tissues responsible for plant defenses against pathogens, timing of developmental outcomes including flowering and leaf senescence, and resilience to abiotic stressors. We evaluated the interacting effects of A. tsugae presence/absence and treatment with imidacloprid on leaf optical properties indicative of photosynthetic potential, photosynthetic efficiency, and tissue senescence. Our results indicated that A. tsugae changes lower canopy leaf optical properties indicative of reduced photosynthetic potential/efficiency and accelerated senescence in mature leaves. Imidacloprid was associated with declines in photosynthetic potential and showed a largely similar, though less pronounced, effect on leaf spectral properties to that of A. tsugae.

Transcriptomic resilience, symbiont shuffling, and vulnerability to recurrent bleaching in reef‐building corals - Luke Thomas; Elora H. López; Megan K. Morikawa; Stephen R. Palumbi (Molecular Ecology, 2019)
As climate change progresses and extreme temperature events increase in frequency, rates of disturbance may soon outpace the capacity of certain species of reef‐building coral to recover from bleaching. This may lead to dramatic shifts in community composition and ecosystem function. Understanding variation in rates of bleaching recovery among species and how that translates to resilience to recurrent bleaching is fundamental to predicting the impacts of increasing disturbances on coral reefs globally. We tracked the response of two heat sensitive species in the genus Acropora to repeated bleaching events during the austral summers of 2015 and 2017. Despite a similar bleaching response, the species Acropora gemmifera recovered faster based on transcriptome‐wide gene expression patterns and had a more dynamic algal symbiont community than Acropora hyacinthus growing on the same reef. Moreover, A. gemmifera had higher survival to repeated heat extremes, with six‐fold lower mortality than A. hyacinthus . These patterns suggest that speed of recovery from a first round of bleaching, based on multiple mechanisms, contributes strongly to sensitivity to a second round of bleaching. Furthermore, our data uncovered intragenus variation in a group of corals thought generally to be heat‐sensitive and therefore paint a more nuanced view of the future health of coral reef ecosystems against a backdrop of increasing thermal disturbances.

A thermodynamic climatology of the disturbed stratospheric polar vortex - Thomas S. Ehrmann; Stephen J. Colucci (International Journal of Climatology, 2019)
A climatology of polar vortex disturbances in the Northern Hemisphere winter stratosphere is constructed from MERRA2 Reanalysis data for the winter seasons of 1981–2017. Sixty disturbances (splits or displacements) of the polar vortex are identified during the 37 winter seasons using geometric moments of stratospheric potential vorticity. The likelihood of a disturbed day is negatively correlated with the stratospheric quasi‐biennial oscillation (positively correlated with its easterly phase). It is also, surprisingly, negatively correlated with the presence of a stratospheric Aleutian anticyclone (the Aleutian high). The position of the polar vortex during each disturbance event is averaged to generate an area‐averaging filter that is applied to thermodynamic diagnostic quantities in the air column enclosed by the polar vortex. This diagnosis reveals that the location of the disturbed polar vortex experiences, on average, cooling driven by horizontal temperature advection in the lower and middle stratosphere prior to the onset of the disturbance, along with significant residual (likely adiabatic) cooling in the troposphere in the weeks surrounding the onset. How these thermodynamic signatures associated with a disturbed polar vortex relate to the Aleutian high and the quasi‐biennial oscillation is also explored.

Defining freshwater as a natural resource: a framework linking water use to the area of protection natural resources - Charlotte Pradinaud; Stephen Northey; Ben Amor; Jane Bare; Lorenzo Benini; Markus Berger; Anne-Marie Boulay; Guillaume Junqua; Michael J. Lathuillière; Manuele Margni; Masaharu Motoshita; Briana Niblick; et al. (The International Journal of Life Cycle Assessment, 2019)

Root density distribution and biomass allocation of co-occurring woody plants on contrasting soils in a subtropical savanna parkland - Yong Zhou; Stephen E. Watts; Thomas W. Boutton; Steven R. Archer (Plant and Soil, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Technological advances in maize breeding: past, present and future - Carson Andorf; William D. Beavis; Matthew Hufford; Stephen Smith; Walter P. Suza; Kan Wang; Margaret Woodhouse; Jianming Yu; Thomas Lübberstedt (Theoretical and Applied Genetics, 2019)

Genomic sequencing of a virus representing a novel type within the species Dyopipapillomavirus 1 in an Indian River Lagoon bottlenose dolphin - Galaxia Cortés-Hinojosa; Kuttichantran Subramaniam; James F. X. Wellehan; Terry Fei Fan Ng; Eric Delwart; Stephen D. McCulloch; Juli D. Goldstein; Adam M. Schaefer; Patricia A. Fair; John S. Reif; Gregory D. Bossart; Thomas B. Waltzek (Archives of Virology, 2019)

Development of a nonlinear hierarchical model to describe the disposition of deuterium in mother–infant pairs to assess exclusive breastfeeding practice - Zheng Liu; Aly Diana; Christine Slater; Thomas Preston; Rosalind S. Gibson; Lisa Houghton; Stephen B. Duffull (Journal of Pharmacokinetics and Pharmacodynamics, 2019)

Limited anti-HIV neutralizing antibody breadth and potency before and after HIV superinfection in Danish men who have sex with men - Andrew D. Redd; Marie Helleberg; Matthew Sievers; Stephen D. Schmidt; Nicole A. Doria-Rose; Daniel Bruno; Shelby Traeger; Craig Martens; Jannik Fonager; Gitte Kronborg; Zoe Packman; John R. Mascola; et al. (Infectious Diseases, 2019)

Draft genome sequence of the symbiotic Frankia sp. strain BMG5.30 isolated from root nodules of Coriaria myrtifolia in Tunisia - Abdellatif Gueddou; Erik Swanson; Karima Hezbri; Imen Nouioui; Amir Ktari; Stephen Simpson; Krystalynne Morris; W. Kelley Thomas; Faten Ghodhbane-Gtari; Maher Gtari; Louis S. Tisa (Antonie van Leeuwenhoek, 2019)

Genomic analysis of the mesophilic Thermotogae genus Mesotoga reveals phylogeographic structure and genomic determinants of its distinct metabolism - Camilla L. Nesbø; Rhianna Charchuk; Stephen M. J. Pollo; Karen Budwill; Ilya V. Kublanov; Thomas H. A. Haverkamp; Julia Foght (Environmental Microbiology, 2019)
Summary The genus Mesotoga , the only described mesophilic Thermotogae lineage, is common in mesothermic anaerobic hydrocarbon‐rich environments. Besides mesophily, Mesotoga displays lineage‐specific phenotypes, such as no or little H 2 production and dependence on sulfur‐compound reduction, which may influence its ecological role. We used comparative genomics of 18 Mesotoga strains (pairwise 16S rRNA identity >99%) and a transcriptome of M. prima to investigate how life at moderate temperatures affects phylogeography and to interrogate the genomic features of its lineage‐specific metabolism. We propose that Mesotoga accomplish H 2 oxidation and thiosulfate reduction using a sulfide dehydrogenase and a hydrogenase‐complex and that a pyruvate:ferredoxin oxidoreductase acquired from Clostridia is responsible for oxidizing acetate. Phylogenetic analysis revealed three distinct Mesotoga lineages (89.6%–99.9% average nucleotide identity [ANI] within lineages, 79.3%–87.6% ANI between lineages) having different geographic distribution patterns and high levels of intra‐lineage recombination but little geneflow between lineages. Including data from metagenomes, phylogeographic patterns suggest that geographical separation historically has been more important for Mesotoga than hyperthermophilic Thermotoga and we hypothesize that distribution of Mesotoga is constrained by their anaerobic lifestyle. Our data also suggest that recent anthropogenic activities and environments (e.g., wastewater treatment, oil exploration) have expanded Mesotoga habitats and dispersal capabilities.

The use of electronic monitoring within tuna longline fisheries: implications for international data collection, analysis and reporting - Timothy J. Emery; Rocio Noriega; Ashley J. Williams; James Larcombe; Simon Nicol; Peter Williams; Neville Smith; Graham Pilling; Malo Hosken; Stephen Brouwer; Laura Tremblay-Boyer; Thomas Peatman (Reviews in Fish Biology and Fisheries, 2018)

Meta-analysis identifies mitochondrial DNA sequence variants associated with walking speed - Todd M. Manini; Thomas W. Buford; John A. Kairalla; Mary M. McDermott; Carlos A. Vaz Fragoso; Roger A. Fielding; Fang-Chi Hsu; Neil Johannsen; Stephen Kritchevsky; Tamara B. Harris; Anne B. Newman; Steven R. Cummings; et al. (GeroScience, 2018)

Real-World Variability in the Prediction of Intracranial Aneurysm Wall Shear Stress: The 2015 International Aneurysm CFD Challenge - Kristian Valen-Sendstad; Aslak W. Bergersen; Yuji Shimogonya; Leonid Goubergrits; Jan Bruening; Jordi Pallares; Salvatore Cito; Senol Piskin; Kerem Pekkan; Arjan J. Geers; Ignacio Larrabide; Saikiran Rapaka; et al. (Cardiovascular Engineering and Technology, 2018)

Attraction and repulsion of mobile wild organisms to finfish and shellfish aquaculture: a review - Myriam D. Callier; Carrie J. Byron; David A. Bengtson; Peter J. Cranford; Stephen F. Cross; Ulfert Focken; Henrice M. Jansen; Pauline Kamermans; Anders Kiessling; Thomas Landry; Francis O'Beirn; Erik Petersson; et al. (Reviews in Aquaculture, 2018)
Knowledge of aquaculture–environment interactions is essential for the development of a sustainable aquaculture industry and efficient marine spatial planning. The effects of fish and shellfish farming on sessile wild populations, particularly infauna, have been studied intensively. Mobile fauna, including crustaceans, fish, birds and marine mammals, also interact with aquaculture operations, but the interactions are more complex and these animals may be attracted to (attraction) or show an aversion to (repulsion) farm operations with various degrees of effects. This review outlines the main mechanisms and effects of attraction and repulsion of wild animals to/from marine finfish cage and bivalve aquaculture, with a focus on effects on fisheries‐related species. Effects considered in this review include those related to the provision of physical structure (farm infrastructure acting as fish aggregating devices ( FAD s) or artificial reefs ( AR s), the provision of food (e.g. farmed animals, waste feed and faeces, fouling organisms associated with farm structures) and some farm activities (e.g. boating, cleaning). The reviews show that the distribution of mobile organisms associated with farming structures varies over various spatial (vertical and horizontal) and temporal scales (season, feeding time, day/night period). Attraction/repulsion mechanisms have a variety of direct and indirect effects on wild organisms at the level of individuals and populations and may have implication for the management of fisheries species and the ecosystem in the context of marine spatial planning. This review revealed considerable uncertainties regarding the long‐term and ecosystem‐wide consequences of these interactions. The use of modelling may help better understand consequences, but long‐term studies are necessary to better elucidate effects.

Genetic modifiers of radon-induced lung cancer risk: a genome-wide interaction study in former uranium miners - Albert Rosenberger; Rayjean J. Hung; David C. Christiani; Neil E. Caporaso; Geoffrey Liu; Stig E. Bojesen; Loic Le Marchand; Ch. A. Haiman; Demetrios Albanes; Melinda C. Aldrich; Adonina Tardon; G. Fernández-Tardón; et al. (International Archives of Occupational and Environmental Health, 2018)

Pragmatic criteria to define chronic pseudomonas aeruginosa infection among adults with cystic fibrosis - Zhe Hui Hoo; Elizabeth Coates; Chin Maguire; Hannah Cantrill; Nadia Shafi; Edward F. Nash; Angela McGowan; Stephen J. Bourke; William G. Flight; Thomas V. Daniels; Julia A. Nightingale; Mark I. Allenby; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Staphylococcus aureus colonisation and its relationship with skin and soft tissue infection in New Zealand children - Mark R. Hobbs; Cameron C. Grant; Mark G. Thomas; Sarah Berry; Susan M. B. Morton; Emma Marks; Stephen R. Ritchie (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Eutrophication erodes inter-basin variation in macrophytes and co-occurring invertebrates in a shallow lake: combining ecology and palaeoecology - Jorge Salgado; Carl D. Sayer; Stephen J. Brooks; Thomas A. Davidson; Beth Okamura (Journal of Paleolimnology, 2018)

Stability of MRI metrics in the advanced research core of the NCAA-DoD concussion assessment, research and education (CARE) consortium - Andrew S. Nencka; Timothy B. Meier; Yang Wang; L. Tugan Muftuler; Yu-Chien Wu; Andrew J. Saykin; Jaroslaw Harezlak; M. Alison Brooks; Christopher C. Giza; John Difiori; Kevin M. Guskiewicz; Jason P. Mihalik; et al. (Brain Imaging and Behavior, 2018)

The development and use of a spatially explicit model for river otters to evaluate environmental hazards: a case study on the Department of Energy’s Savannah River Site - Emily B. McCallen; Karen F. Gaines; James M. Novak; Leslie E. Ruyle; Warren L. Stephens; A. Lawrence Bryan; Susan A. Blas; Thomas L. Serfass (Environmental Monitoring and Assessment, 2018)

Racial differences in the relationship between tobacco, alcohol, and the risk of head and neck cancer: pooled analysis of US studies in the INHANCE Consortium - Kristin J. Voltzke; Yuan-Chin Amy Lee; Zuo-Feng Zhang; Jose P. Zevallos; Guo-Pei Yu; Deborah M. Winn; Thomas L. Vaughan; Erich M. Sturgis; Elaine Smith; Stephen M. Schwartz; Stimson Schantz; Joshua Muscat; et al. (Cancer Causes & Control, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Large uncertainty in carbon uptake potential of land‐based climate‐change mitigation efforts - Andreas Krause; Thomas A. M. Pugh; Anita D. Bayer; Wei Li; Felix Leung; Alberte Bondeau; Jonathan C. Doelman; Florian Humpenöder; Peter Anthoni; Benjamin L. Bodirsky; Philippe Ciais; Christoph Müller; et al. (Global Change Biology, 2018)
Most climate mitigation scenarios involve negative emissions, especially those that aim to limit global temperature increase to 2°C or less. However, the carbon uptake potential in land‐based climate change mitigation efforts is highly uncertain. Here, we address this uncertainty by using two land‐based mitigation scenarios from two land‐use models ( IMAGE and MA g PIE ) as input to four dynamic global vegetation models ( DGVM s; LPJ ‐ GUESS , ORCHIDEE , JULES , LPJ mL). Each of the four combinations of land‐use models and mitigation scenarios aimed for a cumulative carbon uptake of ~130 GtC by the end of the century, achieved either via the cultivation of bioenergy crops combined with carbon capture and storage ( BECCS ) or avoided deforestation and afforestation ( ADAFF ). Results suggest large uncertainty in simulated future land demand and carbon uptake rates, depending on the assumptions related to land use and land management in the models. Total cumulative carbon uptake in the DGVM s is highly variable across mitigation scenarios, ranging between 19 and 130 GtC by year 2099. Only one out of the 16 combinations of mitigation scenarios and DGVM s achieves an equivalent or higher carbon uptake than achieved in the land‐use models. The large differences in carbon uptake between the DGVM s and their discrepancy against the carbon uptake in IMAGE and MA g PIE are mainly due to different model assumptions regarding bioenergy crop yields and due to the simulation of soil carbon response to land‐use change. Differences between land‐use models and DGVM s regarding forest biomass and the rate of forest regrowth also have an impact, albeit smaller, on the results. Given the low confidence in simulated carbon uptake for a given land‐based mitigation scenario, and that negative emissions simulated by the DGVM s are typically lower than assumed in scenarios consistent with the 2°C target, relying on negative emissions to mitigate climate change is a highly uncertain strategy.

Progress in designing and delivering effective fishing industry–science data collection in the UK - Stephen C Mangi; Sven Kupschus; Steven Mackinson; Dale Rodmell; Alexandra Lee; Elizabeth Bourke; Tom Rossiter; Jim Masters; Stuart Hetherington; Thomas Catchpole; David Righton (Fish and Fisheries, 2018)
This study was undertaken to address the increasing need for a strategic approach to industry–science data collections in the face of reducing resources and growing need for evidence in fisheries management. The aim was to evaluate progress in the development of plans and procedures that can be employed to collect, record and use fishing industry knowledge and data in the evidence base for managing fisheries. This was achieved by reviewing industry‐led data initiatives already undertaken or ongoing within the United Kingdom to document how these projects have/are incorporating fishing industry data into the process of management decision‐making; canvassing stakeholder opinion on data gaps and whether these could be filled by data gathered by commercial fishing vessels; establishing what issues might prevent or stimulate commercial fishing vessels in collecting data when they have the opportunity; and describing guidance on a step‐by‐step process for gathering scientific information such that fishers are empowered to collect the right data, at the right times and in the right format for their fishery. Given recent advances in the collection, interpretation and application of fisheries‐dependent data, we compare progress made in the UK to other areas of the world. We conclude that there is considerable evidence of a paradigm shift from the conventional practice of scientists asking fishers to provide data for scientific analyses towards full engagement of key stakeholders in data collection.

Woody plants optimise stomatal behaviour relative to hydraulic risk - William R. L. Anderegg; Adam Wolf; Adriana Arango‐Velez; Brendan Choat; Daniel J. Chmura; Steven Jansen; Thomas Kolb; Shan Li; Frederick C. Meinzer; Pilar Pita; Víctor Resco de Dios; John S. Sperry; et al. (Ecology Letters, 2018)
Stomatal response to environmental conditions forms the backbone of all ecosystem and carbon cycle models, but is largely based on empirical relationships. Evolutionary theories of stomatal behaviour are critical for guarding against prediction errors of empirical models under future climates. Longstanding theory holds that stomata maximise fitness by acting to maintain constant marginal water use efficiency over a given time horizon, but a recent evolutionary theory proposes that stomata instead maximise carbon gain minus carbon costs/risk of hydraulic damage. Using data from 34 species that span global forest biomes, we find that the recent carbon‐maximisation optimisation theory is widely supported, revealing that the evolution of stomatal regulation has not been primarily driven by attainment of constant marginal water use efficiency. Optimal control of stomata to manage hydraulic risk is likely to have significant consequences for ecosystem fluxes during drought, which is critical given projected intensification of the global hydrological cycle.

Brood Production by Xyleborus glabratus in Bolts from Trees Infected and Uninfect ed with the Laurel Wilt Pathogen, Raffaelea lauricola - Stephen W Fraedrich; Thomas C Harrington; Qiong Huang; Stanley J Zarnoch; James L Hanula; Glenda Susan Best (Forest Science, 2018)

The determination of monomers and oligomers from polyester-based can coatings into foodstuffs over extended storage periods - Malcolm Driffield; Monica Garcia-Lopez; Julie Christy; Antony Stephen Lloyd; Jonathan Andrew Tarbin; Patrick Hough; Emma Louise Bradley; Peter Kenneth Thomas Oldring (Food Additives & Contaminants: Part A, 2018)

A Digital Endocranial Cast of the Early Paleocene (Puercan) ‘Archaic’ Mammal Onychodectes tisonensis (Eutheria: Taeniodonta) - James G. Napoli; Thomas E. Williamson; Sarah L. Shelley; Stephen L. Brusatte (Journal of Mammalian Evolution, 2018)

The early inflorescence of Arabidopsis thaliana demonstrates positional effects in floral organ growth and meristem patterning - Andrew R. G. Plackett; Stephen J. Powers; Andy L. Phillips; Zoe A. Wilson; Peter Hedden; Stephen G. Thomas (Plant Reproduction, 2018)

Evidence of repeated long-distance movements by lake charr Salvelinus namaycush in Lake Huron - Stephen C. Riley; Thomas R. Binder; Taaja R. Tucker; Charles C. Krueger (Environmental Biology of Fishes, 2018)

Performance of the Population Bioequivalence (PBE) Statistical Test Using an IPAC-RS Database of Delivered Dose from Metered Dose Inhalers - Beth Morgan; Stephanie Chen; David Christopher; Göran Långström; Christopher Wiggenhorn; Elise Burmeister Getz; Hayden Beresford; Thomas Hoffelder; Daniela Acerbi; Stephen Andrews; Mark Berry; Monisha Dey; et al. (AAPS PharmSciTech, 2018)

Clarifying the key biodiversity areas partnership and programme - Simon N. Stuart; Thomas M. Brooks; Stuart H. M. Butchart; Wendy Elliott; Melanie Heath; Dieter Hoffmann; Leslie Honey; Irina Kostadinova; Penny Langhammer; Olivier Langrand; Susan Lieberman; Daniel Marnewick; et al. (Biodiversity and Conservation, 2018)

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Mechanisms of Thermal Tolerance in Reef-Building Corals across a Fine-Grained Environmental Mosaic: Lessons from Ofu, American Samoa - Luke Thomas; Noah H. Rose; Rachael A. Bay; Elora H. López; Megan K. Morikawa; Lupita Ruiz-Jones; Stephen R. Palumbi (Frontiers in Marine Science, 2018)

The century experiment: the first twenty years of UC Davis' Mediterranean agroecological experiment - Kristina M. Wolf; Emma E. Torbert; Dennis Bryant; Martin Burger; R. Ford Denison; Israel Herrera; Jan Hopmans; Will Horwath; Stephen Kaffka; Angela Y. Y. Kong; R. F. Norris; Johan Six; et al. (Ecology, 2018)
The Century Experiment at the Russell Ranch Sustainable Agriculture Facility at the University of California, Davis provides long‐term agroecological data from row crop systems in California's Central Valley starting in 1993. The Century Experiment was initially designed to study the effects of a gradient of water and nitrogen availability on soil properties and crop performance in ten different cropping systems to measure tradeoffs and synergies between agricultural productivity and sustainability. Currently systems include 11 different cropping systems–consisting of four different crops and a cover crop mixture–and one native grass system. This paper describes the long‐term core data from the Century Experiment from 1993–2014, including crop yields and biomass, crop elemental contents, aerial‐photo‐based Normalized Difference Vegetation Index data, soil properties, weather, chemical constituents in irrigation water, winter weed populations, and operational data including fertilizer and pesticide application amounts and dates, planting dates, planting quantity and crop variety, and harvest dates. This data set represents the only known long‐term set of data characterizing food production and sustainability in irrigated and rainfed Mediterranean annual cropping systems. There are no copyright restrictions associated with the use of this dataset.

Genome-Wide Association Analysis of the Sense of Smell in U.S. Older Adults: Identification of Novel Risk Loci in African-Americans and European-Americans - Jing Dong; Annah Wyss; Jingyun Yang; T. Ryan Price; Aude Nicolas; Michael Nalls; Greg Tranah; Nora Franceschini; Zongli Xu; Claudia Schulte; Alvaro Alonso; Steven R. Cummings; et al. (Molecular Neurobiology, 2017)

Relationships of depressive behavior and sertraline treatment with walking speed and activity in older female nonhuman primates - Jamie N. Justice; Marnie G. Silverstein-Metzler; Beth Uberseder; Susan E. Appt; Thomas B. Clarkson; Thomas C. Register; Stephen B. Kritchevsky; Carol A. Shively (GeroScience, 2017)

Ecological regime shift drives declining growth rates of sea turtles throughout the West Atlantic - Karen A. Bjorndal; Alan B. Bolten; Milani Chaloupka; Vincent S. Saba; Cláudio Bellini; Maria A. G. Marcovaldi; Armando J. B. Santos; Luis Felipe Wurdig Bortolon; Anne B. Meylan; Peter A. Meylan; Jennifer Gray; Robert Hardy; et al. (Global Change Biology, 2017)
Somatic growth is an integrated, individual‐based response to environmental conditions, especially in ectotherms. Growth dynamics of large, mobile animals are particularly useful as bio‐indicators of environmental change at regional scales. We assembled growth rate data from throughout the West Atlantic for green turtles, Chelonia mydas , which are long‐lived, highly migratory, primarily herbivorous mega‐consumers that may migrate over hundreds to thousands of kilometers. Our dataset, the largest ever compiled for sea turtles, has 9690 growth increments from 30 sites from Bermuda to Uruguay from 1973 to 2015. Using generalized additive mixed models, we evaluated covariates that could affect growth rates; body size, diet, and year have significant effects on growth. Growth increases in early years until 1999, then declines by 26% to 2015. The temporal (year) effect is of particular interest because two carnivorous species of sea turtles—hawksbills, Eretmochelys imbricata, and loggerheads, Caretta caretta —exhibited similar significant declines in growth rates starting in 1997 in the West Atlantic, based on previous studies. These synchronous declines in productivity among three sea turtle species across a trophic spectrum provide strong evidence that an ecological regime shift ( ERS ) in the Atlantic is driving growth dynamics. The ERS resulted from a synergy of the 1997/1998 El Niño Southern Oscillation ( ENSO )—the strongest on record—combined with an unprecedented warming rate over the last two to three decades. Further support is provided by the strong correlations between annualized mean growth rates of green turtles and both sea surface temperatures ( SST ) in the West Atlantic for years of declining growth rates ( r = −.94) and the Multivariate ENSO Index ( MEI ) for all years ( r = .74). Granger‐causality analysis also supports the latter finding. We discuss multiple stressors that could reinforce and prolong the effect of the ERS . This study demonstrates the importance of region‐wide collaborations.

Variability of in situ sediment strength and pore pressure behavior of tidal estuary surface sediments - Greg Lucking; Nina Stark; Thomas Lippmann; Stephen Smyth (Geo-Marine Letters, 2017)

A measurement system for vertical seawater profiles close to the air–sea interface - Richard P. Sims; Ute Schuster; Andrew J. Watson; Ming Xi Yang; Frances E. Hopkins; John Stephens; Thomas G. Bell (Ocean Science, 2017)
This paper describes a near-surface ocean profiler, which has been designed to precisely measure vertical gradients in the top 10 m of the ocean. Variations in the depth of seawater collection are minimized when using the profiler compared to conventional CTD/rosette deployments. The profiler consists of a remotely operated winch mounted on a tethered yet free-floating buoy, which is used to raise and lower a small frame housing sensors and inlet tubing. Seawater at the inlet depth is pumped back to the ship for analysis. The profiler can be used to make continuous vertical profiles or to target a series of discrete depths. The profiler has been successfully deployed during wind speeds up to 10 m s−1 and significant wave heights up to 2 m. We demonstrate the potential of the profiler by presenting measured vertical profiles of the trace gases carbon dioxide and dimethylsulfide. Trace gas measurements use an efficient microporous membrane equilibrator to minimize the system response time. The example profiles show vertical gradients in the upper 5 m for temperature, carbon dioxide and dimethylsulfide of 0.15 °C, 4 µatm and 0.4 nM respectively.

Systemic Inflammation during the First Postnatal Month and the Risk of Attention Deficit Hyperactivity Disorder Characteristics among 10 year-old Children Born Extremely Preterm - Elizabeth N. Allred; Olaf Dammann; Raina N. Fichorova; Stephen R Hooper; Scott J Hunter; Robert M. Joseph; Karl Kuban; Alan Leviton; Thomas Michael O’Shea; Megan N. Scott (Journal of Neuroimmune Pharmacology, 2017)

A Review of the Tools Used for Marine Monitoring in the UK: Combining Historic and Contemporary Methods with Modeling and Socioeconomics to Fulfill Legislative Needs and Scientific Ambitions - Tim P. Bean; Naomi Greenwood; Rachel Beckett; Lauren Biermann; John P. Bignell; Jan L. Brant; Gordon H. Copp; Michelle J. Devlin; Stephen Dye; Stephen W. Feist; Liam Fernand; Dean Foden; et al. (Frontiers in Marine Science, 2017)

A primer on systematic reviews in toxicology - Sebastian Hoffmann; Rob B. M. de Vries; Martin L. Stephens; Nancy B. Beck; Hubert A. A. M. Dirven; John R. Fowle; Julie E. Goodman; Thomas Hartung; Ian Kimber; Manoj M. Lalu; Kristina Thayer; Paul Whaley; et al. (Archives of Toxicology, 2017)

The effects of experimental whole-lake mixing on horizontal spatial patterns of fish and Zooplankton - Heald Emily; Thomas R. Hrabik; Yang Li; Zach J. Lawson; Stephen R. Carpenter; M. Jake Vander Zanden (Aquatic Sciences, 2017)

Diversification of deermice (Rodentia: genus Peromyscus ) at their north‐western range limit: genetic consequences of refugial and island isolation - Yadéeh E. Sawyer; Melanie J. Flamme; Thomas S. Jung; Stephen O. MacDonald; Joseph A. Cook (Journal of Biogeography, 2017)
Aim We surveyed the genetic variability of deermice (genus Peromyscus ) at the north‐western edge of their range to test for occupancy in multiple, hypothesized ice‐free regions during the late Pleistocene and explore post‐glacial dynamics. Location North‐western North America. Methods We used sequences from four independent nuclear and mitochondrial loci from 341 specimens of Peromyscus maniculatus, Peromyscus keeni and Peromyscus sp. (Yukon) to assess species limits, population structure, and demographical change as a result of historical climate change, using a Bayesian approach. Species distribution models were built in MaxEnt to explore the niche overlap amongst genetically distinct species. Results Divergence amongst three lineages began before the last interglacial, and each shows signs of post‐glacial expansion. Multilocus species trees strongly support P. keeni and Peromyscus sp. (Yukon) as independent from P. maniculatus . Substantial substructure was observed for P. keeni across the fragmented Alexander Archipelago. Northern lineages or clades ( Peromyscus sp. and P. keeni ) differed in potential ecological distributions. Main conclusions At the extreme north‐western range of deermice in North America, three distinct lineages persist reflecting divergence in at least three ice‐free regions [Beringia, Coastal (near Southeast Alaska) and Southern Continental] throughout the latest Pleistocene glacial cycles. Although spatially proximate in Yukon, no locations were identified where these lineages are in contact. Further, west along the Pacific Coast, P. keeni is widespread across the complex landscape of Southeast Alaska, yet there is limited contemporary gene flow amongst island populations, a finding consistent with the barriers produced by rising sea levels at the end of the Last Glacial Maximum.

Does milk intake promote prostate cancer initiation or progression via effects on insulin-like growth factors (IGFs)? A systematic review and meta-analysis - Sean Harrison; Rosie Lennon; Jeff Holly; Julian P. T. Higgins; Mike Gardner; Claire Perks; Tom Gaunt; Vanessa Tan; Cath Borwick; Pauline Emmet; Mona Jeffreys; Kate Northstone; et al. (Cancer Causes & Control, 2017)

Cognitive reserve moderates the relationship between neuropsychological performance and white matter fiber bundle length in healthy older adults - Laurie M. Baker; David H. Laidlaw; Ryan Cabeen; Erbil Akbudak; Thomas E. Conturo; Stephen Correia; David F. Tate; Jodi M. Heaps-Woodruff; Matthew R. Brier; Jacob Bolzenius; Lauren E. Salminen; Elizabeth M. Lane; et al. (Brain Imaging and Behavior, 2017)

Autonomous Multi-Platform Observations During the Salinity Processes in the Upper-ocean Regional Study - Eric Lindstrom; Andrey Shcherbina; Luc Rainville; Thomas Farrar; Luca Centurioni; Shenfu Dong; Eric D’Asaro; Charles Eriksen; David Fratantoni; Benjamin Hodges; Verena Hormann; William Kessler; et al. (Oceanography, 2017)

Endolithic microbial diversity in sandstone and granite from the McMurdo Dry Valleys, Antarctica - Stephen D. J. Archer; Asuncion de los Ríos; Kevin C. Lee; Thomas S. Niederberger; S. Craig Cary; Kathryn J. Coyne; Susanne Douglas; Donnabella C. Lacap-Bugler; Stephen B. Pointing (Polar Biology, 2017)

Blueprints of Effective Biodiversity and Conservation Knowledge Products That Support Marine Policy - Lauren V. Weatherdon; Ward Appeltans; Nadine Bowles-Newark; Thomas M. Brooks; Frances E. Davis; Katherine Despot-Belmonte; Stephen Fletcher; Cristina Garilao; Craig Hilton-Taylor; Tim Hirsch; Diego Juffe-Bignoli; Kristin Kaschner; et al. (Frontiers in Marine Science, 2017)

Projected 21st century changes in tornado exposure, risk, and disaster potential - Stephen M. Strader; Walker S. Ashley; Thomas J. Pingel; Andrew J. Krmenec (Climatic Change, 2017)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Islands in the ice stream: were spawning habitats for native salmonids in the Great Lakes created by paleo‐ice streams? - Stephen C Riley; Thomas R Binder; Taaja R Tucker; John Menzies; Nick Eyles; John Janssen; Andrew M Muir; Peter C Esselman; Nigel J Wattrus; Charles C Krueger (Fish and Fisheries, 2017)
Lake trout Salvelinus namaycush , lake whitefish Coregonus clupeaformis and cisco Coregonus artedi are salmonid fishes native to the Laurentian Great Lakes that spawn on rocky substrates in the fall and early winter. After comparing the locations of spawning habitat for these species in the main basin of Lake Huron with surficial substrates and the hypothesized locations of fast‐flowing Late Wisconsinan paleo‐ice streams, we hypothesize that much of the spawning habitat for these species in Lake Huron is the result of deposition and erosion by paleo‐ice streams. This hypothesis may represent a new framework for the identification and protection of spawning habitat for these native species, some of which are currently rare or extirpated in some of the Great Lakes. We further suggest that paleo‐ice streams may have been responsible for the creation of native salmonid spawning habitat elsewhere in the Great Lakes and in other glaciated landscapes.

Hybrid plants preserve unique genetic variation in the St Helena endemic trees Commidendrum rotundifolium DC Roxb. and C. spurium (G.Forst.) DC - Alan Gray; Annika Perry; Stephen Cavers; Antonia Eastwood; Michelle Biermann; Andrew Darlow; Vanessa Thomas; Phil Lambdon (Conservation Genetics, 2017)

Ontogenetic changes in sensitivity to nutrient limitation of tadpole growth - Jeffrey P. Stephens; Aaron B. Stoler; Jason P. Sckrabulis; Aaron J. Fetzer; Keith A. Berven; Scott D. Tiegs; Thomas R. Raffel (Oecologia, 2017)

The colorimetric determination of selectively cleaved adenosines and guanosines in DNA oligomers using bicinchoninic acid and copper - Elizabeth M. Thomas; Stephen M. Testa (JBIC Journal of Biological Inorganic Chemistry, 2017)

Observations of a New Zealand dolphin ( Cephalorhynchus hectori ) breathing via its mouth - Stephen M. Dawson; R. Ewan Fordyce; Sam H. Ridgway; Thomas E. Brough; Elisabeth Slooten (Marine Mammal Science, 2017)

Genetically informed ecological niche models improve climate change predictions - Dana H. Ikeda; Tamara L. Max; Gerard J. Allan; Matthew K. Lau; Stephen M. Shuster; Thomas G. Whitham (Global Change Biology, 2017)
We examined the hypothesis that ecological niche models ( ENM s) more accurately predict species distributions when they incorporate information on population genetic structure, and concomitantly, local adaptation. Local adaptation is common in species that span a range of environmental gradients (e.g., soils and climate). Moreover, common garden studies have demonstrated a covariance between neutral markers and functional traits associated with a species’ ability to adapt to environmental change. We therefore predicted that genetically distinct populations would respond differently to climate change, resulting in predicted distributions with little overlap. To test whether genetic information improves our ability to predict a species’ niche space, we created genetically informed ecological niche models ( gENM s) using Populus fremontii (Salicaceae), a widespread tree species in which prior common garden experiments demonstrate strong evidence for local adaptation. Four major findings emerged: (i) gENM s predicted population occurrences with up to 12‐fold greater accuracy than models without genetic information; (ii) tests of niche similarity revealed that three ecotypes, identified on the basis of neutral genetic markers and locally adapted populations, are associated with differences in climate; (iii) our forecasts indicate that ongoing climate change will likely shift these ecotypes further apart in geographic space, resulting in greater niche divergence; (iv) ecotypes that currently exhibit the largest geographic distribution and niche breadth appear to be buffered the most from climate change. As diverse agents of selection shape genetic variability and structure within species, we argue that gENM s will lead to more accurate predictions of species distributions under climate change.

Aquatic food security: insights into challenges and solutions from an analysis of interactions between fisheries, aquaculture, food safety, human health, fish and human welfare, economy and environment - Simon Jennings; Grant D Stentiford; Ana M Leocadio; Keith R Jeffery; Julian D Metcalfe; Ioanna Katsiadaki; Neil A Auchterlonie; Stephen C Mangi; John K Pinnegar; Tim Ellis; Edmund J Peeler; Tiziana Luisetti; et al. (Fish and Fisheries, 2016)
Fisheries and aquaculture production, imports, exports and equitability of distribution determine the supply of aquatic food to people. Aquatic food security is achieved when a food supply is sufficient, safe, sustainable, shockproof and sound: sufficient, to meet needs and preferences of people; safe, to provide nutritional benefit while posing minimal health risks; sustainable, to provide food now and for future generations; shock‐proof, to provide resilience to shocks in production systems and supply chains; and sound, to meet legal and ethical standards for welfare of animals, people and environment. Here, we present an integrated assessment of these elements of the aquatic food system in the United Kingdom, a system linked to dynamic global networks of producers, processors and markets. Our assessment addresses sufficiency of supply from aquaculture, fisheries and trade; safety of supply given biological, chemical and radiation hazards; social, economic and environmental sustainability of production systems and supply chains; system resilience to social, economic and environmental shocks; welfare of fish, people and environment; and the authenticity of food. Conventionally, these aspects of the food system are not assessed collectively, so information supporting our assessment is widely dispersed. Our assessment reveals trade‐offs and challenges in the food system that are easily overlooked in sectoral analyses of fisheries, aquaculture, health, medicine, human and fish welfare, safety and environment. We highlight potential benefits of an integrated, systematic and ongoing process to assess security of the aquatic food system and to predict impacts of social, economic and environmental change on food supply and demand.

Enhancing conservation of A ustralian freshwater ecosystems: identification of freshwater flagship fishes and relevant target audiences - Brendan C Ebner; David L Morgan; Adam Kerezsy; Scott Hardie; Stephen J Beatty; Jamie E Seymour; James A Donaldson; Simon Linke; Stirling Peverell; David Roberts; Thomas Espinoza; Nadine Marshall; et al. (Fish and Fisheries, 2016)
Flagship species, especially mammals and birds, are commonly used to increase awareness of conservation issues in marine and terrestrial ecosystems. However, flagship species oriented programs are often ad hoc with initiatives scarce in the freshwater context. Here, we aim to identify potential flagship candidates that would appeal to a broad cross section of society at a continental scale where freshwater ecosystems are under threat from human impacts. We identified 19 species from a list of 299 Australian freshwater fishes on the basis of body size, trophic guild and threatened species status assuming these characteristics of flagship species are transferable from previous work on terrestrial flagship species. We considered the potential of species to be of international appeal but focused mostly on eight relevant interest groups within Australia. This followed the rationale that public engagement with conservation issues in freshwater systems might be more effective if the link between fish species and the decisions people make were better understood, and we acknowledge the diverging interests of stakeholders. This scoping work contributes towards addressing the challenges of connecting societies to the principles of sharing water resources with ecosystems, and represents the first continental‐scale assessment of its kind.

The Dual Role of Lipids of the Lipoproteins in Trumenba, a Self-Adjuvanting Vaccine Against Meningococcal Meningitis B Disease - Yin Luo; Olga V. Friese; Herbert A. Runnels; Lakshmi Khandke; Gary Zlotnick; Ann Aulabaugh; Thomas Gore; Eugene Vidunas; Stephen W. Raso; Elena Novikova; Emilia Byrne; Michael Schlittler; et al. (The AAPS Journal, 2016)

Erratum to: Use of Modeling and Simulation Tools for Understanding the Impact of Formulation on the Absorption of a Low Solubility Compound: Ciprofloxacin - Marilyn Martinez; Bipin Mistry; Viera Lukacova; James E. Polli; Stephen W. Hoag; Thomas Dowling; Ravikanth Kona; Raafat Fahmy (The AAPS Journal, 2016)

IgE and mast cells in host defense against parasites and venoms - Kaori Mukai; Mindy Tsai; Philipp Starkl; Thomas Marichal; Stephen J. Galli (Seminars in Immunopathology, 2016)

A short-term decrease in household income inequality in the Sundarbans, Bangladesh, following Cyclone Aila - Abu Nasar Mohammad Abdullah; Kerstin Katharina Zander; Bronwyn Myers; Natasha Stacey; Stephen Thomas Garnett (Natural Hazards, 2016)

Genome-wide association of familial prostate cancer cases identifies evidence for a rare segregating haplotype at 8q24.21 - Craig C. Teerlink; Daniel Leongamornlert; Tokhir Dadaev; Alun Thomas; James Farnham; Robert A. Stephenson; Shaun Riska; Shannon K. McDonnell; Daniel J. Schaid; William J. Catalona; S. Lilly Zheng; Kathleen A. Cooney; et al. (Human Genetics, 2016)

Indices based on silicoflagellate assemblages offer potential for paleo-reconstructions of the main oceanographic zones of the Southern Ocean - Andrés S. Rigual-Hernández; Thomas W. Trull; Kevin McCartney; Anne-Marie Ballegeer; Kelly-Anne Lawler; Stephen G. Bray; Leanne K. Armand (Geo-Marine Letters, 2016)

Use of Modeling and Simulation Tools for Understanding the Impact of Formulation on the Absorption of a Low Solubility Compound: Ciprofloxacin - Marilyn Martinez; Bipin Mistry; Viera Lukacova; Jim Polli; Stephen Hoag; Thomas Dowling; Ravikanth Kona; Raafat Fahmy (The AAPS Journal, 2016)

A trait‐based approach for predicting species responses to environmental change from sparse data: how well might terrestrial mammals track climate change? - Luca Santini; Thomas Cornulier; James M. Bullock; Stephen C. F. Palmer; Steven M. White; Jenny A. Hodgson; Greta Bocedi; Justin M. J. Travis (Global Change Biology, 2016)
Estimating population spread rates across multiple species is vital for projecting biodiversity responses to climate change. A major challenge is to parameterise spread models for many species. We introduce an approach that addresses this challenge, coupling a trait‐based analysis with spatial population modelling to project spread rates for 15 000 virtual mammals with life histories that reflect those seen in the real world. Covariances among life‐history traits are estimated from an extensive terrestrial mammal data set using Bayesian inference. We elucidate the relative roles of different life‐history traits in driving modelled spread rates, demonstrating that any one alone will be a poor predictor. We also estimate that around 30% of mammal species have potential spread rates slower than the global mean velocity of climate change. This novel trait‐space‐demographic modelling approach has broad applicability for tackling many key ecological questions for which we have the models but are hindered by data availability.

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Quantifying the relative irreplaceability of important bird and biodiversity areas - Moreno Di Marco; Thomas Brooks; Annabelle Cuttelod; Lincoln D.C. Fishpool; Carlo Rondinini; Robert J. Smith; Leon Bennun; Stuart H.M. Butchart; Simon Ferrier; Ruud P.B. Foppen; Lucas Joppa; Diego Juffe‐Bignoli; et al. (Conservation Biology, 2016)
World governments have committed to increase the global protected areas coverage by 2020, but the effectiveness of this commitment for protecting biodiversity depends on where new protected areas are located. Threshold‐ and complementarity‐based approaches have been independently used to identify important sites for biodiversity. We brought together these approaches by performing a complementarity‐based analysis of irreplaceability in important bird and biodiversity areas (IBAs), which are sites identified using a threshold‐based approach. We determined whether irreplaceability values are higher inside than outside IBAs and whether any observed difference depends on known characteristics of the IBAs. We focused on 3 regions with comprehensive IBA inventories and bird distribution atlases: Australia, southern Africa, and Europe. Irreplaceability values were significantly higher inside than outside IBAs, although differences were much smaller in Europe than elsewhere. Higher irreplaceability values in IBAs were associated with the presence and number of restricted‐range species; number of criteria under which the site was identified; and mean geographic range size of the species for which the site was identified (trigger species). In addition, IBAs were characterized by higher irreplaceability values when using proportional species representation targets, rather than fixed targets. There were broadly comparable results when measuring irreplaceability for trigger species and when considering all bird species, which indicates a good surrogacy effect of the former. Recently, the International Union for Conservation of Nature has convened a consultation to consolidate global standards for the identification of key biodiversity areas (KBAs), building from existing approaches such as IBAs. Our results informed this consultation, and in particular a proposed irreplaceability criterion that will allow the new KBA standard to draw on the strengths of both threshold‐ and complementarity‐based approaches.

Advancing Product Quality: a Summary of the Second FDA/PQRI Conference - Lawrence X. Yu; Ilgaz Akseli; Barbara Allen; Gregory Amidon; Tara Gooen Bizjak; Ashley Boam; Margaret Caulk; David Doleski; Joseph Famulare; Adam C. Fisher; Scott Furness; Brian Hasselbalch; et al. (The AAPS Journal, 2016)

Genotypic variation in foundation species generates network structure that may drive community dynamics and evolution - Matthew K. Lau; Arthur R. Keith; Stuart R. Borrett; Stephen M. Shuster; Thomas G. Whitham (Ecology, 2016)
Although genetics in a single species is known to impact whole communities, little is known about how genetic variation influences species interaction networks in complex ecosystems. Here, we examine the interactions in a community of arthropod species on replicated genotypes (clones) of a foundation tree species, Populus angustifolia James (narrowleaf cottonwood), in a long‐term, common garden experiment using a bipartite “genotype–species” network perspective. We combine this empirical work with a simulation experiment designed to further investigate how variation among individual tree genotypes can impact network structure. Three findings emerged: (1) the empirical “genotype–species network” exhibited significant network structure with modularity being greater than the highly conservative null model; (2) as would be expected given a modular network structure, the empirical network displayed significant positive arthropod co‐occurrence patterns; and (3) furthermore, the simulations of “genotype–species” networks displayed variation in network structure, with modularity in particular clearly increasing, as genotypic variation increased. These results support the conclusion that genetic variation in a single species contributes to the structure of ecological interaction networks, which could influence ecological dynamics (e.g., assembly and stability) and evolution in a community context.

Temporal, regional and geochemical drivers of microbial community variation in the melt ponds of the Ross Sea region, Antarctica - Stephen D. J. Archer; Ian R. McDonald; Craig W. Herbold; Charles K. Lee; Thomas S. Niederberger; Craig Cary (Polar Biology, 2016)

Estimating genomic heritabilities at the level of family-pool samples of perennial ryegrass using genotyping-by-sequencing - Bilal Hassan Ashraf; Stephen Byrne; Dario Fé; Adrian Czaban; Torben Asp; Morten G. Pedersen; Ingo Lenk; Niels Roulund; Thomas Didion; Christian S. Jensen; Just Jensen; Luc L. Janss (Theoretical and Applied Genetics, 2016)

Beyond cool: adapting upland streams for climate change using riparian woodlands - Stephen M. Thomas; Siân W. Griffiths; Steve J. Ormerod (Global Change Biology, 2016)
Managed adaptation could reduce the risks of climate change to the world's ecosystems, but there have been surprisingly few practical evaluations of the options available. For example, riparian woodland is advocated widely as shade to reduce warming in temperate streams, but few studies have considered collateral effects on species composition or ecosystem functions. Here, we use cross‐sectional analyses at two scales (region and within streams) to investigate whether four types of riparian management, including those proposed to reduce potential climate change impacts, might also affect the composition, functional character, dynamics and energetic resourcing of macroinvertebrates in upland Welsh streams ( UK ). Riparian land use across the region had only small effects on invertebrate taxonomic composition, while stable isotope data showed how energetic resources assimilated by macroinvertebrates in all functional guilds were split roughly 50:50 between terrestrial and aquatic origins irrespective of riparian management. Nevertheless, streams draining the most extensive deciduous woodland had the greatest stocks of coarse particulate matter ( CPOM ) and greater numbers of ‘shredding’ detritivores. Stream‐scale investigations showed that macroinvertebrate biomass in deciduous woodland streams was around twice that in moorland streams, and lowest of all in streams draining non‐native conifers. The unexpected absence of contrasting terrestrial signals in the isotopic data implies that factors other than local land use affect the relative incorporation of allochthonous subsidies into riverine food webs. Nevertheless, our results reveal how planting deciduous riparian trees along temperate headwaters as an adaptation to climate change can modify macroinvertebrate function, increase biomass and potentially enhance resilience by increasing basal resources where cover is extensive (>60 m riparian width). We advocate greater urgency in efforts to understand the ecosystem consequences of climate change adaptation to guide future actions.

Terrestrial and marine perspectives on modeling organic matter degradation pathways - Adrian B. Burd; Serita Frey; Anna Cabre; Takamitsu Ito; Naomi M. Levine; Christian Lønborg; Matthew Long; Marguerite Mauritz; R. Quinn Thomas; Brandon M. Stephens; Tom Vanwalleghem; Ning Zeng (Global Change Biology, 2016)
Organic matter (OM) plays a major role in both terrestrial and oceanic biogeochemical cycles. The amount of carbon stored in these systems is far greater than that of carbon dioxide (CO 2 ) in the atmosphere, and annual fluxes of CO 2 from these pools to the atmosphere exceed those from fossil fuel combustion. Understanding the processes that determine the fate of detrital material is important for predicting the effects that climate change will have on feedbacks to the global carbon cycle. However, Earth System Models (ESMs) typically utilize very simple formulations of processes affecting the mineralization and storage of detrital OM. Recent changes in our view of the nature of this material and the factors controlling its transformation have yet to find their way into models. In this review, we highlight the current understanding of the role and cycling of detrital OM in terrestrial and marine systems and examine how this pool of material is represented in ESMs. We include a discussion of the different mineralization pathways available as organic matter moves from soils, through inland waters to coastal systems and ultimately into open ocean environments. We argue that there is strong commonality between aspects of OM transformation in both terrestrial and marine systems and that our respective scientific communities would benefit from closer collaboration.

Fiber bundle length and cognition: a length-based tractography MRI study - Ashley M. Behrman-Lay; Christina Usher; Thomas E. Conturo; Stephen Correia; David H. Laidlaw; Elizabeth M. Lane; Jacob Bolzenius; Jodi M. Heaps; Lauren E. Salminen; Laurie M. Baker; Ryan Cabeen; Erbil Akbudak; et al. (Brain Imaging and Behavior, 2015)

Environment Has Little Effect on Biomass Biochemical Composition of Miscanthus × giganteus Across Soil Types, Nitrogen Fertilization, and Times of Harvest - Rebecca A. Arundale; Stefan Bauer; Fernanda B. Haffner; Valerie D. Mitchell; Thomas B. Voigt; Stephen P. Long (BioEnergy Research, 2015)

Exploring, exploiting and evolving diversity of aquatic ecosystem models: a community perspective - Annette B. G. Janssen; George B. Arhonditsis; Arthur Beusen; Karsten Bolding; Louise Bruce; Jorn Bruggeman; Raoul-Marie Couture; Andrea S. Downing; J. Alex Elliott; Marieke A. Frassl; Gideon Gal; Daan J. Gerla; et al. (Aquatic Ecology, 2015)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

A reply to ‘A meta-database of Holocene sediment cores for England: missing data’ (Tooley 2015) - Andrew J. Suggitt; Richard T. Jones; Chris J. Caseldine; Brian Huntley; John R. Stewart; Stephen J. Brooks; Eleanor Brown; David Fletcher; Phillipa K. Gillingham; Jonathan Larwood; Nicholas A. Macgregor; Barbara Silva; et al. (Vegetation History and Archaeobotany, 2015)

A meta-database of Holocene sediment cores for England - Andrew J. Suggitt; Richard T. Jones; Chris J. Caseldine; Brian Huntley; John R. Stewart; Stephen J. Brooks; Eleanor Brown; David Fletcher; Phillipa K. Gillingham; Jonathan Larwood; Nicholas A. Macgregor; Barbara Silva; et al. (Vegetation History and Archaeobotany, 2015)

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

Copy number variants in patients with intellectual disability affect the regulation of ARX transcription factor gene - Minaka Ishibashi; Elizabeth Manning; Cheryl Shoubridge; Monika Krecsmarik; Thomas A. Hawkins; Jean Giacomotto; Ting Zhao; Thomas Mueller; Patricia I. Bader; Sau W. Cheung; Pawel Stankiewicz; Nicole L. Bain; et al. (Human Genetics, 2015)

Genetic and platelet function testing of antiplatelet therapy for percutaneous coronary intervention: the ARCTIC-GENE study - Jean-Philippe Collet; Jean-Sébastien Hulot; Thomas Cuisset; Grégoire Rangé; Guillaume Cayla; Eric Van Belle; Simon Elhadad; Hélène Rousseau; Pierre Sabouret; Stephen A. O’Connor; Jérémie Abtan; Mathieu Kerneis; et al. (European Journal of Clinical Pharmacology, 2015)

Changes in soil moisture drive soil methane uptake along a fire regeneration chronosequence in a eucalypt forest landscape - Benedikt Fest; Tim Wardlaw; Stephen J. Livesley; Thomas J. Duff; Stefan K. Arndt (Global Change Biology, 2015)
Disturbance associated with severe wildfires (WF) and WF simulating harvest operations can potentially alter soil methane ( CH 4 ) oxidation in well‐aerated forest soils due to the effect on soil properties linked to diffusivity, methanotrophic activity or changes in methanotrophic bacterial community structure. However, changes in soil CH 4 flux related to such disturbances are still rarely studied even though WF frequency is predicted to increase as a consequence of global climate change. We measured in‐situ soil–atmosphere CH 4 exchange along a wet sclerophyll eucalypt forest regeneration chronosequence in Tasmania, Australia, where the time since the last severe fire or harvesting disturbance ranged from 9 to >200 years. On all sampling occasions, mean CH 4 uptake increased from most recently disturbed sites (9 year) to sites at stand ‘maturity’ (44 and 76 years). In stands >76 years since disturbance, we observed a decrease in soil CH 4 uptake. A similar age dependency of potential CH 4 oxidation for three soil layers (0.0–0.05, 0.05–0.10, 0.10–0.15 m) could be observed on incubated soils under controlled laboratory conditions. The differences in soil CH 4 uptake between forest stands of different age were predominantly driven by differences in soil moisture status, which affected the diffusion of atmospheric CH 4 into the soil. The observed soil moisture pattern was likely driven by changes in interception or evapotranspiration with forest age, which have been well described for similar eucalypt forest systems in south‐eastern Australia. Our results imply that there is a large amount of variability in CH 4 uptake at a landscape scale that can be attributed to stand age and soil moisture differences. An increase in severe WF frequency in response to climate change could potentially increase overall forest soil CH 4 sinks.

Long‐term individual foraging site fidelity—why some gannets don't change their spots - Ewan D. Wakefield; Ian R. Cleasby; Stuart Bearhop; Thomas W. Bodey; Rachel D. Davies; Peter I. Miller; Jason Newton; Stephen C. Votier; Keith C. Hamer (Ecology, 2015)
Many established models of animal foraging assume that individuals are ecologically equivalent. However, it is increasingly recognized that populations may comprise individuals who differ consistently in their diets and foraging behaviors. For example, recent studies have shown that individual foraging site fidelity (IFSF, when individuals consistently forage in only a small part of their population's home range) occurs in some colonial breeders. Short‐term IFSF could result from animals using a win–stay, lose–shift foraging strategy. Alternatively, it may be a consequence of individual specialization. Pelagic seabirds are colonial central‐place foragers, classically assumed to use flexible foraging strategies to target widely dispersed, spatiotemporally patchy prey. However, tracking has shown that IFSF occurs in many seabirds, although it is not known whether this persists across years. To test for long‐term IFSF and to examine alternative hypotheses concerning its cause, we repeatedly tracked 55 Northern Gannets ( Morus bassanus ) from a large colony in the North Sea within and across three successive breeding seasons. Gannets foraged in neritic waters, predictably structured by tidal mixing and thermal stratification, but subject to stochastic, wind‐induced overturning. Both within and across years, coarse to mesoscale (tens of kilometers) IFSF was significant but not absolute, and foraging birds departed the colony in individually consistent directions. Carbon stable isotope ratios in gannet blood tissues were repeatable within years and nitrogen ratios were also repeatable across years, suggesting long‐term individual dietary specialization. Individuals were also consistent across years in habitat use with respect to relative sea surface temperature and in some dive metrics, yet none of these factors accounted for IFSF. Moreover, at the scale of weeks, IFSF did not decay over time and the magnitude of IFSF across years was similar to that within years, suggesting that IFSF is not primarily the result of win–stay, lose–shift foraging. Rather, we hypothesize that site familiarity, accrued early in life, causes IFSF by canalizing subsequent foraging decisions. Evidence from this and other studies suggests that IFSF may be common in colonial central‐place foragers, with far‐reaching consequences for our attempts to understand and conserve these animals in a rapidly changing environment.

A Pilot Study of Gait Function in Farmworkers in Eastern North Carolina - Ha T. Nguyen; Stephen B. Kritchevsky; Judy L. Foxworth; Sara A. Quandt; Phillip Summers; Francis O. Walker; Thomas A. Arcury (Journal of Agromedicine, 2015)

Rapid plant evolution in the presence of an introduced species alters community composition - David Solance Smith; Matthew K. Lau; Ryan Jacobs; Jenna A. Monroy; Stephen M. Shuster; Thomas G. Whitham (Oecologia, 2015)

Impact of human land use patterns and climatic variables on badger (Meles meles) foraging behaviour in Ireland - Stephen Elliott; John O’Brien; Thomas J. Hayden (Mammal Research, 2015)

Ecosystem‐scale volatile organic compound fluxes during an extreme drought in a broadleaf temperate forest of the Missouri Ozarks (central USA ) - Roger Seco; Thomas Karl; Alex Guenther; Kevin P. Hosman; Stephen G. Pallardy; Lianhong Gu; Chris Geron; Peter Harley; Saewung Kim (Global Change Biology, 2015)
Considerable amounts and varieties of biogenic volatile organic compounds ( BVOC s) are exchanged between vegetation and the surrounding air. These BVOC s play key ecological and atmospheric roles that must be adequately represented for accurately modeling the coupled biosphere–atmosphere–climate earth system. One key uncertainty in existing models is the response of BVOC fluxes to an important global change process: drought. We describe the diurnal and seasonal variation in isoprene, monoterpene, and methanol fluxes from a temperate forest ecosystem before, during, and after an extreme 2012 drought event in the Ozark region of the central USA . BVOC fluxes were dominated by isoprene, which attained high emission rates of up to 35.4 mg m −2 h −1 at midday. Methanol fluxes were characterized by net deposition in the morning, changing to a net emission flux through the rest of the daylight hours. Net flux of CO 2 reached its seasonal maximum approximately a month earlier than isoprenoid fluxes, which highlights the differential response of photosynthesis and isoprenoid emissions to progressing drought conditions. Nevertheless, both processes were strongly suppressed under extreme drought, although isoprene fluxes remained relatively high compared to reported fluxes from other ecosystems. Methanol exchange was less affected by drought throughout the season, confirming the complex processes driving biogenic methanol fluxes. The fraction of daytime (7–17 h) assimilated carbon released back to the atmosphere combining the three BVOC s measured was 2% of gross primary productivity ( GPP ) and 4.9% of net ecosystem exchange ( NEE ) on average for our whole measurement campaign, while exceeding 5% of GPP and 10% of NEE just before the strongest drought phase. The megan v2.1 model correctly predicted diurnal variations in fluxes driven mainly by light and temperature, although further research is needed to address model BVOC fluxes during drought events.

Approaches to fully documented fisheries: practical issues and stakeholder perceptions - Stephen C Mangi; Paul J Dolder; Thomas L Catchpole; Dale Rodmell; Nathan de Rozarieux (Fish and Fisheries, 2015)
The Common Fisheries Policy ( CFP ) reform sets out a move to a land‐all catch policy in European Union waters with a requirement for full reporting of fishing and on‐board processing activity. We explore the merits, stakeholder perceptions and applicability of different technology and approaches to the full documentation of fisheries that might be considered in the context of implementing the CFP reform. While recent efforts have focused on demonstrating how remote electronic monitoring ( REM ) systems can be utilized in fully documented fisheries ( FDF ), other technologies and approaches such as reference fleet and self‐sampling exist that could contribute to delivering FDF . Perceptions of fishers show that they would prefer using a reference fleet or self‐sampling to REM systems as a future method of implementing FDF . In general, there is support from the fishing industry for data collection and enhancement, but there remains some mistrust concerning the use of the data. Findings show that the most appropriate means and methods of FDF will depend on the circumstances and objectives for full documentation whether in enforcing a discard ban, documentation of total catch or data enhancement. We conclude that any technology or approach that will be used to deliver the monitoring requirements for FDF needs to make practical and commercial sense at the fishing vessel level.

Geographic and temporal dynamics of a global radiation and diversification in the killer whale - Phillip A. Morin; Kim M. Parsons; Frederick I. Archer; María C. Ávila‐Arcos; Lance G. Barrett‐Lennard; Luciano Dalla Rosa; Sebastián Duchêne; John W. Durban; Graeme M. Ellis; Steven H. Ferguson; John K. Ford; Michael J. Ford; et al. (Molecular Ecology, 2015)
Global climate change during the Late Pleistocene periodically encroached and then released habitat during the glacial cycles, causing range expansions and contractions in some species. These dynamics have played a major role in geographic radiations, diversification and speciation. We investigate these dynamics in the most widely distributed of marine mammals, the killer whale ( Orcinus orca ), using a global data set of over 450 samples. This marine top predator inhabits coastal and pelagic ecosystems ranging from the ice edge to the tropics, often exhibiting ecological, behavioural and morphological variation suggestive of local adaptation accompanied by reproductive isolation. Results suggest a rapid global radiation occurred over the last 350 000 years. Based on habitat models, we estimated there was only a 15% global contraction of core suitable habitat during the last glacial maximum, and the resources appeared to sustain a constant global effective female population size throughout the Late Pleistocene. Reconstruction of the ancestral phylogeography highlighted the high mobility of this species, identifying 22 strongly supported long‐range dispersal events including interoceanic and interhemispheric movement. Despite this propensity for geographic dispersal, the increased sampling of this study uncovered very few potential examples of ancestral dispersal among ecotypes. Concordance of nuclear and mitochondrial data further confirms genetic cohesiveness, with little or no current gene flow among sympatric ecotypes. Taken as a whole, our data suggest that the glacial cycles influenced local populations in different ways, with no clear global pattern, but with secondary contact among lineages following long‐range dispersal as a potential mechanism driving ecological diversification.

Ecological stoichiometry quantitatively predicts responses of tadpoles to a food quality gradient - Jeffrey .P Stephens; Keith A. Berven; Scott D. Tiegs; Thomas R. Raffel (Ecology, 2015)
Ecological stoichiometry (ES) uses elemental ratios and mass balance to explain organismal growth, an important parameter in ecological systems. In this study, we tested quantitative predictions of the ES “minimal model” for the growth rates of two tadpole species (wood frogs, Lithobates sylvaticus and American toads, Anaxyrus americanus ), by manipulating light and the quality of a leaf litter mixture in a seminatural mesocosm experiment. We predicted that wood frogs, which consume leaf litter as a resource, would respond more strongly to leaf litter quality than toads, which forage on periphyton and algae. The ES minimal model, parameterized from literature values, provided strikingly accurate quantitative predictions of nonlinear wood frog growth patterns across gradients of leaf litter quality, both in this experiment and when applied to previously published data on wood frog growth responses to various leaf litter species. In contrast, toad growth was best explained by the biomass of periphyton, which was driven primarily by light availability and only indirectly influenced by litter‐derived soluble polyphenols. This study demonstrates the power of ES to predict organism growth rates, and highlights potential applications of this theory to predicting population‐ and community‐level responses to changing forest environments.

Advancing Product Quality: a Summary of the Inaugural FDA/PQRI Conference - Lawrence X. Yu; Jeffrey Baker; Susan C. Berlam; Ashley Boam; E. J. Brandreth; Lucinda Buhse; Thomas Cosgrove; David Doleski; Lynne Ensor; Joseph Famulare; Mohan Ganapathy; Gustavo Grampp; et al. (The AAPS Journal, 2015)

Characterisation of major histocompatibility complex class I genes at the fetal-maternal interface of marsupials - Ina Buentjen; Barbara Drews; Stephen R. Frankenberg; Thomas B. Hildebrandt; Marilyn B. Renfree; Brandon R. Menzies (Immunogenetics, 2015)

Mechanistic relationships between hepatic genotoxicity and carcinogenicity in male B6C3F1 mice treated with polycyclic aromatic hydrocarbon mixtures - Tracie D. Phillips; Molly Richardson; Yi-Shing Lisa Cheng; Lingyu He; Thomas J. McDonald; Leslie H. Cizmas; Stephen H. Safe; Kirby C. Donnelly; Fen Wang; Bhagavatula Moorthy; Guo-Dong Zhou (Archives of Toxicology, 2015)

Understanding Ocean Acidification Impacts on Organismal to Ecological Scales - Andreas Andersson; David Kline; Peter Edmunds; Stephen Archer; Nina Bednaršek; Robert Carpenter; Meg Chadsey; Philip Goldstein; Andrea Grottoli; Thomas Hurst; Andrew King; Janet Kübler; et al. (Oceanography, 2015)

Overuse Activity in the Presence of Scapular Dyskinesis Leads to Shoulder Tendon Damage in a Rat Model - Katherine E. Reuther; Stephen J. Thomas; Jennica J. Tucker; Rameen P. Vafa; Joshua A. Gordon; Stephen S. Liu; Adam C. Caro; Sarah M. Yannascoli; Andrew F. Kuntz; Louis J. Soslowsky (Annals of Biomedical Engineering, 2015)

A whole-lake experiment to control invasive rainbow smelt (Actinoperygii, Osmeridae) via overharvest and a food web manipulation - Jereme W. Gaeta; Thomas R. Hrabik; Greg G. Sass; Brian M. Roth; Stephen J. Gilbert; M. Jake Vander Zanden (Hydrobiologia, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Hyaluronan in aged collagen matrix increases prostate epithelial cell proliferation - Mamatha Damodarasamy; Robert B. Vernon; Christina K. Chan; Stephen R. Plymate; Thomas N. Wight; May J. Reed (In Vitro Cellular & Developmental Biology - Animal, 2015)

Potential impact of invasive alien species on ecosystem services provided by a tropical forested ecosystem: a case study from Montserrat - Kelvin S.-H. Peh; Andrew Balmford; Jennifer C. Birch; Claire Brown; Stuart H. M. Butchart; James Daley; Jeffrey Dawson; Gerard Gray; Francine M. R. Hughes; Stephen Mendes; James Millett; Alison J. Stattersfield; et al. (Biological Invasions, 2015)

Diverse trends in shell weight of three Southern Ocean pteropod taxa collected with Polar Frontal Zone sediment traps from 1997 to 2007 - Donna Roberts; William R. Howard; Jason L. Roberts; Stephen G. Bray; Andrew D. Moy; Thomas W. Trull; Russell R. Hopcroft (Polar Biology, 2014)

Hill Shape Effect on Yield, Quality, Stolon Length and Tuber Orientation of Two Potato Cultivars - William H. Bohl; Stephen L. Love; Thomas Salaiz (American Journal of Potato Research, 2014)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Small Molecule Specific Run Acceptance, Specific Assay Operation, and Chromatographic Run Quality Assessment: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Teams - Eric J. Woolf; Stuart McDougall; Douglas M. Fast; Maristela Andraus; Matthew Barfield; Michael Blackburn; Ben Gordon; David Hoffman; Noriko Inoue; Gabriel Marcelin-Jimenez; Amy Flynn; Richard LeLacheur; et al. (The AAPS Journal, 2014)

Erratum to: Reversal of Thienopyridine-Induced Platelet Dysfunction Following Desmopressin Administration - Michael Levine; Steve Swenson; Taylor McCormick; Sean O. Henderson; Stephen H. Thomas; Francis S. Markland (Journal of Medical Toxicology, 2014)

Preclinical Studies on Neurobehavioral and Neuromuscular Effects of Cocaine Hydrolase Gene Therapy in Mice - Vishakantha Murthy; Yang Gao; Liyi Geng; Nathan LeBrasseur; Thomas White; Stephen Brimijoin (Journal of Molecular Neuroscience, 2014)

Unsupported inferences of high‐severity fire in historical dry forests of the western U nited S tates: response to W illiams and B aker - Peter Z. Fulé; Thomas W. Swetnam; Peter M. Brown; Donald A. Falk; David L. Peterson; Craig D. Allen; Gregory H. Aplet; Mike A. Battaglia; Dan Binkley; Calvin Farris; Robert E. Keane; Ellis Q. Margolis; et al. (Global Ecology and Biogeography, 2014)
Reconstructions of dry western US forests in the late 19th century in A rizona, C olorado and O regon based on G eneral L and O ffice records were used by W illiams & B aker (2012; G lobal E cology and B iogeography , 21 , 1042–1052; hereafter W & B ) to infer past fire regimes with substantial moderate and high‐severity burning. The authors concluded that present‐day large, high‐severity fires are not distinguishable from historical patterns. We present evidence of important errors in their study. First, the use of tree size distributions to reconstruct past fire severity and extent is not supported by empirical age–size relationships nor by studies that directly quantified disturbance history in these forests. Second, the fire severity classification of W & B is qualitatively different from most modern classification schemes, and is based on different types of data, leading to an inappropriate comparison. Third, we note that while W & B asserted ‘surprising’ heterogeneity in their reconstructions of stand density and species composition, their data are not substantially different from many previous studies which reached very different conclusions about subsequent forest and fire behaviour changes. Contrary to the conclusions of W & B , the preponderance of scientific evidence indicates that conservation of dry forest ecosystems in the western U nited S tates and their ecological, social and economic value is not consistent with a present‐day disturbance regime of large, high‐severity fires, especially under changing climate.

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

HIV subtype is not associated with dementia among individuals with moderate and advanced immunosuppression in Kampala, Uganda - Ned Sacktor; Noeline Nakasujja; Andrew D. Redd; Jordyn Manucci; Oliver Laeyendecker; Sarah K. Wendel; Stephen F Porcella; Craig Martens; Daniel Bruno; Richard L. Skolasky; Ozioma C. Okonkwo; Kevin Robertson; et al. (Metabolic Brain Disease, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Development of 15 microsatellite loci from mulloway, Argyrosomus japonicus (Pisces: Sciaenidae) using next generation sequencing and an assessment of their cross amplification in other sciaenids - Thomas C. Barnes; Christopher Izzo; Terry Bertozzi; Kathleen M. Saint; Stephen Donnellan; Michael P. Hammer; Bronwyn M. Gillanders (Conservation Genetics Resources, 2014)

Niche partitioning of bacterial communities in biological crusts and soils under grasses, shrubs and trees in the Kalahari - David R. Elliott; Andrew D. Thomas; Stephen R. Hoon; Robin Sen (Biodiversity and Conservation, 2014)

Cryptic ecology among host generalist Campylobacter jejuni in domestic animals - Samuel K. Sheppard; Lu Cheng; Guillaume Méric; Caroline P. A. de Haan; Ann‐Katrin Llarena; Pekka Marttinen; Ana Vidal; Anne Ridley; Felicity Clifton‐Hadley; Thomas R. Connor; Norval J. C. Strachan; Ken Forbes; et al. (Molecular Ecology, 2014)
Homologous recombination between bacterial strains is theoretically capable of preventing the separation of daughter clusters, and producing cohesive clouds of genotypes in sequence space. However, numerous barriers to recombination are known. Barriers may be essential such as adaptive incompatibility, or ecological, which is associated with the opportunities for recombination in the natural habitat. Campylobacter jejuni is a gut colonizer of numerous animal species and a major human enteric pathogen. We demonstrate that the two major generalist lineages of C. jejuni do not show evidence of recombination with each other in nature, despite having a high degree of host niche overlap and recombining extensively with specialist lineages. However, transformation experiments show that the generalist lineages readily recombine with one another in vitro. This suggests ecological rather than essential barriers to recombination, caused by a cryptic niche structure within the hosts.

Ecological mitigation of hillslope instability: ten key issues facing researchers and practitioners - Alexia Stokes; Grant B. Douglas; Thierry Fourcaud; Filippo Giadrossich; Clayton Gillies; Thomas Hubble; John H. Kim; Kenneth W. Loades; Zhun Mao; Ian R. McIvor; Slobodan B. Mickovski; Stephen Mitchell; et al. (Plant and Soil, 2014)

Pyrogeography, historical ecology, and the human dimensions of fire regimes - Christopher I. Roos; David M. J. S. Bowman; Jennifer K. Balch; Paulo Artaxo; William J. Bond; Mark Cochrane; Carla M. D'Antonio; Ruth DeFries; Michelle Mack; Fay H. Johnston; Meg A. Krawchuk; Christian A. Kull; et al. (Journal of Biogeography, 2014)
In our 2011 synthesis (Bowman et al ., Journal of Biogeography , 2011, 38 , 2223–2236), we argued for a holistic approach to human issues in fire science that we term ‘pyrogeography’. Coughlan & Petty ( Journal of Biogeography , 2013, 40 , 1010–1012) critiqued our paper on the grounds that our ‘pyric phase’ model was built on outdated views of cultural development, claiming we developed it to be the unifying explanatory framework for all human–fire sciences. Rather, they suggest that ‘historical ecology’ could provide such a framework. We used the ‘pyric transition’ for multiple purposes but did not offer it as an exclusive explanatory framework for pyrogeography. Although ‘historical ecology’ is one of many useful approaches to studying human–fire relationships, scholars should also look to political and evolutionary ecology, ecosystems and complexity theories, as well as empirical generalizations to build an interdisciplinary fire science that incorporates human, ecological and biophysical dimensions of fire regimes.

Development of a Multi-modality Compatible Flow Loop System for the Functional Assessment of Mitral Valve Prostheses - Matthew S. Jackson; Stephen R. Igo; Thomas E. Lindsey; Dimitrios Maragiannis; Karen E. Chin; Kyle Autry; Robert Schutt; Dipan J. Shah; Pietro Valsecchi; William B. Kline; Stephen H. Little (Cardiovascular Engineering and Technology, 2014)

Nitrogen Fertilization Does Significantly Increase Yields of Stands of Miscanthus × giganteus and Panicum virgatum in Multiyear Trials in Illinois - Rebecca A. Arundale; Frank G. Dohleman; Thomas B. Voigt; Stephen P. Long (BioEnergy Research, 2014)

The Tendon Injury Response is Influenced by Decorin and Biglycan - Andrew A. Dunkman; Mark R. Buckley; Michael J. Mienaltowski; Sheila M. Adams; Stephen J. Thomas; Lauren Satchell; Akash Kumar; Lydia Pathmanathan; David P. Beason; Renato V. Iozzo; David E. Birk; Louis J. Soslowsky (Annals of Biomedical Engineering, 2014)

Ectomycorrhizal inoculum potential of northeastern US forest soils for American chestnut restoration: results from field and laboratory bioassays - Kristopher M. Dulmer; Stephen D. LeDuc; Thomas R. Horton (Mycorrhiza, 2014)

A taxonomic comparison of local habitat niches of tropical trees - Claire A. Baldeck; Steven W. Kembel; Kyle E. Harms; Joseph B. Yavitt; Robert John; Benjamin L. Turner; George B. Chuyong; David Kenfack; Duncan W. Thomas; Sumedha Madawala; Nimal Gunatilleke; Savitri Gunatilleke; et al. (Oecologia, 2013)

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

Top‐down control of soil fungal community composition by a globally distributed keystone consumer - Thomas W. Crowther; David W. G. Stanton; Stephen M. Thomas; A. Donald A'Bear; Jennifer Hiscox; T. Hefin Jones; Jana Voříšková; Petr Baldrian; Lynne Boddy (Ecology, 2013)
The relative contribution of top‐down and bottom‐up processes regulating primary decomposers can influence the strength of the link between the soil animal community and ecosystem functioning. Although soil bacterial communities are regulated by bottom‐up and top‐down processes, the latter are considered to be less important in structuring the diversity and functioning of fungal‐dominated ecosystems. Despite the huge diversity of mycophagous (fungal‐feeding) soil fauna, and their potential to reverse the outcomes of competitive fungal interactions, top‐down grazing effects have never been found to translate to community‐level changes. We constructed soil mesocosms to investigate the potential of isopods grazing on cord‐forming basidiomycete fungi to influence the community composition and functioning of a complex woodland soil microbial community. Using metagenomic sequencing we provide conclusive evidence of direct top‐down control at the community scale in fungal‐dominated woodland soil. By suppressing the dominant cord‐forming basidiomycete fungi, isopods prevented the competitive exclusion of surrounding litter fungi, increasing diversity in a community containing several hundred fungal species. This isopod‐induced modification of community composition drove a shift in the soil enzyme profile, and led to a restructuring of the wider mycophagous invertebrate community. We highlight characteristics of different soil ecosystems that will give rise to such top‐down control. Given the ubiquity of isopods and basidiomycete fungi in temperate and boreal woodland ecosystems, such top‐down community control could be of widespread significance for global carbon and nutrient cycling.

Transatlantic migration by post-breeding puffins: a strategy to exploit a temporarily abundant food resource? - Mark J. Jessopp; Michelle Cronin; Thomas K. Doyle; Mark Wilson; Abigail McQuatters-Gollop; Stephen Newton; Richard A. Phillips (Marine Biology, 2013)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

MultiSig: a new high-precision approach to the analysis of complex biomolecular systems - Richard B. Gillis; Gary G. Adams; Thomas Heinze; Melanie Nikolajski; Stephen E. Harding; Arthur J. Rowe (European Biophysics Journal, 2013)

Neuronal fiber bundle lengths in healthy adult carriers of the ApoE4 allele: A quantitative tractography DTI study - Lauren E. Salminen; Peter R. Schofield; Elizabeth M. Lane; Jodi M. Heaps; Kerrie D. Pierce; Ryan Cabeen; David H. Laidlaw; Erbil Akbudak; Thomas E. Conturo; Stephen Correia; Robert H. Paul (Brain Imaging and Behavior, 2013)

Multi‐factorial drivers of ammonia oxidizer communities: evidence from a national soil survey - Huaiying Yao; Colin D. Campbell; Stephen J. Chapman; Thomas E. Freitag; Graeme W. Nicol; Brajesh K. Singh (Environmental Microbiology, 2013)
Summary The factors driving the abundance and community composition of soil microbial communities provide fundamental knowledge on the maintenance of biodiversity and the ecosystem services they underpin. Several studies have suggested that microbial communities are spatially organized, including functional groups and much of the observed variation is explained by geographical location or soil pH . S oil ammonia‐oxidizing archaea ( AOA ) and bacteria ( AOB ) are excellent models for such study due to their functional, agronomic and environmental importance and their relative ease of characterization. To identify the dominant drivers of different ammonia oxidizers, we used samples ( n = 713) from the N ational S oil I nventory of S cotland ( NSIS ). Our results indicate that 40–45% of the variance in community compositions can be explained by 71 environmental variables. Soil pH and substrate, which have been regarded as the two main drivers, only explained 13–16% of the total variance. We provide strong evidence of multi‐factorial drivers (land use, soil type, climate and N deposition) of ammonia‐oxidizing communities, all of which play a significant role in the creation of specific niches that are occupied by unique phylotypes. For example, one AOA phylotype was strongly linked to woodland/semi‐natural grassland, rainfall and N deposition. Some soil typologies, namely regosols, have a novel AOA community composition indicating typology as one of the factors which defines this ecological niche. AOA abundance was high and strongly linked the rate of potential nitrification in the highly acidic soils supporting the argument that AOA are main ammonia oxidizers in acidic soils. However, for AOB , soil pH and substrate (ammonia) were the main drivers for abundance and community composition. These results highlight the importance of multiple drivers of microbial niche formation and their impact on microbial biogeography that have significant consequences for ecosystem functioning.

A basic residue in the proximal C-terminus is necessary for efficient activation of the M-channel subunit Kv7.2 by PI(4,5)P2 - Vsevolod Telezhkin; Alison M. Thomas; Stephen C. Harmer; Andrew Tinker; David A. Brown (Pflügers Archiv - European Journal of Physiology, 2013)

Quantifying the production of dissolved organic nitrogen in headwater streams using 15 N tracer additions - Laura T. Johnson; Jennifer L. Tank; Robert O. Hall, Jr.; Patrick J. Mulholland; Stephen K. Hamilton; H. Maurice Valett; Jackson R. Webster; Melody J. Bernot; William H. McDowell; Bruce J. Peterson; Suzanne M. Thomas (Limnology and Oceanography, 2013)
Most nitrogen (N) assimilation in lake and marine ecosystems is often subsequently released via autochthonous dissolved organic nitrogen (DON) production, but autochthonous DON production has yet to be quantified in flowing waters. We measured in‐stream DON production following 24 h 15 N‐nitrate () tracer additions in 36 headwater streams, a subset of sites from the second Lotic Intersite Nitrogen eXperiment. Streams were located in five North American ecoregions and drained basins dominated by native vegetation, agriculture, or urban land use. Using a two‐compartment model, we could quantify DON production in 15 streams as a function of DO 15 N derived from 15 N tracer in biomass compartments. The streams with detectable DON production had higher % modified land use (agriculture + urban) in their basins than did streams with undetectable DON production. Median DON production represented 8% of total uptake when we used N biomass estimates based on N assimilated over 1 d (measured directly from the 15 N additions). Median DON production was 17% of total uptake when we used N assimilated over 42 d (extrapolated from previous 15 N tracer studies). Variation in DON production was positively correlated with ecosystem respiration, indicating that stream heterotrophy may influence DON production. In‐stream DON production was similar in magnitude to stream denitrification and nitrification, indicating that the production of autochthonous DON can represent a substantial transformation of stream N. Our results confirm that headwater streams can quickly convert inorganic N into organic forms, although the ultimate fate of DON remains unclear.

Seasonal and regional differences in the rainfall and intensity of isolated convection over South America - Thomas M. Rickenbach; Rosana Nieto‐Ferreira; Richard P. Barnhill; Stephen W. Nesbitt (International Journal of Climatology, 2013)
Isolated precipitating convection, though a minor contributor to total rainfall in the tropics, is important to regional and seasonal climate variability because its diabatic heating structure is characteristic of the convectively inactive phase of tropical interseasonal oscillations. This study extends a previous analysis of mesoscale convective system (MCS) variability in the South America monsoon system to examine regional differences in the annual cycle of the rainfall and vertical structure of isolated convection over the 10 year period of 1998–2007. The goal is to document the annual variation of shallow and deep isolated convection in order to provide a more complete picture of monsoon onset across South America. Over the 10 year period of 1998–2007, the average rain contribution from isolated convection (compared to MCSs) ranged from 1 to 8% of the total rainfall in the four regions depending on the season. The contribution of rainfall by isolated convection was on the high end of that range during the pre‐monsoon months of June to August in the tropical regions. Of the isolated convection rainfall, 4–9% was attributable to shallow ‘warm rain’, with the largest fraction after monsoon onset (December to February) in the coastal Mouth of Amazon region. Mean annual time series of conditional rainfall, lightning activity, 85 GHz ice‐scattering signature, and radar echo depth for isolated convective features all suggested that an oceanic regime strongly influences isolated convection at the Mouth of Amazon region in northeastern Brazil. In the interior tropical regions, there was a clear pre‐monsoon (August to September) maximum in the vertical intensity of deep isolated convection as indicated by lightning, ice scattering, and radar echo depth. Copyright © 2012 Royal Meteorological Society

A Design Space Verification Protocol for a Small Molecule Drug Substance - Timothy J. N. Watson; Holly Bonsignore; Eileen A. Callaghan-Manning; Stephen T. Colgan; Paul Fitzsimons; Thomas P. Garcia; John G. Groskoph; Michael P. Lynch; Roger Nosal; Megan E. McMahon; Robert A. Singer; Nicholas M. Thomson; et al. (Journal of Pharmaceutical Innovation, 2013)

Reversal of Thienopyridine-Induced Platelet Dysfunction Following Desmopressin Administration - Michael Levine; Steve Swenson; Taylor McCormick; Sean O. Henderson; Stephen H. Thomas; Francis S. Markland (Journal of Medical Toxicology, 2013)

Shallow lake sediments provide evidence for metapopulation dynamics: a pilot study - Beth Okamura; Karen Ayres; Jorge Salgado; Thomas A. Davidson; Rosalind F. Shaw; Thomas W. Stephens; Daniel Hoare; Carl D. Sayer (Aquatic Ecology, 2013)

Ectomycorrhizal fungal succession coincides with shifts in organic nitrogen availability and canopy closure in post-wildfire jack pine forests - Stephen D. LeDuc; Erik A. Lilleskov; Thomas R. Horton; David E. Rothstein (Oecologia, 2013)

Androgenetic alopecia at various ages and prostate cancer risk in an equal-access multiethnic case–control series of veterans - Jean-Alfred Thomas; Jodi A. Antonelli; Lionel L. Banez; Catherine Hoyo; Delores Grant; Wendy Demark-Wahnefried; Elizabeth A. Platz; Leah Gerber; Kathryn Shuler; Enwono Eyoh; Elizabeth Calloway; Stephen J. Freedland (Cancer Causes & Control, 2013)

Microevolution in time and space: SNP analysis of historical DNA reveals dynamic signatures of selection in A tlantic cod - Nina O. Therkildsen; Jakob Hemmer‐Hansen; Thomas D. Als; Douglas P. Swain; M. Joanne Morgan; Edward A. Trippel; Stephen R. Palumbi; Dorte Meldrup; Einar E. Nielsen (Molecular Ecology, 2013)
Little is known about how quickly natural populations adapt to changes in their environment and how temporal and spatial variation in selection pressures interact to shape patterns of genetic diversity. We here address these issues with a series of genome scans in four overfished populations of Atlantic cod ( G adus morhua ) studied over an 80‐year period. Screening of >1000 gene‐associated single‐nucleotide polymorphisms ( SNP s) identified 77 loci that showed highly elevated levels of differentiation, likely as an effect of directional selection, in either time, space or both. Exploratory analysis suggested that temporal allele frequency shifts at certain loci may correlate with local temperature variation and with life history changes suggested to be fisheries induced. Interestingly, however, largely nonoverlapping sets of loci were temporal outliers in the different populations and outliers from the 1928 to 1960 period showed almost complete stability during later decades. The contrasting microevolutionary trajectories among populations resulted in sequential shifts in spatial outliers, with no locus maintaining elevated spatial differentiation throughout the study period. Simulations of migration coupled with observations of temporally stable spatial structure at neutral loci suggest that population replacement or gene flow alone could not explain all the observed allele frequency variation. Thus, the genetic changes are likely to at least partly be driven by highly dynamic temporally and spatially varying selection. These findings have important implications for our understanding of local adaptation and evolutionary potential in high gene flow organisms and underscore the need to carefully consider all dimensions of biocomplexity for evolutionarily sustainable management.

Evaluating atmospheric CO 2 inversions at multiple scales over a highly inventoried agricultural landscape - Andrew E. Schuh; Thomas Lauvaux; Tristram O. West; A. Scott Denning; Kenneth J. Davis; Natasha Miles; Scott Richardson; Marek Uliasz; Erandathie Lokupitiya; Daniel Cooley; Arlyn Andrews; Stephen Ogle (Global Change Biology, 2013)
An intensive regional research campaign was conducted by the N orth A merican Carbon Program ( NACP ) in 2007 to study the carbon cycle of the highly productive agricultural regions of the M idwestern U nited S tates. Forty‐five different associated projects were conducted across five US agencies over the course of nearly a decade involving hundreds of researchers. One of the primary objectives of the intensive campaign was to investigate the ability of atmospheric inversion techniques to use highly calibrated CO 2 mixing ratio data to estimate CO 2 flux over the major croplands of the U nited S tates by comparing the results to an inventory of CO 2 fluxes. Statistics from densely monitored crop production, consisting primarily of corn and soybeans, provided the backbone of a well studied bottom‐up inventory flux estimate that was used to evaluate the atmospheric inversion results. Estimates were compared to the inventory from three different inversion systems, representing spatial scales varying from high resolution mesoscale ( PSU ), to continental ( CSU ) and global (CarbonTracker), coupled to different transport models and optimization techniques. The inversion‐based mean CO 2 ‐C sink estimates were generally slightly larger, 8–20% for PSU , 10–20% for CSU , and 21% for CarbonTracker, but statistically indistinguishable, from the inventory estimate of 135 TgC. While the comparisons show that the MCI region‐wide C sink is robust across inversion system and spatial scale, only the continental and mesoscale inversions were able to reproduce the spatial patterns within the region. In general, the results demonstrate that inversions can recover CO 2 fluxes at sub‐regional scales with a relatively high density of CO 2 observations and adequate information on atmospheric transport in the region.

A physical map of the Chinese chestnut (Castanea mollissima) genome and its integration with the genetic map - Guang-Chen Fang; Barbara P. Blackmon; Margaret E. Staton; C. Dana Nelson; Thomas L. Kubisiak; Bode A. Olukolu; David Henry; Tatyana Zhebentyayeva; Christopher A. Saski; Chun-Huai Cheng; Megan Monsanto; Stephen Ficklin; et al. (Tree Genetics & Genomes, 2013)

Intra-genotypic variation of predominant genotype II strains of dengue type-3 virus isolated during different epidemics in Thailand from 1973 to 2001 - Aimee Zhang; Piyawan Chinnawirotpisan; Yuxin Tang; Yanfei Zhou; Julia Lynch; Stephen Thomas; Siripen Kalayanarooj; Robert Putnak; Chunlin Zhang (Virus Genes, 2013)

Modelling the effects of dispersal mechanisms and hydrodynamic regimes upon the structure of microbial communities within fluvial biofilms - Stephen Woodcock; Katharina Besemer; Tom J. Battin; Thomas P. Curtis; William T. Sloan (Environmental Microbiology, 2013)
Summary The spatial distribution of microbial taxa is determined primarily by physical and chemical environments and by dispersal. In a homogeneous landscape with limited dispersal, the similarity in abundance of taxa in samples declines with separation distance. We present a one‐dimensional model for the spatial autocorrelation in abundances arising from immigration from some remote community and dispersal between environmentally similar landscape patches. Spatial correlation in taxa abundances were calculated from biofilms from the beds of two flumes which differed only in their bedform profiles; one flat and the other a periodic sawtooth shape. The hydraulic regime is approximately uniform over the flat bed, whereas the sawtooth induces fast flow over the peaks and recirculation in the troughs. On the flat bed, the correlation decline between samples was reproduced by a model using one biologically reasonable parameter. A decline was apparent in the other flume; however, a better fit was achieved when dispersal was not assumed constant everywhere. However, analysis of finer‐resolution data for the heterogeneous flume suggested even this model did not adequately capture the community's complexity. We conclude that hydrodynamics are a strong driver of taxa‐abundance patterns in stream biofilms. However, local adaptability must also be considered to build up a complete mechanistic model.

Comparison of common bean (Phaseolus vulgaris L.) genotypes for nitrogen fixation tolerance to soil drying - Mura Jyostna Devi; Thomas R. Sinclair; Stephen E. Beebe; Idupulapati M. Rao (Plant and Soil, 2013)

Tree growth-competition relationships in thinned Eucalyptus plantations vary with stand structure and site quality - David I. Forrester; Stephen R. Elms; Thomas G. Baker (European Journal of Forest Research, 2013)

A constrained least-squares approach to combine bottom-up and top-down CO2 flux estimates - Daniel Cooley; F. Jay Breidt; Stephen M. Ogle; Andrew E. Schuh; Thomas Lauvaux (Environmental and Ecological Statistics, 2013)

Impact of climate warming on upper layer of the Bering Sea - Hyun-Chul Lee; Thomas L. Delworth; Anthony Rosati; Rong Zhang; Whit G. Anderson; Fanrong Zeng; Charles A. Stock; Anand Gnanadesikan; Keith W. Dixon; Stephen M. Griffies (Climate Dynamics, 2013)

Estimating minke whale ( Balaenoptera acutorostrata ) boing sound density using passive acoustic sensors - Stephen W. Martin; Tiago A. Marques; Len Thomas; Ronald P. Morrissey; Susan Jarvis; Nancy DiMarzio; David Moretti; David K. Mellinger (Marine Mammal Science, 2013)
A bstract Density estimation for marine mammal species is performed primarily using visual distance sampling or capture‐recapture. Minke whales in Hawaiian waters are very difficult to sight; however, they produce a distinctive “boing” call, making them ideal candidates for passive acoustic density estimation. We used an array of 14 bottom‐mounted hydrophones, distributed over a 60 × 30 km area off Kauai, Hawaii, to estimate density during 12 d of recordings in early 2006. We converted the number of acoustic cues ( i.e. , boings) detected using signal processing software into a cue density by accounting for the false positive rate and probability of detection. The former was estimated by manual validation, the latter by applying spatially explicit capture‐recapture (SECR) methods to a subset of data where we had determined which hydrophones detected each call. Estimated boing density was 130 boings per hour per 10,000 km 2 (95% CI 104–163). Little is known about the population's acoustic behavior, so conversion from boing to animal density is difficult. As a demonstration of the method, we used a tentative boing rate of 6.04 boings per hour, from a single animal tracked in 2009, to give an estimate of 21.5 boing‐calling minke whales per 10,000 km 2 .

The John Williams Index of Palaeopalynology - James B. Riding; Matthew J. Pound; Thomas C.B. Hill; Stephen Stukins; Susanne Feist-Burkhardt (Palynology, 2012)

Testosterone induces off-line perceptual learning - Nicholas D. Wright; Thomas Edwards; Stephen M. Fleming; Raymond J. Dolan (Psychopharmacology, 2012)

A late glacial Antarctic climate teleconnection and variable Holocene seasonality at Lake Pupuke, Auckland, New Zealand - Thomas Stephens; Daniel Atkin; Paul Augustinus; Philip Shane; Andrew Lorrey; Alayne Street-Perrott; Andreas Nilsson; Ian Snowball (Journal of Paleolimnology, 2012)

A diatom-inferred record of reduced effective precipitation during the Last Glacial Coldest Phase (28.8–18.0 cal kyr BP) and increasing Holocene seasonality at Lake Pupuke, Auckland, New Zealand - Thomas Stephens; Daniel Atkin; Ursula Cochran; Paul Augustinus; Michael Reid; Andrew Lorrey; Philip Shane; Alayne Street-Perrott (Journal of Paleolimnology, 2012)

Targeted genome enrichment for efficient purification of endosymbiont DNA from host DNA - Sandrine Geniez; Jeremy M. Foster; Sanjay Kumar; Bouziane Moumen; Emily LeProust; Owen Hardy; Moraima Guadalupe; Stephen J. Thomas; Braden Boone; Cynthia Hendrickson; Didier Bouchon; Pierre Grève; et al. (Symbiosis, 2012)

Multiple jejunal cancers resulting from combination of germline APC and MLH1 mutations - Noralane M. Lindor; Tom C. Smyrk; Sheila Buehler; Shanaka R. Gunawardena; Brittany C. Thomas; Paul Limburg; Salman Kirmani; Stephen N. Thibodeau (Familial Cancer, 2012)

Contrasting effects of sunitinib within in vivo models of metastasis - Jonathan C. Welti; Thomas Powles; Shane Foo; Morgane Gourlaouen; Natasha Preece; Julie Foster; Sophia Frentzas; Demelza Bird; Kevin Sharpe; Antoinette van Weverwijk; David Robertson; Julie Soffe; et al. (Angiogenesis, 2012)

The variation of tree beta diversity across a global network of forest plots - Miquel De Cáceres; Pierre Legendre; Renato Valencia; Min Cao; Li‐Wan Chang; George Chuyong; Richard Condit; Zhanqing Hao; Chang‐Fu Hsieh; Stephen Hubbell; David Kenfack; Keping Ma; et al. (Global Ecology and Biogeography, 2012)
Aims With the aim of understanding why some of the world's forests exhibit higher tree beta diversity values than others, we asked: (1) what is the contribution of environmentally related variation versus pure spatial and local stochastic variation to tree beta diversity assessed at the forest plot scale; (2) at what resolution are these beta‐diversity components more apparent; and (3) what determines the variation in tree beta diversity observed across regions/continents? Location World‐wide. Methods We compiled an unprecedented data set of 10 large‐scale stem‐mapping forest plots differing in latitude, tree species richness and topographic variability. We assessed the tree beta diversity found within each forest plot separately. The non‐directional variation in tree species composition among cells of the plot was our measure of beta diversity. We compared the beta diversity of each plot with the value expected under a null model. We also apportioned the beta diversity into four components: pure topographic, spatially structured topographic, pure spatial and unexplained. We used linear mixed models to interpret the variation of beta diversity values across the plots. Results Total tree beta diversity within a forest plot decreased with increasing cell size, and increased with tree species richness and the amount of topographic variability of the plot. The topography‐related component of beta diversity was correlated with the amount of topographic variability but was unrelated to its species richness. The unexplained variation was correlated with the beta diversity expected under the null model and with species richness. Main conclusions Because different components of beta diversity have different determinants, comparisons of tree beta diversity across regions should quantify not only overall variation in species composition but also its components. Global‐scale patterns in tree beta diversity are largely coupled with changes in gamma richness due to the relationship between the latter and the variation generated by local stochastic assembly processes.

A European science plan to sustainably increase food security under climate change - Jean‐François Soussana; Elias Fereres; Stephen P. Long; Frits GMJ Mohren; Rajul Pandya‐Lorch; Pirjo Peltonen‐Sainio; John R. Porter; Thomas Rosswall; Joachim von Braun (Global Change Biology, 2012)

Recovery of ponderosa pine ecosystem carbon and water fluxes from thinning and stand‐replacing fire - Sabina Dore; Mario Montes‐Helu; Stephen C. Hart; Bruce A. Hungate; George W. Koch; John B. Moon; Alex J. Finkral; Thomas E. Kolb (Global Change Biology, 2012)
Carbon uptake by forests is a major sink in the global carbon cycle, helping buffer the rising concentration of CO 2 in the atmosphere, yet the potential for future carbon uptake by forests is uncertain. Climate warming and drought can reduce forest carbon uptake by reducing photosynthesis, increasing respiration, and by increasing the frequency and intensity of wildfires, leading to large releases of stored carbon. Five years of eddy covariance measurements in a ponderosa pine ( Pinus ponderosa )‐dominated ecosystem in northern Arizona showed that an intense wildfire that converted forest into sparse grassland shifted site carbon balance from sink to source for at least 15 years after burning. In contrast, recovery of carbon sink strength after thinning, a management practice used to reduce the likelihood of intense wildfires, was rapid. Comparisons between an undisturbed‐control site and an experimentally thinned site showed that thinning reduced carbon sink strength only for the first two posttreatment years. In the third and fourth posttreatment years, annual carbon sink strength of the thinned site was higher than the undisturbed site because thinning reduced aridity and drought limitation to carbon uptake. As a result, annual maximum gross primary production occurred when temperature was 3 °C higher at the thinned site compared with the undisturbed site. The severe fire consistently reduced annual evapotranspiration (range of 12–30%), whereas effects of thinning were smaller and transient, and could not be detected in the fourth year after thinning. Our results show large and persistent effects of intense fire and minor and short‐lived effects of thinning on southwestern ponderosa pine ecosystem carbon and water exchanges.

Consensus Paper: Pathological Role of the Cerebellum in Autism - S. Hossein Fatemi; Kimberly A. Aldinger; Paul Ashwood; Margaret L. Bauman; Charles D. Blaha; Gene J. Blatt; Abha Chauhan; Ved Chauhan; Stephen R. Dager; Price E. Dickson; Annette M. Estes; Dan Goldowitz; et al. (The Cerebellum, 2012)

Promoter variants in the MSMB gene associated with prostate cancer regulate MSMB/NCOA4 fusion transcripts - Hong Lou; Hongchuan Li; Meredith Yeager; Kate Im; Bert Gold; Thomas D. Schneider; Joseph F. Fraumeni; Stephen J. Chanock; Stephen K. Anderson; Michael Dean (Human Genetics, 2012)

Specific protease activity indicates the degree of Pseudomonas aeruginosa infection in chronic infected wounds - D. Wildeboer; K. E. Hill; F. Jeganathan; D. W. Williams; A. D. Riddell; P. E. Price; D. W. Thomas; P. Stephens; R. A. Abuknesha; R. G. Price (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Pinyon pine (Pinus edulis) mortality and response to water addition across a three million year substrate age gradient in northern Arizona, USA - Christopher E. Looney; Benjamin W. Sullivan; Thomas E. Kolb; Jeffrey M. Kane; Stephen C. Hart (Plant and Soil, 2012)

Decomposing the mid‐Holocene Tsuga decline in eastern North America - Robert K. Booth; Simon Brewer; Maarten Blaauw; Thomas A. Minckley; Stephen T. Jackson (Ecology, 2012)
The mid‐Holocene decline of Tsuga canadensis (hereafter Tsuga ) populations across eastern North America is widely perceived as a synchronous event, driven by pests/pathogens, rapid climate change, or both. Pattern identification and causal attribution are hampered by low stratigraphic density of pollen‐sampling and radiometric dates at most sites, and by absence of highly resolved, paired pollen and paleoclimate records from single sediment cores, where chronological order of climatic and vegetational changes can be assessed. We present an intensely sampled (contiguous 1‐cm intervals) record of pollen and water table depth (inferred from testate amoebae) from a single core spanning the Tsuga decline at Irwin Smith Bog in Lower Michigan, with high‐precision chronology. We also present an intensively sampled pollen record from Tower Lake in Upper Michigan. Both sites show high‐magnitude fluctuations in Tsuga pollen percentages during the pre‐decline maximum. The terminal decline is dated at both sites ca. 5000 cal yr BP, some 400 years later than estimates from other sites and data compilations. The terminal Tsuga decline was evidently heterochronous across its range. A transient decline ca. 5350 cal yr BP at both sites may correspond to the terminal decline at other sites in eastern North America. At Irwin Smith Bog, the terminal Tsuga decline preceded an abrupt and persistent decline in water table depths by ∼200 years, suggesting the decline was not directly driven by abrupt climate change. The Tsuga decline may best be viewed as comprising at least three phases: a long‐duration pre‐decline maximum with high‐magnitude and high‐frequency fluctuations, followed by a terminal decline at individual sites, followed in turn by two millennia of persistently low Tsuga populations. These phases may not be causally linked, and may represent dynamics taking place at multiple temporal and spatial scales. Further progress toward understanding the phenomenon requires an expanded network of high‐resolution pollen and paleoclimate chronologies.

Early life sun exposure, vitamin D-related gene variants, and risk of non-Hodgkin lymphoma - Jennifer L. Kelly; Matthew T. Drake; Zachary S. Fredericksen; Yan W. Asmann; Mark Liebow; Tait D. Shanafelt; Andrew L. Feldman; Stephen M. Ansell; William R. Macon; Megan M. Herr; Alice H. Wang; Grzegorz S. Nowakowski; et al. (Cancer Causes & Control, 2012)

Leadership, social learning, and the maintenance (or collapse) of migratory populations - William F. Fagan; Robert Stephen Cantrell; Chris Cosner; Thomas Mueller; Andrew E. Noble (Theoretical Ecology, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Matrix population models from 20 studies of perennial plant populations - Martha M. Ellis; Jennifer L. Williams; Peter Lesica; Timothy J. Bell; Paulette Bierzychudek; Marlin Bowles; Elizabeth E. Crone; Daniel F. Doak; Johan Ehrlén; Albertine Ellis-Adam; Kathryn McEachern; Rengaian Ganesan; et al. (Ecology, 2012)
Demographic transition matrices are among the most commonly applied population models for both basic and applied ecological research. The relatively simple framework of these models and simple, easily interpretable summary statistics they produce have prompted the wide use of these models across an exceptionally broad range of taxa. Here, we provide annual transition matrices and observed stage structures/population sizes for 20 perennial plant species which have been the focal species for long‐term demographic monitoring. These data were assembled as part of the “Testing Matrix Models” working group through the National Center for Ecological Analysis and Synthesis (NCEAS). The data represent 82 populations with >460 total population‐years of observations. It is our hope that making these data available will help promote and improve our ability to monitor and understand plant population dynamics. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

Soil-mediated local adaptation alters seedling survival and performance - David Solance Smith; Jennifer A. Schweitzer; Philip Turk; Joseph K. Bailey; Stephen C. Hart; Stephen M. Shuster; Thomas G. Whitham (Plant and Soil, 2012)

Fine mapping of 14q24.1 breast cancer susceptibility locus - Phoebe Lee; Yi-Ping Fu; Jonine D. Figueroa; Ludmila Prokunina-Olsson; Jesus Gonzalez-Bosquet; Peter Kraft; Zhaoming Wang; Kevin B. Jacobs; Meredith Yeager; Marie-Josèphe Horner; Susan E. Hankinson; Amy Hutchinson; et al. (Human Genetics, 2012)

Familial renal cancer as an indicator of hereditary leiomyomatosis and renal cell cancer syndrome - Victoria M. Raymond; Casey M. Herron; Thomas J. Giordano; Stephen B. Gruber (Familial Cancer, 2012)

Aspergillus oryzae NRRL 35191 from coffee, a non-toxigenic endophyte with the ability to synthesize kojic acid - Fabio C. Chaves; Thomas J. Gianfagna; Madhu Aneja; Francisco Posada; Stephen W. Peterson; Fernando E. Vega (Mycological Progress, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Spatially explicit capture–recapture methods to estimate minke whale density from data collected at bottom-mounted hydrophones - Tiago A. Marques; Len Thomas; Stephen W. Martin; David K. Mellinger; Susan Jarvis; Ronald P. Morrissey; Carroll-Anne Ciminello; Nancy DiMarzio (Journal of Ornithology, 2012)

Social organization and genetic structure: insights from codistributed bat populations - STEPHEN J. ROSSITER; AKBAR ZUBAID; ADURA MOHD‐ADNAN; MATTHEW J. STRUEBIG; THOMAS H. KUNZ; SUCHARITA GOPAL; ERIC J. PETIT; TIGGA KINGSTON (Molecular Ecology, 2012)
The impact of ecology and social organization on genetic structure at landscape spatial scales, where gene dynamics shape evolution as well as determine susceptibility to habitat fragmentation, is poorly understood. Attempts to assess these effects must take into account the potentially confounding effects of history. We used microsatellites to compare genetic structure in seven bat species with contrasting patterns of roosting ecology and social organization, all of which are codistributed in an ancient forest habitat that has been exceptionally buffered from radical habitat shifts. Over one thousand individuals were captured at foraging sites and genotyped at polymorphic microsatellite loci. Analyses of spatially explicit genotype data revealed interspecies differences in the extent of movement and gene flow and genetic structure across continuous intact forest. Highest positive genetic structure was observed in tree‐roosting taxa that roost either alone or in small groups. By comparison, a complete absence of genetic autocorrelation was noted in the cave‐roosting colonial species across the study area. Our results thus reveal measurable interspecies differences in the natural limits of gene flow in an unmodified habitat, which we attribute to contrasting roosting ecology and social organization. The consequences of ecology and behaviour for gene flow have important implications for conservation. In particular, tree‐roosting species characterized by lower vagility and thus gene flow will be disproportionally impacted by landscape‐scale forest clearance and habitat fragmentation, which are prevalent in the study region. Our method also highlights the usefulness of rapid sampling of foraging bats for assaying genetic structure, particularly where roosting sites are not always known.

Massive dominance of Epsilonproteobacteria in formation waters from a Canadian oil sands reservoir containing severely biodegraded oil - Casey R. J. Hubert; Thomas B. P. Oldenburg; Milovan Fustic; Neil D. Gray; Stephen R. Larter; Kevin Penn; Arlene K. Rowan; Rekha Seshadri; Angela Sherry; Richard Swainsbury; Gerrit Voordouw; Johanna K. Voordouw; et al. (Environmental Microbiology, 2012)
Summary The subsurface microbiology of an Athabasca oil sands reservoir in western Canada containing severely biodegraded oil was investigated by combining 16S rRNA gene‐ and polar lipid‐based analyses of reservoir formation water with geochemical analyses of the crude oil and formation water. Biomass was filtered from formation water, DNA was extracted using two different methods, and 16S rRNA gene fragments were amplified with several different primer pairs prior to cloning and sequencing or community fingerprinting by denaturing gradient gel electrophoresis (DGGE). Similar results were obtained irrespective of the DNA extraction method or primers used. Archaeal libraries were dominated by Methanomicrobiales (410 of 414 total sequences formed a dominant phylotype affiliated with a Methanoregula sp.), consistent with the proposed dominant role of CO 2 ‐reducing methanogens in crude oil biodegradation. In two bacterial 16S rRNA clone libraries generated with different primer pairs, > 99% and 100% of the sequences were affiliated with Epsilonproteobacteria ( n = 382 and 72 total clones respectively). This massive dominance of Epsilonproteobacteria sequences was again obtained in a third library (99% of sequences; n = 96 clones) using a third universal bacterial primer pair (inosine‐341f and 1492r). Sequencing of bands from DGGE profiles and intact polar lipid analyses were in accordance with the bacterial clone library results. Epsilonproteobacterial OTUs were affiliated with Sulfuricurvum , Arcobacter and Sulfurospirillum spp. detected in other oil field habitats. The dominant organism revealed by the bacterial libraries (87% of all sequences) is a close relative of Sulfuricurvum kujiense – an organism capable of oxidizing reduced sulfur compounds in crude oil. Geochemical analysis of organic extracts from bitumen at different reservoir depths down to the oil water transition zone of these oil sands indicated active biodegradation of dibenzothiophenes, and stable sulfur isotope ratios for elemental sulfur and sulfate in formation waters were indicative of anaerobic oxidation of sulfur compounds. Microbial desulfurization of crude oil may be an important metabolism for Epsilonproteobacteria indigenous to oil reservoirs with elevated sulfur content and may explain their prevalence in formation waters from highly biodegraded petroleum systems.

Multi‐decadal drought and amplified moisture variability drove rapid forest community change in a humid region - Robert K. Booth; Stephen T. Jackson; Valerie A. Sousa; Maura E. Sullivan; Thomas A. Minckley; Michael J. Clifford (Ecology, 2012)
Climate variability, particularly the frequency of extreme events, is likely to increase in the coming decades, with poorly understood consequences for terrestrial ecosystems. Hydroclimatic variations of the Medieval Climate Anomaly (MCA) provide a setting for studying ecological responses to recent climate variability at magnitudes and timescales comparable to expectations of coming centuries. We examined forest response to the MCA in the humid western Great Lakes region of North America, using proxy records of vegetation, fire, and hydroclimate. Multi‐decadal moisture variability during the MCA was associated with a widespread, episodic decline in Fagus grandifolia (beech) populations. Spatial patterns of drought and forest changes were coherent, with beech declining only in areas where proxy‐climate records indicate that severe MCA droughts occurred. The occurrence of widespread, drought‐induced ecological changes in the Great Lakes region indicates that ecosystems in humid regions are vulnerable to rapid changes in drought magnitude and frequency.

Diet and the risk of head and neck cancer: a pooled analysis in the INHANCE consortium - Shu-Chun Chuang; Mazda Jenab; Julia E. Heck; Cristina Bosetti; Renato Talamini; Keitaro Matsuo; Xavier Castellsague; Silvia Franceschi; Rolando Herrero; Deborah M. Winn; Carlo La Vecchia; Hal Morgenstern; et al. (Cancer Causes & Control, 2012)

Comparative sequence analysis of VRN1 alleles of Lolium perenne with the co-linear regions in barley, wheat, and rice - Torben Asp; Stephen Byrne; Heidrun Gundlach; Rémy Bruggmann; Klaus F. X. Mayer; Jeppe R. Andersen; Mingliang Xu; Morten Greve; Ingo Lenk; Thomas Lübberstedt (Molecular Genetics and Genomics, 2011)

Maximal voluntary contraction force, SR function and glycogen resynthesis during the first 72 h after a high-level competitive soccer game - Peter Krustrup; Niels Ørtenblad; Joachim Nielsen; Lars Nybo; Thomas P. Gunnarsson; F. Marcello Iaia; Klavs Madsen; Francis Stephens; Paul Greenhaff; Jens Bangsbo (European Journal of Applied Physiology, 2011)

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

The Changing Face of Arctic Snow Cover: A Synthesis of Observed and Projected Changes - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Roger G. Barry; Olga N. Bulygina; Richard L. H. Essery; D. M. Frolov; Vladimir N. Golubev; Thomas C. Grenfell; et al. (Ambio, 2011)

Genetic variation in productivity of foundation riparian species at the edge of their distribution: implications for restoration and assisted migration in a warming climate - Kevin C. Grady; Sharon M. Ferrier; Thomas E. Kolb; Stephen C. Hart; Gerard J. Allan; Thomas G. Whitham (Global Change Biology, 2011)
We examined the hypothesis that genotypic variation among populations of commonly co‐occurring phreatophytic trees ( P opulus fremontii , S alix gooddingii ) and the shrub ( S alix exigua ) regulates aboveground net primary productivity ( ANPP ) at a hot site at the edge of the species’ distribution. We used a provenance trial in which replicated genotypes from populations varying in mean annual temperature were transplanted to a common garden adjacent to the L ower C olorado R iver in southeastern C alifornia. The garden environment represented an extreme maximum temperature for the study species. Four major findings emerged: (1) Genotypic variation in ANPP was significant for all species with broad‐sense heritability ( H 2 ) across populations of 0.11, 0.13, and 0.10 for P . fremontii , S . gooddingii , and S . exigua , respectively, and within‐population H 2 ranging from 0.00 to 0.25, 0.00 to 0.44, and 0.02 to 0.21, respectively. (2) Population ANPP decreased linearly as mean annual maximum temperature ( MAMT ) transfer distance increased for both P . fremontii ( r 2 = 0.64) and S . gooddingii ( r 2 = 0.37), whereas it did not change for S . exigua ; (3) Populations with similar MAMT to that of the common garden were 1.5 and 1.2 times more productive than populations with 5.0 °C MAMT transfer distances for P . fremontii and S . gooddingii , respectively; and (4) Variation in regression slopes among species for the relationship between ANPP and MAMT indicate species‐specific responses to temperature. As these plant species characterize a threatened habitat type and support a diverse community that includes endangered species, ecosystem restoration programs should consider using both local genotypes and productive genotypes from warmer environments to maximize productivity of riparian ecosystems in the face of global climate change.

Interannual pteropod variability in sediment traps deployed above and below the aragonite saturation horizon in the Sub-Antarctic Southern Ocean - Donna Roberts; William R. Howard; Andrew D. Moy; Jason L. Roberts; Thomas W. Trull; Stephen G. Bray; Russell R. Hopcroft (Polar Biology, 2011)

Does a bout of strength training affect 2,000 m rowing ergometer performance and rowing-specific maximal power 24 h later? - Thomas I. Gee; Duncan N. French; Glyn Howatson; Stephen J. Payton; Nicolas J. Berger; Kevin G. Thompson (European Journal of Applied Physiology, 2011)

Reconnecting to the Biosphere - Carl Folke; Åsa Jansson; Johan Rockström; Per Olsson; Stephen R. Carpenter; F. Stuart Chapin; Anne-Sophie Crépin; Gretchen Daily; Kjell Danell; Jonas Ebbesson; Thomas Elmqvist; Victor Galaz; et al. (Ambio, 2011)

Phylogenetic and Preliminary Phenotypic Analysis of Yeast PAQR Receptors: Potential Antifungal Targets - Nancy Y. Villa; Patricia Moussatche; Stephen G. Chamberlin; Anuj Kumar; Thomas J. Lyons (Journal of Molecular Evolution, 2011)

Extremes in rapid cellular morphogenesis: post-transcriptional regulation of spermatogenesis in Marsilea vestita - Stephen M. Wolniak; Corine M. van der Weele; Faten Deeb; Thomas Boothby; Vincent P. Klink (Protoplasma, 2011)

Nitrogen dynamics in Lake Okeechobee: forms, functions, and changes - R. Thomas James; Wayne S. Gardner; Mark J. McCarthy; Stephen A. Carini (Hydrobiologia, 2011)

The association of diabetes mellitus and high-grade prostate cancer in a multiethnic biopsy series - Daniel M. Moreira; Tiffany Anderson; Leah Gerber; Jean-Alfred Thomas; Lionel L. Bañez; Madeline G. McKeever; Cathrine Hoyo; Delores Grant; Jayakrishnan Jayachandran; Stephen J. Freedland (Cancer Causes & Control, 2011)

Fine mapping the KLK3 locus on chromosome 19q13.33 associated with prostate cancer susceptibility and PSA levels - Hemang Parikh; Zhaoming Wang; Kerry A. Pettigrew; Jinping Jia; Sarah Daugherty; Meredith Yeager; Kevin B. Jacobs; Amy Hutchinson; Laura Burdett; Michael Cullen; Liqun Qi; Joseph Boland; et al. (Human Genetics, 2011)

Hydrochemical Impacts of Limestone Rock Mining - Ghinwa M. Naja; Rosanna Rivero; Stephen E. Davis; Thomas Van Lent (Water, Air, & Soil Pollution, 2011)

Changes in gravity rapidly alter the magnitude and direction of a cellular calcium current - Mari L. Salmi; Aeraj ul Haque; Thomas J. Bushart; Stephen C. Stout; Stanley J. Roux; D. Marshall Porterfield (Planta, 2011)

Nrf2: control of sensitivity to carcinogens - Stephen L. Slocum; Thomas W. Kensler (Archives of Toxicology, 2011)

The Role of the Everglades Mangrove Ecotone Region (EMER) in Regulating Nutrient Cycling and Wetland Productivity in South Florida - Victor H. Rivera-Monroy; Robert R. Twilley; Stephen E. Davis; Daniel L. Childers; Marc Simard; Randolph Chambers; Rudolf Jaffe; Joseph N. Boyer; David T. Rudnick; Keqi Zhang; Edward Castañeda-Moya; Sharon M. L. Ewe; et al. (Critical Reviews in Environmental Science and Technology, 2011)

Erratum: Design and Analysis of Line Transect Surveys for Primates - Stephen T. Buckland; Andrew J. Plumptre; Len Thomas; Eric A. Rexstad (International Journal of Primatology, 2011)

Erratum: Line Transect Sampling of Primates: Can Animal-to-Observer Distance Methods Work? - Stephen T. Buckland; Andrew J. Plumptre; Len Thomas; Eric A. Rexstad (International Journal of Primatology, 2011)

How can soil monitoring networks be used to improve predictions of organic carbon pool dynamics and CO2 fluxes in agricultural soils? - Bas van Wesemael; Keith Paustian; Olof Andrén; Carlos E. P. Cerri; Mike Dodd; Jorge Etchevers; Esther Goidts; Peter Grace; Thomas Kätterer; Brian G. McConkey; Stephen Ogle; Genxing Pan; et al. (Plant and Soil, 2011)

Genome-wide analysis of copy number variants in age-related macular degeneration - Kacie J. Meyer; Lea K. Davis; Emily I. Schindler; John S. Beck; Danielle S. Rudd; A. Jason Grundstad; Todd E. Scheetz; Terry A. Braun; John H. Fingert; Wallace L. Alward; Young H. Kwon; James C. Folk; et al. (Human Genetics, 2011)

Sensitization of human bladder tumor cells to TNF-related apoptosis-inducing ligand (TRAIL)-induced apoptosis with a small molecule IAP antagonist - Thomas S. Griffith; Tamara A. Kucaba; Michael A. O’Donnell; Jennifer Burns; Christopher Benetatos; Mark A. McKinlay; Stephen Condon; Srinivas Chunduru (Apoptosis, 2011)

Comparative analysis of angiogenic gene expression in normal and impaired wound healing in diabetic mice: effects of extracorporeal shock wave therapy - Stephen R. Zins; Mihret F. Amare; Douglas K. Tadaki; Eric. A. Elster; Thomas A. Davis (Angiogenesis, 2010)

Design and Analysis of Line Transect Surveys for Primates - Stephen T. Buckland; Andrew J. Plumptre; Len Thomas; Eric A. Rexstad (International Journal of Primatology, 2010)

Spatial distribution of lead concentrations in urban surface soils of New Orleans, Louisiana USA - Michael T. Abel; Burton Suedel; Steven M. Presley; Thomas R. Rainwater; Galen P. Austin; Stephen B. Cox; Les N. McDaniel; Richard Rigdon; Timothy Goebel; Richard Zartman; Blair D. Leftwich; Todd A. Anderson; et al. (Environmental Geochemistry and Health, 2010)

Spectroscopic insights into axial ligation and active-site H-bonding in substrate-bound human heme oxygenase-2 - Jessica D. Gardner; Li Yi; Stephen W. Ragsdale; Thomas C. Brunold (JBIC Journal of Biological Inorganic Chemistry, 2010)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Deep sequencing reveals exceptional diversity and modes of transmission for bacterial sponge symbionts - Nicole S. Webster; Michael W. Taylor; Faris Behnam; Sebastian Lücker; Thomas Rattei; Stephen Whalan; Matthias Horn; Michael Wagner (Environmental Microbiology, 2010)
Summary Marine sponges contain complex bacterial communities of considerable ecological and biotechnological importance, with many of these organisms postulated to be specific to sponge hosts. Testing this hypothesis in light of the recent discovery of the rare microbial biosphere, we investigated three Australian sponges by massively parallel 16S rRNA gene tag pyrosequencing. Here we show bacterial diversity that is unparalleled in an invertebrate host, with more than 250 000 sponge‐derived sequence tags being assigned to 23 bacterial phyla and revealing up to 2996 operational taxonomic units (95% sequence similarity) per sponge species. Of the 33 previously described ‘sponge‐specific’ clusters that were detected in this study, 48% were found exclusively in adults and larvae – implying vertical transmission of these groups. The remaining taxa, including ‘ Poribacteria ’, were also found at very low abundance among the 135 000 tags retrieved from surrounding seawater. Thus, members of the rare seawater biosphere may serve as seed organisms for widely occurring symbiont populations in sponges and their host association might have evolved much more recently than previously thought.

Genetic effective size, Ne, tracks density in a small freshwater cyprinid, Pecos bluntnose shiner (Notropis simus pecosensis) - MEGAN J. OSBORNE; STEPHEN R. DAVENPORT; CHRISTOPHER W. HOAGSTROM; THOMAS F. TURNER (Molecular Ecology, 2010)

Soil nitrogen availability varies with plant genetics across diverse river drainages - Dylan G. Fischer; Stephen C. Hart; Jennifer A. Schweitzer; Paul C. Selmants; Thomas G. Whitham (Plant and Soil, 2010)

Line Transect Sampling of Primates: Can Animal-to-Observer Distance Methods Work? - Stephen T. Buckland; Andrew J. Plumptre; Len Thomas; Eric A. Rexstad (International Journal of Primatology, 2010)

Land plant evolution and weathering rate changes in the Devonian - Thomas J. Algeo; Stephen E. Scheckler (Journal of Earth Science, 2010)

Human papillomavirus is not associated with colorectal cancer in a large international study - Michele C. Gornick; Xavier Castellsague; Gloria Sanchez; Thomas J. Giordano; Michelle Vinco; Joel K. Greenson; Gabriel Capella; Leon Raskin; Gad Rennert; Stephen B. Gruber; Victor Moreno (Cancer Causes & Control, 2010)

Relationship between cystic fibrosis respiratory tract bacterial communities and age, genotype, antibiotics and Pseudomonas aeruginosa - Vanja Klepac‐Ceraj; Katherine P. Lemon; Thomas R. Martin; Martin Allgaier; Steven W. Kembel; Alixandra A. Knapp; Stephen Lory; Eoin L. Brodie; Susan V. Lynch; Brendan J. M. Bohannan; Jessica L. Green; Brian A. Maurer; et al. (Environmental Microbiology, 2010)
Summary Polymicrobial bronchopulmonary infections in cystic fibrosis (CF) cause progressive lung damage and death. Although the arrival of Pseudomonas aeruginosa often heralds a more rapid rate of pulmonary decline, there is significant inter‐individual variation in the rate of decline, the causes of which remain poorly understood. By coupling culture‐independent methods with ecological analyses, we discovered correlations between bacterial community profiles and clinical disease markers in respiratory tracts of 45 children with CF. Bacterial community complexity was inversely correlated with patient age, presence of P. aeruginosa and antibiotic exposure, and was related to CF genotype. Strikingly, bacterial communities lacking P. aeruginosa were much more similar to each other than were those containing P. aeruginosa , regardless of antibiotic exposure. This suggests that community composition might be a better predictor of disease progression than the presence of P. aeruginosa alone and deserves further study.

Effects of Nutrient Pre-Exposure on Atrazine Toxicity to Vallisneria americana Michx. (Wild Celery) - Darrin D. Dantin; Ronald G. Boustany; Michael A. Lewis; Stephen J. Jordan; Rebecca F. Moss; Thomas C. Michot (Archives of Environmental Contamination and Toxicology, 2010)

A comprehensive resequence analysis of the KLK15–KLK3–KLK2 locus on chromosome 19q13.33 - Hemang Parikh; Zuoming Deng; Meredith Yeager; Joseph Boland; Casey Matthews; Jinping Jia; Irene Collins; Ariel White; Laura Burdett; Amy Hutchinson; Liqun Qi; Jennifer A. Bacior; et al. (Human Genetics, 2010)

A retrospective evaluation of shortened-duration oral N-acetylcysteine for the treatment of acetaminophen poisoning - David P. Betten; Elizabeth E. Burner; Stephen C. Thomas; Christian Tomaszewski; Richard F. Clark (Journal of Medical Toxicology, 2009)

Comprehensive resequence analysis of a 97 kb region of chromosome 10q11.2 containing the MSMB gene associated with prostate cancer - Meredith Yeager; Zuoming Deng; Joseph Boland; Casey Matthews; Jennifer Bacior; Victor Lonsberry; Amy Hutchinson; Laura A. Burdett; Liqun Qi; Kevin B. Jacobs; Jesus Gonzalez-Bosquet; Sonja I. Berndt; et al. (Human Genetics, 2009)

Papyriferic Acid, An Antifeedant Triterpene From Birch Trees, Inhibits Succinate Dehydrogenase From Liver Mitochondria - Stuart McLean; Stephen M. Richards; Siow-Leng Cover; Sue Brandon; Noel W. Davies; John P. Bryant; Thomas P. Clausen (Journal of Chemical Ecology, 2009)

Changes in the relative reinforcing effects of cigarette smoking as a function of initial abstinence - Jin H. Yoon; Stephen T. Higgins; Matthew P. Bradstreet; Gary J. Badger; Colleen S. Thomas (Psychopharmacology, 2009)

The Science of USP 1 and 2 Dissolution: Present Challenges and Future Relevance - Vivian Gray; Gregg Kelly; Min Xia; Chris Butler; Saji Thomas; Stephen Mayock (Pharmaceutical Research, 2009)

Generation of large droplet aerosols within microbiological containment using a novel flow-focussing technique - Richard J. Thomas; Daniel Webber; William Sellors; Aaron Collinge; Andrew Frost; Anthony J. Stagg; Stephen C. Bailey; Pramukh N. Jayasekera; Rosa R. Taylor; Steve Eley; Richard W. Titball (Aerobiologia, 2009)

Nitrate removal in stream ecosystems measured by 15N addition experiments: Total uptake - Robert O. Hall; Jennifer L. Tank; Daniel J. Sobota; Patrick J. Mulholland; Jonathan M. O'Brien; Walter K. Dodds; Jackson R. Webster; H. Maurice Valett; Geoffrey C. Poole; Bruce J. Peterson; Judy L. Meyer; William H. McDowell; et al. (Limnology and Oceanography, 2009)
We measured uptake length of 15 NO 3 − in 72 streams in eight regions across the United States and Puerto Rico to develop quantitative predictive models on controls of NO 3 − uptake length. As part of the Lotic Intersite Nitrogen eXperiment II project, we chose nine streams in each region corresponding to natural (reference), suburban‐urban, and agricultural land uses. Study streams spanned a range of human land use to maximize variation in NO 3 − concentration, geomorphology, and metabolism. We tested a causal model predicting controls on NO 3 − uptake length using structural equation modeling. The model included concomitant measurements of ecosystem metabolism, hydraulic parameters, and nitrogen concentration. We compared this structural equation model to multiple regression models which included additional biotic, catchment, and riparian variables. The structural equation model explained 79% of the variation in log uptake length ( S Wtot ). Uptake length increased with specific discharge ( Q/w ) and increasing NO 3 − concentrations, showing a loss in removal efficiency in streams with high NO 3 − concentration. Uptake lengths shortened with increasing gross primary production, suggesting autotrophic assimilation dominated NO 3 − removal. The fraction of catchment area as agriculture and suburban‐urban land use weakly predicted NO 3 − uptake in bivariate regression, and did improve prediction in a set of multiple regression models. Adding land use to the structural equation model showed that land use indirectly affected NO 3 − uptake lengths via directly increasing both gross primary production and NO 3 − concentration. Gross primary production shortened S Wtot , while increasing NO 3 − lengthened S Wtot resulting in no net effect of land use on NO 3 − removal.

Modification of gibberellin signalling (metabolism & signal transduction) in sugar beet: analysis of potential targets for crop improvement - Effie Mutasa-Gottgens; Aiming Qi; Ann Mathews; Stephen Thomas; Andrew Phillips; Peter Hedden (Transgenic Research, 2009)

Angiogenic response to extracorporeal shock wave treatment in murine skin isografts - Alexander Stojadinovic; Eric A. Elster; Khairul Anam; Douglas Tadaki; Mihret Amare; Stephen Zins; Thomas A. Davis (Angiogenesis, 2008)

The complete genome sequence of Moorella thermoacetica (f. Clostridium thermoaceticum ) - Elizabeth Pierce; Gary Xie; Ravi D. Barabote; Elizabeth Saunders; Cliff S. Han; John C. Detter; Paul Richardson; Thomas S. Brettin; Amaresh Das; Lars G. Ljungdahl; Stephen W. Ragsdale (Environmental Microbiology, 2008)
Summary This paper describes the genome sequence of Moorella thermoacetica (f. Clostridium thermoaceticum ), which is the model acetogenic bacterium that has been widely used for elucidating the Wood–Ljungdahl pathway of CO and CO 2 fixation. This pathway, which is also known as the reductive acetyl‐CoA pathway, allows acetogenic (often called homoacetogenic) bacteria to convert glucose stoichiometrically into 3 mol of acetate and to grow autotrophically using H 2 and CO as electron donors and CO 2 as an electron acceptor. Methanogenic archaea use this pathway in reverse to grow by converting acetate into methane and CO 2 . Acetogenic bacteria also couple the Wood–Ljungdahl pathway to a variety of other pathways to allow the metabolism of a wide variety of carbon sources and electron donors (sugars, carboxylic acids, alcohols and aromatic compounds) and electron acceptors (CO 2 , nitrate, nitrite, thiosulfate, dimethylsulfoxide and aromatic carboxyl groups). The genome consists of a single circular 2 628 784 bp chromosome encoding 2615 open reading frames (ORFs), which includes 2523 predicted protein‐encoding genes. Of these, 1834 genes (70.13%) have been assigned tentative functions, 665 (25.43%) matched genes of unknown function, and the remaining 24 (0.92%) had no database match. A total of 2384 (91.17%) of the ORFs in the M. thermoacetica genome can be grouped in orthologue clusters. This first genome sequence of an acetogenic bacterium provides important information related to how acetogens engage their extreme metabolic diversity by switching among different carbon substrates and electron donors/acceptors and how they conserve energy by anaerobic respiration. Our genome analysis indicates that the key genetic trait for homoacetogenesis is the core acs gene cluster of the Wood–Ljungdahl pathway.

Comprehensive resequence analysis of a 136 kb region of human chromosome 8q24 associated with prostate and colon cancers - Meredith Yeager; Nianqing Xiao; Richard B. Hayes; Pascal Bouffard; Brian Desany; Laura Burdett; Nick Orr; Casey Matthews; Liqun Qi; Andrew Crenshaw; Zdenek Markovic; Karin M. Fredrikson; et al. (Human Genetics, 2008)

From Genes to Ecosystems: The Genetic Basis of Condensed Tannins and Their Role in Nutrient Regulation in a Populus Model System - Jennifer A. Schweitzer; Michael D. Madritch; Joseph K. Bailey; Carri J. LeRoy; Dylan G. Fischer; Brian J. Rehill; Richard L. Lindroth; Ann E. Hagerman; Stuart C. Wooley; Stephen C. Hart; Thomas G. Whitham (Ecosystems, 2008)

Spatially-averaged flow statistics within a canopy of large bluff bodies: Results from direct numerical simulations - Omduth Coceal; T. Glyn Thomas; Stephen E. Belcher (Acta Geophysica, 2008)

A general framework for the distance–decay of similarity in ecological communities - Hélène Morlon; George Chuyong; Richard Condit; Stephen Hubbell; David Kenfack; Duncan Thomas; Renato Valencia; Jessica L. Green (Ecology Letters, 2008)
Species spatial turnover, or β ‐diversity, induces a decay of community similarity with geographic distance known as the distance–decay relationship. Although this relationship is central to biodiversity and biogeography, its theoretical underpinnings remain poorly understood. Here, we develop a general framework to describe how the distance–decay relationship is influenced by population aggregation and the landscape‐scale species‐abundance distribution. We utilize this general framework and data from three tropical forests to show that rare species have a weak influence on distance–decay curves, and that overall similarity and rates of decay are primarily influenced by species abundances and population aggregation respectively. We illustrate the utility of the framework by deriving an exact analytical expression of the distance–decay relationship when population aggregation is characterized by the Poisson Cluster Process. Our study provides a foundation for understanding the distance–decay relationship, and for predicting and testing patterns of beta‐diversity under competing theories in ecology.

Effects of haloperidol on the behavioral, subjective, cognitive, motor, and neuroendocrine effects of Δ-9-tetrahydrocannabinol in humans - Deepak Cyril D’Souza; Gabriel Braley; Rebecca Blaise; Michael Vendetti; Stephen Oliver; Brian Pittman; Mohini Ranganathan; Savita Bhakta; Zoran Zimolo; Thomas Cooper; Edward Perry (Psychopharmacology, 2008)

Interactions of lipids with aquaporin-0 and other membrane proteins - Richard K. Hite; Tamir Gonen; Stephen C. Harrison; Thomas Walz (Pflügers Archiv - European Journal of Physiology, 2008)

Evaluating the post-release efficacy of invasive plant biocontrol by insects: a comprehensive approach - Walter P. Carson; Stephen M. Hovick; Anthony J. Baumert; Daniel E. Bunker; Thomas H. Pendergast (Arthropod-Plant Interactions, 2008)

SWAT.nz: New-Zeland-based “Sand Waves and Turbulence” experimental programme - Stephen E. Coleman; Vladimir I. Nikora; Bruce W. Melville; Derek G. Goring; Thomas M. Dougal Clunie; Heide Friedrich (Acta Geophysica, 2008)

Genetic variants in the 8q24 locus and risk of testicular germ cell tumors - Michael B. Cook; Barry I. Graubard; Sabah M. Quraishi; Meredith Yeager; Stephen J. Chanock; Andrew Crenshaw; Ralph L. Erickson; Mark V. Rubertone; Gilles Thomas; Katherine A. McGlynn (Human Genetics, 2008)

Common polymorphisms of ALOX5 and ALOX5AP and risk of coronary artery disease - Themistocles L. Assimes; Joshua W. Knowles; James R. Priest; Analabha Basu; Kelly A. Volcik; Audrey Southwick; Holly K. Tabor; Jaana Hartiala; Hooman Allayee; Megan L. Grove; Raymond Tabibiazar; Stephen Sidney; et al. (Human Genetics, 2008)

Computational studies of Fe(III) binding to bryostatins, bryostatin analogs, siderophores and marine natural products: arguments for ferric complexes in medicinal applications - Thomas J. Manning; Jessica Thomas; Stephen Osiro; Justin Smith; Giso Abadi; Lyn Noble; Dennis Phillips (Natural Product Research, 2008)

Second Generation Biofuels: High-Efficiency Microalgae for Biodiesel Production - Peer M. Schenk; Skye R. Thomas-Hall; Evan Stephens; Ute C. Marx; Jan H. Mussgnug; Clemens Posten; Olaf Kruse; Ben Hankamer (BioEnergy Research, 2008)

Ecological stability in a changing world? Reassessment of the palaeoenvironmental history of Cuatrociénegas, Mexico - Thomas A. Minckley; Stephen T. Jackson (Journal of Biogeography, 2008)
Previous work on the palaeoenvironmental history of Cuatrociénegas, Coahuila, Mexico, suggests that the local environments of the basin have been relatively stable since the last glacial period. Reassessment of the palaeoenvironmental record from Cuatrociénegas, combined with the analysis of a glacial‐age packrat midden (∼ 16,900 cal yr bp ), shows that this region has experienced substantial climatic and ecological changes during the Late Quaternary. Woodlands occurred near the valley floor until ca. 11,000 years ago, migrating upslope as climate warmed. The apparent lack of change in the flora of the basin floor may be attributable to high soil salinity. This edaphic control led to earlier interpretations that the region was environmentally stable.

Spatial Variability of Flow Statistics within Regular Building Arrays - Omduth Coceal; T. Glyn Thomas; Stephen E. Belcher (Boundary-Layer Meteorology, 2007)

Germ-line DNA copy number variation frequencies in a large North American population - George Zogopoulos; Kevin C. H. Ha; Faisal Naqib; Sara Moore; Hyeja Kim; Alexandre Montpetit; Frederick Robidoux; Philippe Laflamme; Michelle Cotterchio; Celia Greenwood; Stephen W. Scherer; Brent Zanke; et al. (Human Genetics, 2007)

A Dynamic Model for Determining the Temporal Distribution of Environmental Burden - Stephen H. Levine; Thomas P. Gloria; Eliahu Romanoff (Journal of Industrial Ecology, 2007)
In an article on the role of temporal information in life‐cycle assessment in this journal, Field and colleagues argued that frequently it is not the single product but the “fleet” (or cohort) of products that “is the appropriate unit of analysis,” and that in focusing on the fleet one “explicitly introduces the notion of time as a critical element of comparative life‐cycle assessments. …” Major transitions, such as replacement of one fleet of products by an alternative fleet, correspond to a system in a transient rather than steady state, and explicit consideration of time is central to transient analysis. One tool increasingly used as part of life‐cycle assessment, economic input‐output (EIO) analysis, at best deals with time in an implicit fashion. This article illustrates how the sequential interindustry model (SIM), a formulation of the EIOmodel that explicitly represents time, might be utilized in life‐cycle assessment. SIM introduces this temporal component by explicitly accounting for the time required by production activities and the resulting sequencing of the inputs. This can be thought of as engineering rather than accounting information. The data demands of such a model are not likely to be met at present or at any time in the near future. Even so, simulation methods and the use of so‐called synthetic data have a history of productive use in a number of fields, including the social sciences. SIM also utilizes the contribution of Joshi on the application of the EIO model to environmental impact and the inclusion of the use as well as the production phases of a product in EIO analysis. The possibility of accounting for discounting of future events, with its impact on decision making, is also briefly discussed.

Microsatellite mapping of adult-plant leaf rust resistance gene Lr22a in wheat - Colin W. Hiebert; Julian B. Thomas; Daryl J. Somers; Brent D. McCallum; Stephen L. Fox (Theoretical and Applied Genetics, 2007)

Microsatellite mapping of adult-plant leaf rust resistance gene Lr22a in wheat - Colin W. Hiebert; Julian B. Thomas; Daryl J. Somers; Brent D. McCallum; Stephen L. Fox (Theoretical and Applied Genetics, 2007)

3-Hydroxyglutaric acid is transported via the sodium-dependent dicarboxylate transporter NaDC3 - Franziska Stellmer; Britta Keyser; Birgitta C. Burckhardt; Hermann Koepsell; Thomas Streichert; Markus Glatzel; Sabrina Jabs; Joachim Thiem; Wilhelm Herdering; David M. Koeller; Stephen I. Goodman; Zoltan Lukacs; et al. (Journal of Molecular Medicine, 2007)

Season mediates herbivore effects on litter and soil microbial abundance and activity in a semi-arid woodland - Aimée T. Classen; Steven T. Overby; Stephen C. Hart; George W. Koch; Thomas G. Whitham (Plant and Soil, 2007)

TagSNP evaluation for the association of 42 inflammation loci and vascular disease: evidence of IL6, FGB, ALOX5, NFKBIA, and IL4R loci effects - Christopher S. Carlson; Patrick J. Heagerty; Alex S. Nord; David K. Pritchard; Jane Ranchalis; Joshua M. Boguch; Hangjun Duan; Thomas S. Hatsukami; Stephen M. Schwartz; Mark J. Rieder; Deborah A. Nickerson; Gail P. Jarvik (Human Genetics, 2007)

Molecular and genomic studies of IMMP2L and mutation screening in autism and Tourette syndrome - Erwin Petek; Thomas Schwarzbraun; Abdul Noor; Megha Patel; Kazuhiko Nakabayashi; Sanaa Choufani; Christian Windpassinger; Mara Stamenkovic; Mary M. Robertson; Harald N. Aschauer; Hugh M. D. Gurling; Peter M. Kroisel; et al. (Molecular Genetics and Genomics, 2007)

Family-based association study of matrix metalloproteinase-3 and -9 haplotypes with susceptibility to ischemic white matter injury - Myriam Fornage; Thomas H. Mosley; Clifford R. Jack; Mariza de Andrade; Sharon L. R. Kardia; Eric Boerwinkle; Stephen T. Turner (Human Genetics, 2007)

Bottom‐up forcing and the decline of Steller sea lions ( Eumetopias jubatus ) in Alaska: assessing the ocean climate hypothesis - ANDREW W. TRITES; ARTHUR J. MILLER; HERBERT D. G. MASCHNER; MICHAEL A. ALEXANDER; STEVEN J. BOGRAD; JOHN A. CALDER; ANTONIETTA CAPOTONDI; KENNETH O. COYLE; EMANUELE DI LORENZO; BRUCE P. FINNEY; EDWARD J. GREGR; CHESTER E. GROSCH; et al. (Fisheries Oceanography, 2007)
Declines of Steller sea lion ( Eumetopias jubatus ) populations in the Aleutian Islands and Gulf of Alaska could be a consequence of physical oceanographic changes associated with the 1976–77 climate regime shift. Changes in ocean climate are hypothesized to have affected the quantity, quality, and accessibility of prey, which in turn may have affected the rates of birth and death of sea lions. Recent studies of the spatial and temporal variations in the ocean climate system of the North Pacific support this hypothesis. Ocean climate changes appear to have created adaptive opportunities for various species that are preyed upon by Steller sea lions at mid‐trophic levels. The east–west asymmetry of the oceanic response to climate forcing after 1976–77 is consistent with both the temporal aspect (populations decreased after the late 1970s) and the spatial aspect of the decline (western, but not eastern, sea lion populations decreased). These broad‐scale climate variations appear to be modulated by regionally sensitive biogeographic structures along the Aleutian Islands and Gulf of Alaska, which include a transition point from coastal to open‐ocean conditions at Samalga Pass westward along the Aleutian Islands. These transition points delineate distinct clusterings of different combinations of prey species, which are in turn correlated with differential population sizes and trajectories of Steller sea lions. Archaeological records spanning 4000 yr further indicate that sea lion populations have experienced major shifts in abundance in the past. Shifts in ocean climate are the most parsimonious underlying explanation for the broad suite of ecosystem changes that have been observed in the North Pacific Ocean in recent decades.

Significant linkage to airway responsiveness on chromosome 12q24 in families of children with asthma in Costa Rica - Juan C. Celedón; Manuel E. Soto-Quiros; Lydiana Avila; Stephen L. Lake; Catherine Liang; Eduardo Fournier; Mitzi Spesny; Craig P. Hersh; Jody S. Sylvia; Thomas J. Hudson; Andrei Verner; Barbara J. Klanderman; et al. (Human Genetics, 2006)

Ezrin mediates growth and survival in Ewing’s sarcoma through the AKT/mTOR, but not the MAPK, signaling pathway - Kartik Krishnan; Ben Bruce; Stephen Hewitt; Dafydd Thomas; Chand Khanna; Lee J. Helman (Clinical & Experimental Metastasis, 2006)

Diurnal time-activity budgets of redheads (Aythya americana) wintering in seagrass beds and coastal ponds in Louisiana and Texas - Thomas C. Michot; Marc C. Woodin; Stephen E. Adair; E. Barry Moser (Hydrobiologia, 2006)

Taxa–area relationships for microbes: the unsampled and the unseen - Stephen Woodcock; Thomas P. Curtis; Ian M. Head; Mary Lunn; William T. Sloan (Ecology Letters, 2006)
The recent observation of a power–law relationship, S ∝ A z , between number of taxa, S , and area, A , for microbial eukaryotes and bacteria suggests that this is one of the few generic relationships in ecology, applicable to plants, animals and microbes. However, the rate of increase in the number of species with area varies from approximately the fourth ( z = 0.26) to as little as the 50th root ( z = 0.0019) in microbes. This is an enormous range for which no quantitative explanation has been proffered. We show by sampling from synthetic populations that the disparity between sample and community sizes in microbial community surveys means z can be considerably underestimated and accrual of rare taxa with increasing area will not be detectable. Significant microbial taxa–area relationships will only be observed when changes in community structure within samples correlate with area. Thus, the very low z values observed recently cannot be used as the sole evidence in support of any particular community theory of community assembly. More generally, this suggests that our search for patterns and laws in the microbial world will be profoundly influenced and, potentially distorted by the sample sizes that are typical of microbial community surveys.

An insect parasitoid carrying an ochratoxin producing fungus - Fernando E. Vega; Francisco Posada; Thomas J. Gianfagna; Fabio C. Chaves; Stephen W. Peterson (The Science of Nature, 2006)

Ambient monitoring and biomonitoring of workers exposed to N-methyl-2-pyrrolidone in an industrial facility - Michael Bader; Wolfgang Rosenberger; Thomas Rebe; Stephen A. Keener; Thomas H. Brock; Hans-Jürgen Hemmerling; Renate Wrbitzky (International Archives of Occupational and Environmental Health, 2006)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

Cell-type-specific pathways of neurotensin endocytosis - Cheryl Savdie; Stephen S. G. Ferguson; J.– P. Vincent; Alain Beaudet; Thomas Stroh (Cell and Tissue Research, 2006)

Quantifying the roles of immigration and chance in shaping prokaryote community structure - William T. Sloan; Mary Lunn; Stephen Woodcock; Ian M. Head; Sean Nee; Thomas P. Curtis (Environmental Microbiology, 2006)
Summary Naturally occurring populations of bacteria and archaea are vital to life on the earth and are of enormous practical significance in medicine, engineering and agriculture. However, the rules governing the formation of such communities are still poorly understood, and there is a need for a usable mathematical description of this process. Typically, microbial community structure is thought to be shaped mainly by deterministic factors such as competition and niche differentiation. Here we show, for a wide range of prokaryotic communities, that the relative abundance and frequency with which different taxa are observed in samples can be explained by a neutral community model (NCM). The NCM, which is a stochastic, birth–death immigration process, does not explicitly represent the deterministic factors and therefore cannot be a complete or literal description of community assembly. However, its success suggests that chance and immigration are important forces in shaping the patterns seen in prokaryotic communities.

A photoacoustic method for rapid assessment of temperature effects on photosynthesis - Stephen K. Herbert; Karl Y. Biel; Thomas C Vogelmann (Photosynthesis Research, 2006)

Assembling complex genotypes to resist Fusarium in wheat (Triticum aestivum L.) - Daryl J. Somers; Julian Thomas; Ron DePauw; Stephen Fox; Gavin Humphreys; George Fedak (Theoretical and Applied Genetics, 2005)

Improving Estimates of Nitrate Leaching for Quantifying New Zealand’s Indirect Nitrous Oxide Emissions - Stephen M. Thomas; Stewart F. Ledgard; Glyn S. Francis (Nutrient Cycling in Agroecosystems, 2005)

Bioanalytical Method Validation for Macromolecules in Support of Pharmacokinetic Studies - JoMarie Smolec; Binodh DeSilva; Wendell Smith; Russell Weiner; Marian Kelly; Ben Lee; Masood Khan; Richard Tacey; Howard Hill; Abbie Celniker; Vinod Shah; Ronald Bowsher; et al. (Pharmaceutical Research, 2005)

Folivory in Fruit Bats: Leaves Provide a Natural Source of Calicum - Suzanne L. Nelson; Thomas H. Kunz; Stephen R. Humphrey (Journal of Chemical Ecology, 2005)

The Seismic Project of the National Tsunami Hazard Mitigation Program - David H. Oppenheimer; Alex N. Bittenbinder; Barbara M. Bogaert; Raymond P. Buland; Lynn D. Dietz; Roger A. Hansen; Stephen D. Malone; Charles S. McCreery; Thomas J. Sokolowski; Paul M. Whitmore; Craig S. Weaver (Natural Hazards, 2005)

Novel human α1a-adrenoceptor single nucleotide polymorphisms alter receptor pharmacology and biological function - Beilei Lei; Daniel P. Morris; Michael P. Smith; Laura P. Svetkey; Mark F. Newman; Jerome I. Rotter; Thomas A. Buchanan; Stephen M. Beckstrom-Sternberg; Eric D. Green; Debra A. Schwinn (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Distribution Patterns of Mercury in Lakes and Rivers of Northeastern North America - Ian F. Dennis; Thomas A. Clair; Charles T. Driscoll; Neil Kamman; Ann Chalmers; Jamie Shanley; Stephen A. Norton; Steve Kahl (Ecotoxicology, 2005)

Factors Influencing Mercury in Freshwater Surface Sediments of Northeastern North America - Neil C Kamman; Ann Chalmers; Thomas A. Clair; Andrew Major; Richard B. Moore; Stephen A. Norton; James B. Shanley (Ecotoxicology, 2005)

Economic performance of two new potato varieties using a fresh market consignment-packing model - Thomas A. Salaiz; Stephen L. Love; Paul E. Patterson; Joseph F. Guenthner (American Journal of Potato Research, 2005)

Relative Importance of Environmental Stress and Herbivory in Reducing Litter Fall in a Semiarid Woodland - Thomas D. Schuster; Neil S. Cobb; Thomas G. Whitham; Stephen C. Hart (Ecosystems, 2005)

The feline major histocompatibility complex is rearranged by an inversion with a breakpoint in the distal class I region - Thomas W. Beck; Joan Menninger; William J. Murphy; William G. Nash; Stephen J. O’Brien; Naoya Yuhki (Immunogenetics, 2005)

System dynamics modeling for community-based water planning: Application to the Middle Rio Grande - Vincent C. Tidwell; Howard D. Passell; Stephen H. Conrad; Richard P. Thomas (Aquatic Sciences, 2004)

Miscanthus for Renewable Energy Generation: European Union Experience and Projections for Illinois - Emily A. Heaton; Stephen P. Long; Thomas B. Voigt; Michael B. Jones; John Clifton-Brown (Mitigation and Adaptation Strategies for Global Change, 2004)

Principles of Conservation Biology: Recommended Guidelines for Conservation Literacy from the Education Committee of the Society forConservation Biology* - STEPHEN C. TROMBULAK; KRISTIAN S. OMLAND; JULIE A. ROBINSON; JEFFREY J. LUSK; THOMAS L. FLEISCHNER; GLENN BROWN; MEG DOMROESE (Conservation Biology, 2004)

A Comparison of the Efficacy of Pond-Net and Box Sampling Methods in Turloughs - Irish Ephemeral Aquatic Systems - Áine O Connor; Stephen Bradish; Thomas Reed; James Moran; Eugenie Regan; Marjolein Visser; Mike Gormally; Micheline Sheehy Skeffington (Hydrobiologia, 2004)

Stream denitrification and total nitrate uptake rates measured using a field 15 N tracer addition approach - Patrick J. Mulholland; H. Maurice Valett; Jackson R. Webster; Steven A. Thomas; Lee W. Cooper; Stephen K. Hamilton; Bruce J. Peterson (Limnology and Oceanography, 2004)
We measured denitrification and total nitrate uptake rates in a small stream (East Fork of Walker Branch in eastern Tennessee) using a new field 15 N tracer addition and modeling approach that quantifies these rates for entire stream reaches. The field experiment consisted of an 8‐h addition of 99 atom% K 15 NO 3 and a conservative solute tracer. Two 15 N tracer addition experiments were performed on consecutive days, the first under ambient NO 3 − concentrations (23 µg N L −1 ) and the second with a NO 3 − addition of approximately 500 µg N L −1 . We fit first‐order NO 3 − uptake and two‐box denitrification models to the longitudinal measurements of tracer 15 N in dissolved NO 3 − , N 2 , and N 2 O in stream water to determine rates. Total NO 3 − uptake rates were 0.028 m −1 (0.32 µg N m −2 s −1 ) and 0.01 m −1 (1.6 µg N m −2 s −1 ) under ambient NO 3 − and with NO 3 − addition, respectively. Denitrification rates were 0.0046 m −1 (uncertainty range of 0.002 to 0.008 m −1 ) and 9×10 −5 m −1 (uncertainty range of 3 × 10 −5 to 21×10 −5 m −1 ) under ambient NO 3 − and with NO 3 − addition, respectively. Denitrification resulted almost exclusively in N 2 production (>99%) and comprised about 16% (±10%) of total NO 3 − uptake rate under ambient NO 3 − concentrations and about 1% (±1%) of total NO 3 uptake rate with NO 3 − addition. Denitrification rate expressed on a mass flux basis was about 12 µmol m −2 h −1 under ambient NO 3 − concentrations, a value within the range reported for other streams with low NO 3 − concentrations.

Radon fluxes in tropical forest ecosystems of Brazilian Amazonia: night‐time CO 2 net ecosystem exchange derived from radon and eddy covariance methods - Christopher S. Martens; Thomas J. Shay; Howard P. Mendlovitz; Daniel M. Matross; Scott R. Saleska; Steven C. Wofsy; W. Stephen Woodward; Mary C. Menton; José M. S. De Moura; Patrick M. Crill; Osvaldo L. L. De Moraes; Risonaldo L. Lima (Global Change Biology, 2004)
Radon‐222 (Rn‐222) is used as a transport tracer of forest canopy–atmosphere CO 2 exchange in an old‐growth, tropical rain forest site near km 67 of the Tapajós National Forest, Pará, Brazil. Initial results, from month‐long periods at the end of the wet season (June–July) and the end of the dry season (November–December) in 2001, demonstrate the potential of new Rn measurement instruments and methods to quantify mass transport processes between forest canopies and the atmosphere. Gas exchange rates yield mean canopy air residence times ranging from minutes during turbulent daytime hours to greater than 12 h during calm nights. Rn is an effective tracer for net ecosystem exchange of CO 2 (CO 2 NEE) during calm, night‐time hours when eddy covariance‐based NEE measurements are less certain because of low atmospheric turbulence. Rn‐derived night‐time CO 2 NEE (9.00±0.99 μmol m −2 s −1 in the wet season, 6.39±0.59 in the dry season) was significantly higher than raw uncorrected, eddy covariance‐derived CO 2 NEE (5.96±0.51 wet season, 5.57±0.53 dry season), but agrees with corrected eddy covariance results (8.65±1.07 wet season, 6.56±0.73 dry season) derived by filtering out lower NEE values obtained during calm periods using independent meteorological criteria. The Rn CO 2 results suggest that uncorrected eddy covariance values underestimate night‐time CO 2 loss at this site. If generalizable to other sites, these observations indicate that previous reports of strong net CO 2 uptake in Amazonian terra firme forest may be overestimated.

The performance of models relating species geographical distributions to climate is independent of trophic level - Brian Huntley; Rhys E. Green; Yvonne C. Collingham; Jane K. Hill; Stephen G. Willis; Patrick J. Bartlein; Wolfgang Cramer; Ward J. M. Hagemeijer; Christopher J. Thomas (Ecology Letters, 2004)
Species–climate ‘envelope’ models are widely used to evaluate potential climate change impacts upon species and biodiversity. Previous studies have used a variety of methods to fit models making it difficult to assess relative model performance for different taxonomic groups, life forms or trophic levels. Here we use the same climatic data and modelling approach for 306 European species representing three major taxa (higher plants, insects and birds), and including species of different life form and from four trophic levels. Goodness‐of‐fit measures showed that useful models were fitted for >96% of species, and that model performance was related neither to major taxonomic group nor to trophic level. These results confirm that such climate envelope models provide the best approach currently available for evaluating reliably the potential impacts of future climate change upon biodiversity.

Qualification of analytical instruments for use in the pharmaceutical industry: A scientific approach - Surendra K. Bansal; Thomas Layloff; Ernest D. Bush; Marta Hamilton; Edward A. Hankinson; John S. Landy; Stephen Lowes; Moheb M. Nasr; Paul A. St. Jean; Vinod P. Shah (AAPS PharmSciTech, 2004)

Qualification of analytical instruments for use in the pharmaceutical industry: A scientific approach - Surendra K. Bansal; Thomas Layloff; Ernest D. Bush; Marta Hamilton; Edward A. Hankinson; John S. Landy; Stephen Lowes; Moheb M. Nasr; Paul A. St. Jean; Vinod P. Shah (AAPS PharmSciTech, 2004)

Genetically based trait in a dominant tree affects ecosystem processes - Jennifer A. Schweitzer; Joseph K. Bailey; Brian J. Rehill; Gregory D. Martinsen; Stephen C. Hart; Richard L. Lindroth; Paul Keim; Thomas G. Whitham (Ecology Letters, 2004)
Fundamental links between genes and ecosystem processes have remained elusive, although they have the potential to place ecosystem sciences within a genetic and evolutionary framework. Utilizing common gardens with cottonwood trees of known genotype, we found that the concentration of condensed tannins is genetically based and is the best predictor of ecosystem‐level processes. Condensed tannin inputs from foliage explained 55–65% of the variation in soil net nitrogen (N) mineralization under both field and laboratory conditions. Alternative associations with litter lignin, soil moisture or soil temperature were relatively poor predictors of litter decomposition and net N mineralization. In contrast to the paradigm that the effects of genes are too diffuse to be important at the ecosystem‐level, here we show that plant genes had strong, immediate effects on ecosystem function via a tight coupling of plant polyphenols to rates of nitrogen cycling.

Spectroscopic and computational characterization of the nickel-containing F430 cofactor of methyl-coenzyme M reductase - Jennifer L. Craft; Yih-Chern Horng; Stephen W. Ragsdale; Thomas C. Brunold (JBIC Journal of Biological Inorganic Chemistry, 2004)

Downhill running in rats: influence on neutrophils, macrophages, and MyoD+ cells in skeletal muscle - Susan K. Tsivitse; Thomas J. McLoughlin; Jennifer M. Peterson; Eleni Mylona; Stephen J. McGregor; Francis X. Pizza (European Journal of Applied Physiology, 2003)

Landscape Trends in Mid-Atlantic and Southeastern United States Ecoregions - Jerry A. Griffith; Stephen V. Stehman; Thomas R. Loveland (Environmental Management, 2003)

Ecological Monitoring for Assessing the State of the Nearshore and Open Waters of the Great Lakes - Melanie A. Neilson; D. Scott Painter; Glenn Warren; Ronald A. Hites; Ilora Basu; D.V. Chip Weseloh; D. Michael Whittle; Gavin Christie; Richard Barbiero; Marc Tuchman; Ora E. Johannsson; Thomas F. Nalepa; et al. (Environmental Monitoring and Assessment, 2003)

Haplotype diversity in the interleukin-4 gene is not associated with HIV-1 transmission and AIDS progression - William S. Modi; Thomas R. O'Brien; David Vlahov; Susan Buchbinder; Edward Gomperts; John Phair; Stephen J. O'Brien; Cheryl Winkler (Immunogenetics, 2003)

A novel fibrocartilaginous tendon from an elasmobranch fish (Rhinoptera bonasus) - Adam P. Summers; Magdalena M. Koob-Emunds; Stephen M. Kajiura; Thomas J. Koob (Cell and Tissue Research, 2003)

Arsenic resistance in the archaeon "Ferroplasma acidarmanus": new insights into the structure and evolution of the ars genes - Thomas M. Gihring; Philip L. Bond; Stephen C. Peters; Jillian F. Banfield (Extremophiles, 2003)

CaM kinase IIδC phosphorylation of 14-3-3β in vascular smooth muscle cells: Activation of class II HDAC repression - Joel J. Ellis; Thomas G. Valencia; Hong Zeng; L. Don Roberts; Rebecca A. Deaton; Stephen R. Grant (Molecular and Cellular Biochemistry, 2003)

Managing Troubled Data: Coastal Data Partnerships Smooth Data Integration - Stephen S. Hale; Anne Hale Miglarese; M. Patricia Bradley; Thomas J. Belton; Larry D. Cooper; Michael T. Frame; Christopher A. Friel; Linda M. Harwell; Robert E. King; William K. Michener; David T. Nicolson; Bruce G. Peterjohn (Environmental Monitoring and Assessment, 2003)

Gene gun bombardment-mediated expression and translocation of EGFP-tagged GLUT4 in skeletal muscle fibres in vivo - Hans Lauritzen; Christine Reynet; Peter Schjerling; Evelyn Ralston; Stephen Thomas; Henrik Galbo; Thorkil Ploug (Pflügers Archiv - European Journal of Physiology, 2002)

Opioid-insensitive hypoalgesia to mechanical stimuli at sites ipsilateral and contralateral to experimental muscle pain in human volunteers - Thomas Graven-Nielsen; Stephen J. Gibson; René J. Laursen; Peter Svensson; Lars Arendt-Nielsen (Experimental Brain Research, 2002)

Do sediments from coastal sites accurately reflect time trends in water column phytoplankton? A test from Himmerfjärden Bay (Baltic Sea proper) - Thomas S. Bianchi; Erika Engelhaupt; Brent A. McKee; Stephen Miles; Ragnar Elmgren; Susanna Hajdu; Candida Savage; Mark Baskaran (Limnology and Oceanography, 2002)
Long‐term (1977–2000) ecological biomass data for total phytoplankton, diatoms, and cyanobacteria, based on plankton samples from Himmerfjärden Bay (Baltic proper), were compared to the historical sediment record using diagnostic plant pigment biomarkers. Radionuclides ( 210 Pb and 137 Cs) were used to determine chronology, sedimentation, and carbon burial rate. Despite high resolution sampling, using crust‐freeze sampling, of sediment layers representing annual varves, no significant correlations between pigments preserved in sediments and phytoplankton biomass in plankton samples were detected for periods of 1–4 yr. This lack of correspondence was probably at least partly due to the importance of resuspension events in Himmerfjärden. When sedimentary pigments were averaged over longer time intervals (5 yr) averages of annual diatom biomass in the Himmerfjärd inlet were positively correlated to down‐core concentrations of fucoxanthin (r 2 = 0.98) and diatoxanthin (r 2 = 0.62). This indicates that pigment biomarkers can still be used to interpret longer term development of eutrophication‐related blooms in such estuarine systems. In contrast, zeaxanthin concentrations were not significantly correlated (p > 0.05, r 2 = 0.05) to cyanobacterial biomass as a 5–yr average. Using fossil pigments to determine relative differences in phytoplankton biomass composition in the absence of historical ecological patterns of phytoplankton composition can be misleading due to selective losses of pigments such as the epoxy‐carotenoids. However, while the use of fossil pigments in laminated sediments alone may not allow for detailed interpretations of past phytoplankton communities, it does allow for the simple determination of the presence of significant biomass of phytoplankton classes, for which unique biomarker pigments exist.

Haemoglobin and oxygen transport of the West Australian dhufish, Glaucosoma hebraicum Richardson, and other species - F J Stephens; J J Cleary; G Jenkins; B Jones; S R Raidal; J B Thomas (Journal of Fish Diseases, 2002)
To better understand the possible role of deoxygenation of haemoglobin in the pathogenesis of exophthalmos in the West Australian dhufish, Glaucosoma hebraicum Richardson, some oxygen transport properties of haemoglobin from this species were determined and compared with haemoglobin from black bream, Acanthopagrus butcheri (Munro), snapper, Pagrus auratus (Bloch & Schneider) and King George whiting, Sillaginodes punctata (Cuvier). Dhufish had a single haemoglobin with a pronounced Root effect. Snapper and black bream blood had six and five types of haemoglobin, respectively. The magnitude of the Root effect of haemoglobins in the haemolysate was demonstrated by comparing oxygenation and total deoxygenation at pH 8 with relative deoxygenation at pH 6.9. Dhufish haemoglobin demonstrated a large Root effect, with the Root effect of King George whiting, snapper and black bream being of lesser magnitude. Deoxygenation of all haemolysates was more pronounced in the presence of adenosine triphosphate (ATP). Seasonal changes in haematological parameters and ATP content of dhufish blood were not evident. The Root effect is discussed in the context of its possible role in oxygen supply to the retina and adaptation to the fish's habitat and the environment.

Improved Lung Delivery from a Passive Dry Powder Inhaler Using an Engineered PulmoSphere® Powder - Sarma P. Duddu; Steven A. Sisk; Yulia H. Walter; Thomas E. Tarara; Kevin R. Trimble; Andrew R. Clark; Michael A. Eldon; Rebecca C. Elton; Matthew Pickford; Peter H. Hirst; Stephen P. Newman; Jeffry G. Weers (Pharmaceutical Research, 2002)

In Vivo Lung Deposition of Hollow Porous Particles from a Pressurized Metered Dose Inhaler - Peter H. Hirst; Gary R. Pitcairn; Jeff G. Weers; Thomas E. Tarara; Andrew R. Clark; Luis A. Dellamary; Gail Hall; Jolene Shorr; Stephen P. Newman (Pharmaceutical Research, 2002)

The Greening of a Pulp and Paper Mill: International Paper's Androscoggin Mill, Jay, Maine - Marquita Hill; Thomas Saviello; Stephen Groves (Journal of Industrial Ecology, 2002)
Summary International Paper (IP), the world's largest forest products company, owns the Androscoggin Mill, a large pulp and paper mill in Jay, Maine, in the northeastern United States. This case study describes the transformation of the Androscoggin Mill from an object of public opprobrium and conflict to a show‐case for environmental management. In the late 1980s, an 18‐month strike had embittered workers and townspeople and left the mill's reputation in tatters. In response to mill environ‐mental violations, some of which were considered crimes by state regulators, the town of Jay passed its own environmental ordinance to control mill emissions. Early in the 1990s, new management, including two former corporate‐level employ‐ees, sought to change the mill's business approach and turn the Androscoggin Mill into IP's best environmental performer. The initial emphasis on establishing and maintaining compliance was expanded to include aggressive pollution prevention efforts that led to cooperative projects with the Maine Department of Environmental Protection, the U.S. Environmental Protection Agency, and stakeholder groups. The mill's ap‐proach in the 1990s evolved further to essentially follow prin‐ciples of industrial ecology. New approaches focused on “clos‐ing the loop” by finding beneficial uses for previously landfilled wastes, replacements for most hazardous chemicals, and re‐ductions in solid and hazardous waste generation. The mill also pursued the establishment of symbiotic relationships with a facility that began using a mill by‐product on‐site and an on‐site natural gas burning facility that provided part of the mill's steam demand. IP also established a public advisory committee in 1992 to advise management on operational and “big‐picture” issues, which later included the application of sustain‐ability criteria to the mill. IP has since formed community advisory committees at each of their integrated pulp and paper mills.

Rinderpest and peste des petits ruminants viruses exhibit neurovirulence in mice - Sareen E Galbraith; Stephen McQuaid; Louise Hamill; L. Pullen; Thomas Barrett; S. Louise Cosby (Journal of NeuroVirology, 2002)

Pathogenesis and epidemiology of spontaneous exophthalmos in the West Australian dhufish, Glaucosoma hebraicum Richardson - F J Stephens; J J Cleary; G Jenkins; B Jones; S R Raidal; J B Thomas (Journal of Fish Diseases, 2001)
The West Australian dhufish, Glaucosoma hebraicum Richardson (family Glaucosomatidae) is a potentially valuable aquaculture species, but spontaneous exophthalmos is common in freshly caught and cultured dhufish. To investigate the epidemiology and pathogenesis of exophthalmos in tanks of wild‐caught and captive‐bred dhufish, records of culture conditions, the prevalence of lesions and pathological examinations were used to study the disease and associated environmental and management factors. Naturally occurring cases of exophthalmos that were examined were mostly unilateral and occurred more frequently in summer months during periods of increasing water temperature. In 15 affected eyes that were examined histologically gas bubbles and haemorrhages were consistently present in the choroid. In some, gas bubbles and haemorrhage were also present in retrobulbar tissues associated with perforation of the sclera. Oxygen concentrations were measured in 12 exophthalmic eyes and concentrations of 50–73% were recorded in gas bubbles in the anterior chamber of three of these that were acute cases. Very low oxygen tensions were recorded at the retinal–vitreal junction of four eyes with retrobulbar haemorrhages indicating that there may have been disruption of arterial blood supply to the choroid in chronic lesions or with perforation of the sclera. The results of experiments to determine the significance of exercise, high water temperature, sudden increases in light intensity, fish handling or tank cleaning indicate that exercise and/or high water temperature (25.5 °C) may be important risk factors for the development of exophthalmos in dhufish. Possible mechanisms for the formation of gas bubbles and haemorrhage in the choroid are discussed.

Primary productivity of planet earth: biological determinants and physical constraints in terrestrial and aquatic habitats - Richard J. Geider; Evan H. Delucia; Paul G. Falkowski; Adrien C. Finzi; J. Philip Grime; John Grace; Todd M. Kana; Julie La Roche; Stephen P. Long; Bruce A. Osborne; Trevor Platt; I. Colin Prentice; et al. (Global Change Biology, 2001)

Opposite association of two PPARG variants with cancer: overrepresentation of H449H in endometrial carcinoma cases and underrepresentation of P12A in renal cell carcinoma cases - Wendy Smith; Xiao-Ping Zhou; Keisuke Kurose; Xin Gao; Farida Latif; Todd Kroll; Kokichi Sugano; Stephen Cannistra; Steven Clinton; Eamonn Maher; Thomas Prior; Charis Eng (Human Genetics, 2001)

Priscoan (4.00–4.03 Ga) orthogneisses from northwestern Canada - by Samuel A. Bowring and Ian S. Williams: discussion - Martin J. Whitehouse; Thomas F. Nagler; Stephen Moorbath; Jan D. Kramers; Balz S. Kamber; Robert Frei (Contributions to Mineralogy and Petrology, 2001)

Diverse prevalence of large deletions within the OA1 gene in ocular albinism type 1 patients from Europe and North America - M. Bassi; Arthur Bergen; Pierre Bitoun; Stephen Charles; Maurizio Clementi; Richard Gosselin; Jane Hurst; Richard Lewis; Birgit Lorenz; Thomas Meitinger; Ludwine Messiaen; Rajkumar Ramesar; et al. (Human Genetics, 2001)

Flies that are parasitoids of a marine snail: the larviposition behaviour and life cycles of Sarcophaga megafilosia and Sarcophaga meiofilosia - Stephen C. McKillup; Ruth V. McKillup; Thomas Pape (Hydrobiologia, 2000)

New applications of photoacoustics to the study of photosynthesis - Stephen K. Herbert; Tao Han; Thomas C. Vogelmann (Photosynthesis Research, 2000)

Responses of Physical, Chemical, and Biological Indicators of Water Quality to a Gradient of Agricultural Land Use in the Yakima River Basin, Washington - Thomas F. Cuffney; Michael R. Meador; Stephen D. Porter; Martin E. Gurtz (Environmental Monitoring and Assessment, 2000)

A synoptic climatology of derecho producing mesoscale convective systems in the North‐Central Plains - Mace L. Bentley; Thomas L. Mote; Stephen F. Byrd (International Journal of Climatology, 2000)

Quantitative analysis of thymosin α1 in human serum by LC-MS/MS - Cynthia W. Tuthill; Alfred Rudolph; Yang Li; Beijing Tan; Thomas J. Fitzgerald; Stephen R. Beck; Yong-Xi Li (AAPS PharmSciTech, 2000)

Quantitative analysis of thymosin α1 in human serum by LC-MS/MS - Cynthia W. Tuthill; Alfred Rudolph; Yang Li; Beijing Tan; Thomas J. Fitzgerald; Stephen R. Beck; Yong-Xi Li (AAPS PharmSciTech, 2000)

Seasonal soil‐surface carbon fluxes from the root systems of young Pinus radiata trees growing at ambient and elevated CO 2 concentration - Stephen M. Thomas; Freeman J. Cook; David Whitehead; John A. Adams (Global Change Biology, 2000)
Summary Elevated atmospheric CO 2 concentration may result in increased below‐ground carbon allocation by trees, thereby altering soil carbon cycling. Seasonal estimates of soil surface carbon flux were made to determine whether carbon losses from Pinus radiata trees growing at elevated CO 2 concentration were higher than those at ambient CO 2 concentration, and whether this was related to increased fine root growth. Monthly soil surface carbon flux density ( f ) measurements were made on plots with trees growing at ambient (350) and elevated (650 μmol mol −1 ) CO 2 concentration in large open‐top chambers. Prior to planting the soil carbon concentration (0.1%) and f (0.28 μmol m −2 s −1 at 15 °C) were low. A function describing the radial pattern of f with distance from tree stems was used to estimate the annual carbon flux from tree plots. Seasonal estimates of fine root production were made from minirhizotrons and the radial distribution of roots compared with radial measurements of f . A one‐dimensional gas diffusion model was used to estimate f from soil CO 2 concentrations at four depths. For the second year of growth, the annual carbon flux from the plots was 1671 g y −1 and 1895 g y −1 at ambient and elevated CO 2 concentrations, respectively, although this was not a significant difference. Higher f at elevated CO 2 concentration was largely explained by increased fine root biomass. Fine root biomass and stem production were both positively related to f. Both root length density and f declined exponentially with distance from the stem, and had similar length scales. Diurnal changes in f were largely explained by changes in soil temperature at a depth of 0.05 m. Ignoring the change of f with increasing distance from tree stems when scaling to a unit ground area basis from measurements with individual trees could result in under‐ or overestimates of soil‐surface carbon fluxes, especially in young stands when fine roots are unevenly distributed.

An integrated physical and genetic map of the PLS locus interval on Chromosome 11q14 - Thomas C. Hart; Stephen J. Walker; Donald W. Bowden; Patricia S. Hart; Scott A. Callison; Peggy L. Bobby; Erhan Firatli (Mammalian Genome, 2000)

The Distribution of Nearshore Fishes in Kelp and Eelgrass Communities in Prince William Sound, Alaska: Associations with Vegetation and Physical Habitat Characteristics - Thomas A. Dean; Lewis Haldorson; David R. Laur; Stephen C. Jewett; Arny Blanchard (Environmental Biology of Fishes, 2000)

Towards a US GOOS: A Synthesis of Lessons Learned from Previous Coastal Monitoring Efforts - Stephen Weisberg; Thomas Hayward; Muriel Cole (Oceanography, 2000)

V4 region of small subunit rDNA indicates polyphyly of the Fellodistomidae (Digenea) which is supported by morphology and life-cycle data - Kathryn A. Hall; Thomas H. Cribb; Stephen C. Barker (Systematic Parasitology, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Growth, loss, and vertical distribution of Pinus radiata fine roots growing at ambient and elevated CO 2 concentration - Stephen M. Thomas; David Whitehead; JefF. B. Reid; Freeman J. Cook; JohN. A. Adams; AlaN. C. Leckie (Global Change Biology, 1999)
Increased below‐ground carbon allocation in forest ecosystems is a likely consequence of rising atmospheric CO 2 concentration. If this results in changes to fine root growth, turnover and distribution long‐term soil carbon cycling and storage could be altered. Bi‐weekly measurements were made to determine the dynamics and distribution of fine roots ( Pinus radiata trees growing at ambient (350 μmol mol –1 ) and elevated (650 μmol mol –1 ) CO 2 concentration in large open‐top chambers. Measurements were made using minirhizotrons installed horizontally at depths of 0.1, 0.3, 0.5 and 0.9 m. During the first year, at a depth of 0.3 m, the increase in relative growth rate of roots occurred 6 weeks earlier in the elevated CO 2 treatment and the maximum rate was reached 10 weeks earlier than for trees in the ambient treatment. After 2 years, cumulative fine root growth ( P t ) was 36% greater for trees growing at elevated CO 2 than at ambient CO 2 concentration, although this difference was not significant. A model of root growth driven by daily soil temperature accounted for between 43 and 99% of root growth variability. Total root loss ( L t ) was 9% in the ambient and 14% in the elevated CO 2 treatment, although this difference was not significant. Root loss was greatest at 0.3 m. In the first year, 62% of fine roots grown between mid‐summer and late‐autumn disappeared within a year in the elevated CO 2 treatment, but only 18% in the ambient CO 2 treatment ( P L t to time accounted for between 74 and 99% of the variability. Root cohort half‐lives were 951 d for the ambient and 333 d for the elevated treatment. Root length density decreased exponentially with depth in both treatments, but relatively more fine roots grown in the elevated CO 2 treatment tended to occur deeper in the soil profile.

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Managing Scientific Data: the EMAP Approach - Stephen S. Hale; Melissa M. Hughes; John F. Paul; R. Scott McAskill; Steven A. Rego; David R. Bender; Nancy J. Dodge; Thomas L. Richter; Jane L. Copeland (Environmental Monitoring and Assessment, 1998)

Inhibition by inositoltetrakisphosphates of calcium- and volume-activated Cl - currents in macrovascular endothelial cells - B. Nilius; Jean Prenen; Thomas Voets; J. Eggermont; Karol S. Bruzik; Stephen B. Shears; Guy Droogmans (Pflügers Archiv - European Journal of Physiology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Spectral karyotyping refines cytogenetic diagnostics of constitutional chromosomal abnormalities - E. Schröck; T. Veldman; Hesed Padilla-Nash; Y. Ning; Jack Spurbeck; Syed Jalal; Lisa G. Shaffer; Peter Papenhausen; Chahira Kozma; Mary C. Phelan; Eigil Kjeldsen; Stephen A. Schonberg; et al. (Human Genetics, 1997)

Thyroid autoantibody measurement by enzyme immunoassay - D. Charles Stephen; Nihal Thomas; R. Selvakumar; M. S. Seshadri; A. S. Kanagasabapathy (Indian Journal of Clinical Biochemistry, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Scale-up of Adhesive Transdermal Drug Delivery Systems - Glenn A. Van Buskirk; Mario A. González; Vinod P. Shah; Scott Barnhardt; Colin Barrett; Stephen Berge; Gary Cleary; Keith Chan; Gordon Flynn; Thomas Foster; Robert Gale; Raymond Garrison; et al. (Pharmaceutical Research, 1997)

Responses of huvec and EAhy926 to heparin and fibroblast growth factors - Stephen Thomas; Elaine Gray; C. Jane Robinson (In Vitro Cellular & Developmental Biology - Animal, 1997)

Distribution of contact force during impact to the hip - Stephen N. Robinovitch; Wilson C. Hayes; Thomas A. McMahon (Annals of Biomedical Engineering, 1997)

Population Viability Analysis of the Florida Manatee ( Trichechus manatus latirostris ), 1976–1991 - Miriam Marmontel; Stephen R. Humphrey; Thomas J. O'Shea (Conservation Biology, 1997)
Recent development of age‐determination techniques for Florida manatees (Trichechus manatus latirostris) has permitted derivation of age‐specific data on reproduction and survival of a sample of 1212 carcasses obtained throughout Florida from 1976–1991. Population viability analysis using these data projects a slightly negative growth rate (−0.003) and an unacceptably low probability of persistence (0.44) over 1000 years. The main factors affecting population projections were adult survival and fecundity. A 10% increase in adult mortality would drive the population to extinction over a 1000‐year time scale, whereas a 10% decrease in adult mortality would allow slow population growth. A 10% decrease in reproduction would also result in extinction. We conclude that management must focus on retaining and improving the conditions under which manatee demography operates. The major identified agent of mortality is boat‐manatee collisions, and rapidly increasing numbers of humans and registered boats portend an increase in manatee mortality. Zoning of manatee‐occupied waters for reductions in boating activity and speed is essential to safeguard the manatee population. If boating regulations being implemented by the state of Florida in each of 13 key coastal counties are completed, enforced, and effective, manatees and human recreation could coexist indefinitely. If regulation is unsuccessful, the Florida manatee population is likely to decline slowly toward extinction.

Restoring Ecosystem Health in Ponderosa Pine Forests of the Southwest - W. Wallace Covington; Peter Z. Fulé; Margaret M. Moore; Stephen C. Hart; Thomas E. Kolb; Joy N. Mast; Stephen S. Sackett; Michael R. Wagner (Journal of Forestry, 1997)

Postlepidapedon Zdzitowiecki, 1993 and Gibsonivermis n. g. (Digenea: Lepocreadiidae) from fishes of the southern Great Barrier Reef, Australia, and their relationship to Intusatrium Durio & Manter, 1968 - Rodney A. Bray; Thomas H. Cribb; Stephen C. Barker (Systematic Parasitology, 1997)

Physiologically based pharmacokinetic/pharmacodynamic modeling of the toxicologic interaction between carbon tetrachloride and Kepone - H. A. El-Masri; Russell S. Thomas; G. Rob Sabados; Jenny K. Phillips; Alexander A. Constan; Stephen A. Benjamin; Melvin E. Andersen; Harihara M. Mehendale; Raymond S. H. Yang (Archives of Toxicology, 1996)

Organic aciduria and butyryl CoA dehydrogenase deficiency in BALB/cByJ mice - Stephen P. Schiffer; Michal Prochazka; Peter F. Jezyk; Thomas H. Roderick; Marc Yudkoff; Donald F. Patterson (Biochemical Genetics, 1989)

Comparison of the protection given by selenite, selenomethionine and biological selenium against the renotoxicity of mercury - Laszlo Magos; Thomas W. Clarkson; Stephen Sparrow; Anthony R. Hudson (Archives of Toxicology, 1987)

The half-cycle sinusoid as an alternative defibrillating waveform in low-energy applications - Thomas W. Moore; Frank N. DiMeo; Stephen E. Dubin (Annals of Biomedical Engineering, 1977)